Temperature history determines the adult size and maturation rates in seasonal cohorts of Loligo forbesii squid - A.M. Power; M.A. Collins; A. Arkhipkin; S. Wangvoralak; M. Petroni; G.J. Pierce (Estuarine, Coastal and Shelf Science, 2026)

Marine migration influences mercury accumulation in anadromous Arctic char ( Salvelinus alpinus ) - Isabel R. Hilgendag; Michael Power; Mehdi M. Aqdam; Christopher W. Lewis; Zoya Martin; Ashley D. Ehrman; Heidi K. Swanson (Journal of Fish Biology, 2026)
Mercury (Hg) is a globally distributed toxic metal present in northern natural environments that biomagnifies in food webs and bioaccumulates in apex predator fish, such as Arctic char ( Salvelinus alpinus )—an iteroparous species with a circumpolar distribution. Arctic char exhibit a variety of life history types, with the migrating, anadromous life‐history type supporting many subsistence and small‐scale commercial fisheries in the Arctic and sub‐Arctic. Despite anadromous Arctic char having generally lower Hg concentrations than non‐anadromous conspecifics, the mechanisms that contribute to significant inter‐individual differences within this life‐history group have not been well investigated. A total of 119 anadromous Arctic char were captured from inner Frobisher Bay on Baffin Island near Iqaluit, Nunavut, in 2018 and 2019, to investigate causes of inter‐individual differences in Hg concentrations in the anadromous life‐history type of Arctic char. As hypothesized, Hg concentrations significantly decreased with increasing marine prey reliance; marine prey reliance—quantified using δ 34 S ratios—explained 93% of the variability in Hg. Arctic char that relied more on marine (vs freshwater) prey had lower Hg concentrations. Delta 34 S ratios and average somatic growth rate (size‐at‐age) were the best predictors of Hg concentrations among the set of biological variables assessed, and both were negatively related to Hg concentrations in common age groups (i.e., ages 9–13). For samples that had migration data available, Hg concentration increased with age‐at‐first migration ( R 2 = 0.32) and decreased with number of marine migrations ( R 2 = 0.57), suggesting that plasticity in life history tactics affects Hg concentrations in anadromous Arctic char. Overall, results indicate that differences in habitat use and feeding environment (i.e., freshwater vs. marine) play a significant role in determining Hg bioaccumulation in anadromous Arctic char.

Incorporating CT-Derived Body Composition Analysis Into the Global Leadership Initiative on Malnutrition Criteria Is Associated With Overall Survival: Findings From an International Cancer Cohort - Clodagh Scannell; Erin Stella Sullivan; Ross D. Dolan; Josh McGovern; Marie Fallon; Barry J. Laird; Derek G. Power; Aoife M. Ryan (Journal of the Academy of Nutrition and Dietetics, 2026)

Freshwater biodiversity in a rapidly changing Arctic: An expert horizon scan of key research questions - Joseph M. Culp; Michael Power; Kirsten S. Christoffersen; Willem Goedkoop; Kimmo K. Kahilainen; Milla Rautio; Fernando Chaguaceda; Marie-Pier Hébert; Sanne M. Moedt; Dermot Antoniades; Simon Belle; Daniel Bolnick; et al. (Ambio, 2026)
Arctic freshwater biodiversity is rapidly changing due to climate warming, resource extraction, infrastructure development, and landscape transformation. To improve understanding, predict future responses, and inform policy formulation, research needs must be clearly identified. Using a horizon scan survey, Arctic freshwater experts from government, international agencies, and Indigenous Peoples identified 77 biodiversity research questions with 17 highlighted as most important for near term assessment. These questions span nine thematic categories: biodiversity and taxonomic challenges, hydrological change, productivity and food webs, ecosystem connectivity, methods, monitoring and assessment, permafrost change, winter ecology, anthropogenic development, and Indigenous Knowledge. Climate change emerged as the major driver among all categories and research questions. A key priority identified was the urgent need for long-term, harmonized monitoring programs among Arctic countries. Multiple knowledge gaps detected suggest that circumpolar research collaborations are required to tackle these issues.

Nutrient Enrichment Increases Grassland Biomass Sensitivity to Interannual Precipitation Variation - Ingrid J. Slette; Eric W. Seabloom; Carlos Alberto Arnillas; Jonathan D. Bakker; Dana Blumenthal; Jane A. Catford; Scott L. Collins; Nico Eisenhauer; Philip A. Fay; Magda Garbowski; Sylvia Haider; W. Stanley Harpole; et al. (Global Change Biology, 2026)
Primary production underpins much of ecosystem functioning and is often limited by nutrient and water availability. Ongoing global increases in nutrient inputs and interannual precipitation variability are thus likely to impact primary production, with unclear consequences for interannual variability in plant biomass. We used data from 35 grasslands in the Nutrient Network coordinated fertilization experiment to test if nutrient addition alters the response of plant biomass to year‐to‐year variation in growing season precipitation, and whether the effects of nutrient addition vary with factors such as site aridity or plant community composition. Nutrient addition increased biomass (by an average of 46% across sites), rain‐use efficiency (by 48%), and the sensitivity of biomass to interannual variation in precipitation (i.e., larger increase in biomass in wet years; by 13%), but did not change the strength of the interannual precipitation‐biomass correlation. Both sensitivity and correlation strength were higher in more arid sites, regardless of nutrient addition. These results suggest that grassland ecosystem functioning may become more variable from year to year as nutrient enrichment increases biomass sensitivity to precipitation and precipitation becomes more variable.

Extreme environmental conditions are associated with poor recruitment of an estuarine sportfish - Manuel E. Coffill-Rivera; Zhilong Liu; John C. Lehrter; Brian Dzwonkowski; Jason M. Cope; Julie M. Gross; John Mareska; Sean P. Powers (Fisheries Research, 2026)

Coping with marine heatwaves: Tissue‐specific neuroendocrine and immune adjustments in small‐spotted catsharks - Sandra Martins; Rute Felix; Catarina Pereira Santos; Rui Rosa; Deborah M. Power (Journal of Fish Biology, 2026)
Rising ocean temperatures disrupt neuroendocrine–immune interactions in vertebrates. Neuroendocrine gene expression in the liver, spleen, intestine, blood cells and epigonal organ was examined in small‐spotted catsharks ( Scyliorhinus canicula ) exposed to a 30‐day simulated marine heatwave. Correlations among neuroendocrine genes, immune‐ and iron‐related genes, plasma biochemistry and leukocyte assays revealed tissue‐specific expression patterns, reduced inter‐individual variability and coordinated transcriptional modulation across tissues. Overall, catsharks exhibited integrated adjustments to thermal stress, most likely to balance metabolic demands with immune resilience.

A systematic literature inventory on the interaction between dietary factors and environmental chemical exposures for nervous system health outcomes - Chelsea A. Weitekamp; Caleb Watson; Ellen Hata; Kirstin Hester; Urmila P. Kodavanti; Christopher Lau; David M. Lehmann; Colette N. Miller; Rachel M. Shaffer; Fatima Soliman; Martha Powers; Francesca M. Branch (Food and Chemical Toxicology, 2026)

Multifactorial neural disruption in the brain of the Senegalese sole (Solea senegalensis) under ocean acidification - Rita A. Costa; Aurora Olvera; Sergiy Sylantyev; Peter C. Hubbard; Manuel Manchado; Deborah M. Power; Zélia Velez (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Directed evolution of Gram-negative Klebsiella michiganensis M5al for desiccation tolerance and survivability of a spray-drying encapsulation process - Benjamin M. Arbaugh; Emily M. Makeev; Matthew L. Cope-Arguello; Tiffany M. Lowe-Power; Tina Jeoh (Systems Microbiology and Biomanufacturing, 2026)
Spray drying is a scalable method for producing dry microbial inoculants, but Gram-negative bacteria often exhibit poor survival under desiccation stress. We employed a directed-evolution approach to improve the survivability of diazotroph Klebsiella michiganensis M5al during spray-drying encapsulation in cross-linked alginate microcapsules (CLAMs). Wildtype K. michiganensis M5al was serially passaged through the CLAMs spray-drying process under incrementally increasing selection pressure. Viable cell density in powders improved over 1000-fold compared to baseline, reaching 3.07 × 10 10 CFU/g over the course of the directed evolution experiment. Paired trials confirmed a statistically significant increase in survival of evolved isolates relative to the parental strain (mean difference of 1.39 log 10 , P < 0.05). Whole-genome sequencing and analysis using breseq identified candidate mutations associated with desiccation tolerance, including a single point mutation in the phosphoenolpyruvate carboxylase gene ( pepC ), suggesting a potential link between central carbon metabolism and stress adaptation. These results demonstrate that genetic adaptation can rapidly enhance microbial fitness under industrial drying conditions without modifying formulation, providing a practical strategy for improving the manufacturability and deployment of Gram-negative microbial biostimulants and related products.

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Stretch–shortening cycles mitigate single muscle fibre power deficits following a two-week immobilization of the rat hindlimb - Alexander M. Zero; Geoffrey A. Power (Journal of Muscle Research and Cell Motility, 2026)

A critical review of potential modifiers of air pollutant associations with dementia and related outcomes - JeongWon Han; Yina Li; Sangji Lee; Katie M. Lynch; Erin E. Bennett; Qi Ying; Eun Sug Park; Richard L. Smith; James D. Stewart; Eric A. Whitsel; Melinda C. Power; Xiaohui Xu (NeuroToxicology, 2026)

Understanding the impacts of hydropower development on people, fish and the environment on the Madeira River of Amazonia, Brazil - Shannon H. Clarke; Maria Clara B. T. Cavalcanti; Vivian M. Nguyen; Taylor D. Ward; Eduardo G. Martins; Michael Power; Gustavo Hallwass; Priscila F. M. Lopes; Steven J. Cooke (Environmental Management, 2026)

Metal ecotoxicity in sea anemones: Accumulation, effects, and knowledge gaps - Juliano M. Vilke; Deborah M. Power; Cármen S.V. de Sousa; Nélia C. Mestre (Marine Pollution Bulletin, 2026)

Millennial-scale fire and climate dynamics in the world's largest tropical wetland show emerging fire threat to flooded ecosystems - Bronwen S. Whitney; Danilo M. Neves; Nicholas J.D. Loughlin; Carlos D'Apolito; Carla Coblinski Tavares; Emma P. Hocking; Francis E. Mayle; Mitchell J. Power; Aguinaldo Silva; Mario L. Assine (Global and Planetary Change, 2026)

Classification of European Illex coindetii and Loligo forbesii Squid Stocks by Trace Element Analysis of Statoliths - Bianca T. C. Bobowski; Anne Marie Power; Finlay Burns; Pierluigi Carbonara; Danila Cuccu; Maria Cristina Follesa; Klaus Peter Jochum; Ana Moreno; Inna M. Sokolova; Maria Valls; Daniel Oesterwind (Fisheries Management and Ecology, 2026)
We investigated whether statolith microchemistry analysis could classify ommastrephid and loliginid squid species into fishery stocks. Statolith nucleus (early life stage) and edge (life stage at time before catch) of Illex coindetii (Verany, 1839) and Loligo forbesii (Steenstrup, 1856) from various areas of the North East Atlantic Ocean and Mediterranean Sea during 2021–2022 were analysed using laser ablation ICP‐MS to measure values of 11 trace elements (Na, Mg, Mn, Fe Co, Cu, Zn, Sr., Ba, Pb and U) next to calcium. Four stocks were categorised for I. coindetii and five stocks for L. forbesii amongst sample areas. Common hatching areas and migration into distinct fishing regions were also identified. Our results provide substantial information to sustainably manage fisheries for both species in European waters by providing stock definitions, spawning periods and migration patterns.

Organic-inorganic carbon cycling: Implications for CO2 mineralization of brucite-bearing mine tailings - Justin A. Lockhart; Ian M. Power; Kwon Rausis; Shaheen Akhtar; Robert Caldwell; David French (International Journal of Greenhouse Gas Control, 2026)

Multi-millennial reconstruction of fire return intervals from a fynbos – Afrotemperate forest ecotone in the Cape Floristic Region, South Africa: Paleoecological implications for present-day management - Stella G. Mosher; Mitchell J. Power; Lynne J. Quick; Brian M. Chase; Torsten Haberzettl; Thomas Kasper; Simon C. Brewer; David R. Braun; J. Tyler Faith (Global and Planetary Change, 2026)

Nutrient Transfer Dynamics of Anadromous Alewives (Alosa pseudoharengus) in Freshwater Spawning and Nursery Habitats - Robert E. Vincent; John M. Logan; John J. Sheppard; Michael Power; Stephen T. Hurley; Kevin Bennett (Estuaries and Coasts, 2026)
River herring (alewife, Alosa pseudoharengus and blueback herring, A . aestivalis ) can act as vectors of nutrient transfer between marine and freshwater environments. Adult river herring can transfer marine-derived nutrients to freshwater ecosystems during spawning migrations through excretions and direct consumption of adults, eggs, and early phase juveniles by freshwater scavengers and predators. Adults and juveniles can transfer nutrients derived during freshwater residency back to the marine environment following emigration and the same excretion and consumption mechanisms. Potential nutrient transfers were assessed by applying carbon, nitrogen, and sulfur stable isotope analyses to a collection of juvenile and adult alewives, baseline food web components, and freshwater fish predators in three ponds in southeastern Massachusetts USA. Out-migrating adult alewife tissue stable isotope values were lower for both carbon and sulfur but higher for nitrogen than in-migrating conspecifics reflecting incorporation of freshwater-derived nutrients. Most juvenile alewife stable isotope values were at steady state with freshwater food webs at the time of sampling reflecting additional export of freshwater-derived nutrients with their eventual emigration to the marine environment. Stable isotope-based detection of marine-derived nutrients in freshwater predators was limited to catadromous elvers ( Anguilla rostrata ), anadromous white perch ( Morone americana ), and semi-anadromous yellow perch ( Perca flavescens ) with no marine-derived nutrients detected in resident freshwater fish predators. However, juvenile alewives were observed in stomachs of smallmouth ( Micropterus dolomieu ) and largemouth bass ( M . nigricans ). Results further inform current alewife ecosystem-level interactions with the marine and freshwater environments that they occupy during different life history phases for the many coastal watersheds in New England.

Retrogressive Thaw Slumps Produce a Changing Disturbance Regime for Arctic Stream Invertebrates - Maria Dolan; Jordan Musetta‐Lambert; Krista S. Chin; Steven V. Kokelj; Suzanne E. Tank; Jennifer Lento; Michael Power; Joseph M. Culp (Global Change Biology, 2026)
For many Arctic rivers and streams, climate‐driven intensification of permafrost thaw slumping is a major source of disturbance to aquatic habitats. Thaw slumps are dynamic landforms that severely increase total suspended solids (TSS) and nutrients in downstream reaches and can persist over decades. Effects may differ in magnitude as slumps cycle through periods of higher and lower activity, with expansion of retrogressive slumps increasing over time. Increases in TSS are known to cause reduced invertebrate abundance and diversity in impacted watersheds; however, it remains unclear if water quality and critical aquatic biodiversity have recovered after prolonged exposure to slumps. Here, we examined decadal‐scale effects of slumps and environmental change on benthic macroinvertebrates (BMI) by comparing environmental and BMI data collected between 2010–2014 and a recent sampling campaign from 2021. High TSS and nutrient concentrations observed during 2010–2014 persisted in slump‐impacted sites in 2021, with no significant change in TSS and total nutrient concentrations after the 10‐year exposure period. TSS continued to act as a nonspecific stressor on BMI, as abundance remained significantly lower in impacted streams compared to reference streams. Although total abundance within reference and impacted sites did not differ significantly between sampling periods, abundance and richness of disturbance tolerant taxa was greater in 2021 as compared to 2010–2014 across all sites, with differences linked to lower precipitation in 2021. These community compositional changes were reflected in increased Shannon‐Weiner diversity between sampling campaigns. Overall, the number of thaw slumps upstream was an important driver of both BMI abundance and diversity across sampling periods and will likely continue to be an important determinant of benthic macroinvertebrate communities as the number and size of thaw slumps continues to increase across the circumpolar Arctic.

Non-communicating abomasal (gastric) diverticulum in a 7-day-old bull calf: a case report - Cassandra M. Powers (Journal of Comparative Pathology, 2026)

Association of midlife air pollution and road proximity exposure with 29-year cognitive decline - Melinda C. Power; Ziwei Song; Annie Chen; Katie M. Lynch; Naa Adoley Parker-Allotey; Erin E. Bennett; Xiaohui Xu; Eric A. Whitsel; Richard L. Smith; James D. Stewart; Eun Sug Park; Qi Ying; et al. (NeuroToxicology, 2025)

Ambient air pollution and incident dementia: exploration of relevant exposure windows - Melinda C. Power; Katie M. Lynch; Vixey Fang; Qi Ying; Eun Sug Park; Richard L. Smith; James D. Stewart; Jeff D. Yanosky; Eric A. Whitsel; Xiaohui Xu (Environmental Research, 2025)

Pre- and post-move exposure to air pollution and neighborhood socioeconomic status - Chelsea Liu; Erin E. Bennett; Katie M. Lynch; Xiaohui Xu; Eun Sug Park; Qi Ying; Richard L. Smith; James D. Stewart; Eric A. Whitsel; Joel D. Kaufman; Emma K. Stapp; Melinda C. Power (Science of The Total Environment, 2025)

Incorporating enhanced rock weathering into sustainable forest management - Minger Guo; Ian M. Power; Shaun A. Watmough; Adam S. Gorgolewski; Larissa M.M. Wallisch; Jonathan Spence; Sasha Wilson (Journal of Environmental Management, 2025)

Mount Spurr volcano, August 18, 1992: The eruption heard around Alaska - Alexandra M. Iezzi; John A. Power (Bulletin of Volcanology, 2025)

Evaluating climatic and anthropogenic drivers of fire activity over four millennia at Eilandvlei, southern Cape coast, South Africa - Stella G. Mosher; Mitchell J. Power; Brian M. Chase; Lynne J. Quick; Torsten Haberzettl; Thomas Kasper; David R. Braun; J. Tyler Faith (Quaternary Science Reviews, 2025)

Multidimensional characterization of microplastic pollution in subtropical urban soils: Combining geospatial analysis and polymer risk indexing - Aolei Du; Yanjun Li; Qiying Jian; Kai Zhang; Yutang Luo; Jun Yan; Peixin Du; Deborah M. Power; Ying Li; Yibing Ma (Journal of Hazardous Materials, 2025)

Carbon dioxide supply and scaling constraints on direct air capture using calcium oxide powder - Lance Dostie; Ian M. Power; Kwon Rausis (Journal of Cleaner Production, 2025)

Composition, Growth, Succession, and Function in the Cladophora Microbiome: Insights From Quantitative Stable Isotope Probing and NanoSIMS Imaging - Raina M. Fitzpatrick; Bruce A. Hungate; Mary Power; Megan Foley; Ty Samo; Egbert Schwartz; Micheala Hayer; Peter K. Weber; Jennifer Pett‐Ridge; Jane C. Marks (Environmental Microbiology, 2025)
The branching green macroalga Cladophora glomerata and its epiphytic microbiome dominate summer biomass in the Eel River, a Northern California river under Mediterranean (summer drought, winter rain) seasonality. Green Cladophora streamers proliferate in early summer, then change to yellow and then red‐brown as epiphyte loads increase. We characterised successional changes in epiphytic bacteria on Cladophora , examining both community composition and growth rates, using quantitative Stable Isotope Probing (qSIP) and 16S rRNA gene amplicon sequencing. The number of bacterial taxa increased with succession while growth rates peaked in the middle stage. NanoSIMS imaging confirmed high sulphur (S) concentrations in Cladophora cell walls relative to surrounding biomass, coinciding with a bloom of sulphur bacteria (bacteria that reduce or oxidise sulphur/sulphates). In general, relative abundances and growth rates were independent, indicating that either metric alone is insufficient for understanding how taxonomy and functional groups affect ecosystem processes. For instance, the relative abundance of nitrogen fixers peaked in the late summer when their relative growth rates were slowest. Such patterns may be driven by space competition limiting growth. Together, changes in abundance and relative growth rates suggest different limiting factors for different functional groups in the Cladophora microbiome at multiple successional stages.

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Sailing together: A review of the pelagic Sargassum microbiome - D.D. Cox; A.K. Stiffler; V. Hervé; M. Léger-Pigout; L.C. Powers; P.J. Lopez; O.A. Sosa; R.J. Parsons (Harmful Algae, 2025)

Quantifying the contribution of biogenic iron sulfides to magnesite formation in the Basque Lakes, British Columbia, Canada - Colton J. Vessey; Maija J. Raudsepp; Maria L. Arizaleta; Sasha Wilson; Anna L. Harrison; Kelly J. Rozanitis; Helen E.A. Brand; Kurt O. Konhauser; Kwon Rausis; Ian M. Power (Chemical Geology, 2025)

Towards the Rational Use of Plastic Packaging to Reduce Microplastic Pollution: A Mini Review - Evmorfia Athanasopoulou; Deborah M. Power; Emmanouil Flemetakis; Theofania Tsironi (Journal of Marine Science and Engineering, 2025)
Plastic pollution has been recognized as an emerging risk for the aquatic environment. Shifting from the prevailing linear “take-make-dispose” model to a “circular” economy framework is essential for mitigating the environmental impact of plastics. Microplastics (MPs) in the natural environment are formed when synthetic polymers are fragmented and micronized to a size ≤ 5 mm. MPs are a global environmental problem, particularly within aquatic ecosystems, due to their persistence, accumulation, and uncertain long-term effects. This review examines the degradation pathways of polymers that result in MP formulation, their rate and distribution across ecosystems, and their potential entry into food systems. Key challenges include a lack of standardized detection methods, specifically for nanoparticles; limited evidence of long-term toxicity; and the inefficiency of current waste management frameworks. Emphasis is placed on the cradle-to-grave lifecycle of plastic materials, highlighting how poor design, excessive packaging, and inadequate post-consumer treatment contribute to MP release. The transition from Directive 94/62/EC to the new Regulation (EU) 2025/40 marks a significant policy shift towards stronger preventive measures. In line with the waste hierarchy and reduction in unnecessary packaging and plastic use, effective recycling must be supported by appropriate collection systems, improved separation processes, and citizen education to prevent waste and improve recycling rates to minimize the accumulation of MPs in the environment and reduce health impacts. This review identifies critical gaps in current knowledge and suggests crucial approaches in order to mitigate MP pollution and protect marine biodiversity and public health.

CO2 mineralization of kimberlite residues from the Gahcho Kué Diamond Mine, Northwest Territories, Canada - Duncan T.E. McDonald; Ian M. Power; Carlos Paulo; Sasha Wilson (International Journal of Greenhouse Gas Control, 2025)

Equine microbiome shifts with dietary mannan-rich fraction inclusion - M. Brummer-Holder; R. Power (Journal of Equine Veterinary Science, 2025)

Optimizing the management of quarry fines for on-site carbon removal: Implications of grain size and mineralogy on CO2 mineralization - Amanda R. Stubbs; Faisal W.K. Khudhur; Ian M. Power; Linzi McDade; Mark Friel; Iain Neill; John MacDonald (International Journal of Greenhouse Gas Control, 2025)

Multiple global change factors and the long‐term dynamics of harmful algal blooms in the North Sea - Karen M. Brandenburg; Julian Merder; Andrea Budiša; Anne Marie Power; Catharina J. M. Philippart; Anna M. Michalak; Tim J. van den Broek; Dedmer B. Van de Waal (Limnology and Oceanography, 2025)
The North Sea has been identified as an area where the impacts of climate change and de‐eutrophication efforts are already apparent, specifically on phytoplankton communities, with shifts in biogeography, altered species composition, and increased biomass of harmful algal bloom (HAB) species. Here, we test whether environmental changes in the Dutch North Sea are associated with changes in the abundances of HAB species and if the probability of blooms has increased over the past two decades. We do so by using generalized additive and logistic regression models, respectively. Results show that Phaeocystis globosa and potential ASP (amnesic shellfish poisoning) and DSP (diarrhetic shellfish poisoning) toxin‐producing species have increased in abundance along the coast over the period 2000–2018, despite overall declines in total phytoplankton biomass over the same period. Conversely, the abundance of potential ASP producers and particularly P. globosa declined in the more central areas of the North Sea. The probability of blooms, which varied across months during the season, generally increased. Environmental factors associated with these increases in the probability of HABs included increasing sea surface temperatures (for potential ASP and DSP toxin producers), possibly related to summer stratification of the water column, and increasing total nitrogen (TN) : total phosphorus (TP) ratios (for potential ASP and DSP toxin producers and P. globosa ) due to de‐eutrophication efforts that more effectively reduced TP than TN. Our results demonstrate how long‐term changes in HAB species abundances in the North Sea are associated with shifts in multiple global change factors that together may lead to intensified HAB development.

Supplemental Feeding as a Driver of Population Expansion and Morphological Change in Anna's Hummingbirds - Nicolas M. Alexandre; Faye G. Romero; Simon G. English; Eliza Grames; Felipe Garzón‐Agudelo; Kevin Epperly; Timothy Barnes; Donald R. Powers; Audrey E. Smith; Zoë Migicovsky; Laura Stein; Saron Akalu; et al. (Global Change Biology, 2025)
Bird beaks are highly adaptable, with the potential to undergo rapid morphological shifts in response to environmental change such as climatic variation or food availability. Anna's Hummingbirds ( Calypte anna ) have undergone dramatic population range expansions over the last 160 years into novel climatic regimes, where supplemental feeders and introduced plant species are frequented. We used museum specimens to measure and characterize the shape of Anna's Hummingbird bills, hypothesizing that the introduction of novel food sources and the colonization of colder climates were associated with distinct dimensions of beak morphology. We estimated feeder and Eucalyptus availability using data from archived newspaper databases and found that these two abundances are linked to population increases in Anna's Hummingbirds, while feeders were associated with changes to beak morphology. We found that bill size and shape changed with feeder use, exhibiting a more tapered and longer bill and a distinct maxillary constriction. In males, dorsal bill shape increased in pointedness, which may have provided an advantage with increased agonistic encounters at feeders. In contrast, bill size decreased in association with lower temperatures at higher latitudes. Our data document rapid morphological changes in the Anna's Hummingbird's bill induced by human‐caused environmental changes over the last century.

TropiRoot 1.0: Database of tropical root characteristics across environments - Amanda L. Cordeiro; Daniela F. Cusack; Nathaly Guerrero‐Ramírez; Richard J. Norby; Laura Toro; Michelle Y. Wong; S. Joseph Wright; Kristine Grace M. Cabugao; Kelly M. Andersen; Lucia Fuchslueger; Colleen M. Iversen; Fiona Soper; et al. (Ecology, 2025)
Tropical ecosystems contain the world's largest biodiversity of vascular plants. Yet, our understanding of tropical functional diversity and its contribution to global diversity patterns is constrained by data availability. This discrepancy underscores an urgent need to bridge data gaps by incorporating comprehensive tropical root data into global datasets. Here, we provide a database of tropical root characteristics. This new database, TropiRoot 1.0, will be instrumental in evaluating an array of hypotheses pertaining to root functional ecology and plant biogeography, both within the tropics and relative to other global biomes. The data compilation was conducted by the TropiRoot Initiative, in partnership with the Fine‐Root Ecology Database (FRED) and the Global Root Trait (GRooT) database, Colorado State University (CSU) and the Smithsonian Tropical Research Institute (STRI). Literature search and data extraction were conducted between 2020 and 2024. Literature was identified using Web of Science, Scopus, and complemented using the expert knowledge of members of TropiRoot. To provide broad environmental and geographical distributions, literature searches included root characteristics (traits) across global change drivers, natural gradients, and from different continents. We adopted FRED standardized data columns and streamlined the format to enhance accessibility for data extraction across various user groups. This optimized framework resulted in a smaller, yet comprehensive datasheet. To make the database compatible with other global root trait initiatives, column identification was standardized following the codes provided by FRED. These efforts culminated in data extracted from 104 new sources, resulting in more than 8000 rows of data (either species or community data). Most of the data in TropiRoot 1.0 include root characteristics such as root biomass, morphology, root dynamics, mass fraction, architecture, anatomy, physiology, and root chemistry. This initiative represents a 30% increase in the currently available data for tropical roots in FRED. TropiRoot 1.0 contains root characteristics from 25 different countries, where seven are located in Asia, six in South America, five in Central America and the Caribbean, four in Africa, two in North America, and 1 in Oceania. Due to the volume of data, when ancillary data were available, including soil data, these data were either extracted and included in the database or its availability was recorded in an additional column. Multiple contributors checked the entries for outliers during the collation process to ensure data quality. For text‐based observations, we examined all cells to ensure that their content relates to their specific categories. For numerical observations, we ordered each numerical value from least to greatest and plotted the values, checking apparent outliers against the data in their respective sources and correcting or removing incorrect or impossible values. Some data (soil and aboveground) have different columns for the same variable presented in different units, including originally published units, but root characteristics data had units converted to match those reported in FRED. By filling a gap from global databases, TropiRoot 1.0 expands our knowledge of otherwise so far underrepresented regions and our ability to assess global trends. This advancement can be used to improve tropical forest representation in vegetation models. The data are freely available and should be cited when used.

The nature of microbial diversity and assembly in the Nebraska Sandhills depends on organismal identity and habitat type - Kaitlin Gattoni; Eli M. S. Gendron; J. Parr McQueen; Kirsten Powers; Thomas O. Powers; Mary J. Harner; Jessica R. Corman; Dorota L. Porazinska (Community Ecology, 2025)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Meta-analysis of biogenic odour management solutions for operational drinking water treatment plants - Jin Zhu; Richard M. Stuetz; Lisa Hamilton; Kaye Power; Bojan Tamburic (Journal of Water Process Engineering, 2025)

Prevalence and molecular characterization of Campylobacter spp. isolated from chicken, beef, pork and sheep livers at Irish abattoirs - Deirdre M. Prendergast; Richard O'Keeffe; Dayle Johnston; Joanne McLernon; Fiona Power; Brian Byrne; Montserrat Gutierrez (International Journal of Food Microbiology, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Using otolith δ18O to assess habitat selection and growth in young-of-the-year Arctic charr - M. Power; J.B. Dempson (Fisheries Research, 2025)

Validation of On-Head OPM MEG for Language Laterality Assessment - Lindsey Power; Timothy Bardouille; Kristin M. Ikeda; Antonina Omisade (Brain Topography, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Weathering and cementation of historic kimberlite residues from South Africa: Implications for residue stabilization and CO2 sequestration - Justin A. Lockhart; Ian M. Power; Carlos Paulo; Amanda R. Stubbs; Nina Zeyen; Sasha Wilson; Matthew Steele-MacInnis; Robert Caldwell; Chris Gunning (Science of The Total Environment, 2024)

Evolution of chitin-synthase in molluscs and their response to ocean acidification - Maoxiao Peng; João C.R. Cardoso; Deborah M. Power (Molecular Phylogenetics and Evolution, 2024)

Gene Expression Comparison Between the Injured Tubercule Skin of Turbot (Scophthalmus maximus) and the Scale Skin of Brill (Scophthalmus rhombus) - João Estêvão; Andrés Blanco-Hortas; Juan A. Rubiolo; Óscar Aramburu; Carlos Fernández; Antonio Gómez-Tato; Deborah M. Power; Paulino Martínez (Fishes, 2024)
Turbot and brill are two congeneric commercial flatfish species with striking differences in skin organization. The calcified appendages in turbot skin are conical tubercles, while in brill, they are elasmoid scales. A skin injury involving epidermal and dermal levels was evaluated 72 h post-injury to compare the skin regeneration processes between both species. An immune-enriched 4x44k turbot oligo-microarray was used to characterize the skin transcriptome and gene expression profiles in both species. RNA-seq was also performed on the brill samples to improve transcriptome characterization and validate the microarray results. A total of 15,854 and 12,447 expressed genes were identified, respectively, in the turbot and brill skin (10,101 shared) using the oligo-microarray (11,953 and 9629 annotated). RNA-seq enabled the identification of 11,838 genes in brill skin (11,339 annotated). Functional annotation of skin transcriptomes was similar in both species, but in turbot, it was enriched on mechanisms related to maintenance of epithelial structure, mannosidase activity, phospholipid binding, and cell membranes, while in brill, it was enriched on biological and gene regulation mechanisms, tissue development, and transferase and catalytic activities. The number of DEGs identified after skin damage in brill and turbot was 439 and 143, respectively (only 14 shared). Functions related to catabolic and metabolic processes, visual and sensorial perception, response to wounding, and wound healing were enriched in turbot DEGs, while metabolism, immune response, oxidative stress, phospholipid binding, and response to stimulus were enriched in brill. The results indicate that differences may be related to the stage of wound repair due to their different skin architecture. This work provides a foundation for future studies directed at skin defense mechanisms, with practical implications in flatfish aquaculture.

Individual differences in perceived changes and impacts on well-being of working from home during the COVID-19 pandemic - Jiaxuan Xu; José Guillermo Cedeño Laurent; Vasuta Chan; Deunchalerm Khiewpun; Wendy M. Purcell; John D. Spengler; Linda Powers Tomasso (Building and Environment, 2024)

Effects of a Fruit and Vegetable Supplement on the Skin Carotenoid Scores in Healthy Adults: A Pilot Study - R. Brooks; C. Washburn; M. Powers; J. Mayo; A. Landry (Journal of the Academy of Nutrition and Dietetics, 2024)

Examination of the effects of excess microalgae availability on the disruption of mussel byssus secretion - Ji-Yue Ni; Yan Zhou; Yu-Qing Wang; Shi-Hui Huang; Qian-Wen Cui; Wen-Yi Wang; Xiao-Ying Yang; Deborah M. Power; Yi-Feng Li (Aquaculture, 2024)

Insights into core molecular changes associated with metamorphosis in gilthead seabream larvae across diverse hatcheries - Babak Najafpour; Soraia Santos; Manuel Manchado; Aurora Vidal; Andreas Tsipourlianos; Adelino V.M. Canário; Katerina A. Moutou; Deborah M. Power (Aquaculture, 2024)

A comparison of PM2.5 exposure estimates from different estimation methods and their associations with cognitive testing and brain MRI outcomes - Melinda C. Power; Katie M. Lynch; Erin E. Bennett; Qi Ying; Eun Sug Park; Xiaohui Xu; Richard L. Smith; James D. Stewart; Jeff D. Yanosky; Duanping Liao; Aaron van Donkelaar; Joel D. Kaufman; et al. (Environmental Research, 2024)

Correction: Progress in the analysis of English Channel loliginid squid diets using DNA-metabarcoding techniques - A. Larivain; C. Zatylny-Gaudin; E. Gonzalez; G. J. Pierce; A. M. Power; J. P. Robin (Marine Biology, 2024)

From field station to forecast: managing data at the Alaska Volcano Observatory - Michelle L. Coombs; Cheryl E. Cameron; Hannah R. Dietterich; Eleanor S. Boyce; Aaron G. Wech; Ronni Grapenthin; Kristi L. Wallace; Tom Parker; Taryn Lopez; Scott Crass; David Fee; Matthew M. Haney; et al. (Bulletin of Volcanology, 2024)

TRPC Channels Activated by G Protein-Coupled Receptors Drive Ca2+ Dysregulation Leading to Secondary Brain Injury in the Mouse Model - Jasneet Parmar; Georg von Jonquieres; Nagarajesh Gorlamandala; Brandon Chung; Amanda J. Craig; Jeremy L. Pinyon; Lutz Birnbaumer; Matthias Klugmann; Andrew J. Moorhouse; John M. Power; Gary D. Housley (Translational Stroke Research, 2024)
Canonical transient receptor potential (TRPC) non-selective cation channels, particularly those assembled with TRPC3, TRPC6, and TRPC7 subunits, are coupled to G αq -type G protein-coupled receptors for the major classes of excitatory neurotransmitters. Sustained activation of this TRPC channel-based pathophysiological signaling hub in neurons and glia likely contributes to prodigious excitotoxicity-driven secondary brain injury expansion. This was investigated in mouse models with selective Trpc gene knockout (KO). In adult cerebellar brain slices, application of glutamate and the class I metabotropic glutamate receptor agonist (S)-3,5-dihydroxyphenylglycine to Purkinje neurons expressing the GCaMP5g Ca 2+ reporter demonstrated that the majority of the Ca 2+ loading in the molecular layer dendritic arbors was attributable to the TRPC3 effector channels ( Trpc3 KO compared with wildtype (WT)). This Ca 2+ dysregulation was associated with glutamate excitotoxicity causing progressive disruption of the Purkinje cell dendrites (significantly abated in a GAD67-GFP - Trpc3 KO reporter brain slice model). Contribution of the G αq -coupled TRPC channels to secondary brain injury was evaluated in a dual photothrombotic focal ischemic injury model targeting cerebellar and cerebral cortex regions, comparing day 4 post-injury in WT mice, Trpc3 KO , and Trpc1/3/6/7 quadruple knockout ( Trpc QKO ), with immediate 2-h (primary) brain injury. Neuroprotection to secondary brain injury was afforded in both brain regions by Trpc3 KO and Trpc QKO models, with the Trpc QKO showing greatest neuroprotection. These findings demonstrate the contribution of the G αq -coupled TRPC effector mechanism to excitotoxicity-based secondary brain injury expansion, which is a primary driver for mortality and morbidity in stroke, traumatic brain injury, and epilepsy.

Southern Flounder: Major Milestones and Remaining Knowledge Gaps in Their Biology, Ecology, and Fishery Management - Stephen R. Midway; Frederick S. Scharf; Michael A. Dance; Nancy J. Brown-Peterson; Joseph C. Ballenger; Nicolette S. Beeken; Russell J. Borski; Tanya L. Darden; Kenneth A. Erickson; Troy M. Farmer; Ashley Fincannon; John Godwin; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Valuing shoreline habitats for recreational fishing - Andrew M. Scheld; Donna M. Bilkovic; Sarah Stafford; Kathleen Powers; Susanna Musick; Amanda G. Guthrie (Ocean & Coastal Management, 2024)

Parents Report Positive Changes in Parental Feeding Practices 12 Months After Intervention - Theresa VB. Peirce; M. Catalina Aragón; Garry Auld; Karen V. Barale; Sheryl O. Hughes; Thomas G. Power; Jane D. Lanigan; Louise Parker; Susan S. Baker (Journal of Nutrition Education and Behavior, 2024)

Progress in the analysis of English Channel loliginid squid diets using DNA-metabarcoding techniques - A. Larivain; C. Zatylny-Gaudin; E. Gonzalez; G. J. Pierce; A. M. Power; J. P. Robin (Marine Biology, 2024)

Tropical root responses to global changes: A synthesis - Daniela Yaffar; Laynara F. Lugli; Michelle Y. Wong; Richard J. Norby; Shalom D. Addo‐Danso; Marie Arnaud; Amanda L. Cordeiro; Lee H. Dietterich; Milton H. Diaz‐Toribio; Ming Y. Lee; Om Prakash Ghimire; Chris M. Smith‐Martin; et al. (Global Change Biology, 2024)
Tropical ecosystems face escalating global change. These shifts can disrupt tropical forests' carbon (C) balance and impact root dynamics. Since roots perform essential functions such as resource acquisition and tissue protection, root responses can inform about the strategies and vulnerabilities of ecosystems facing present and future global changes. However, root trait dynamics are poorly understood, especially in tropical ecosystems. We analyzed existing research on tropical root responses to key global change drivers: warming, drought, flooding, cyclones, nitrogen (N) deposition, elevated (e) CO 2 , and fires. Based on tree species‐ and community‐level literature, we obtained 266 root trait observations from 93 studies across 24 tropical countries. We found differences in the proportion of root responsiveness to global change among different global change drivers but not among root categories. In particular, we observed that tropical root systems responded to warming and eCO 2 by increasing root biomass in species‐scale studies. Drought increased the root: shoot ratio with no change in root biomass, indicating a decline in aboveground biomass. Despite N deposition being the most studied global change driver, it had some of the most variable effects on root characteristics, with few predictable responses. Episodic disturbances such as cyclones, fires, and flooding consistently resulted in a change in root trait expressions, with cyclones and fires increasing root production, potentially due to shifts in plant community and nutrient inputs, while flooding changed plant regulatory metabolisms due to low oxygen conditions. The data available to date clearly show that tropical forest root characteristics and dynamics are responding to global change, although in ways that are not always predictable. This synthesis indicates the need for replicated studies across root characteristics at species and community scales under different global change factors.

Passive direct air capture using calcium oxide powder: The importance of water vapor - Lance Dostie; Kwon Rausis; Ian M. Power (Journal of Cleaner Production, 2024)

Impact of turbidity on the gill morphology and hypoxia tolerance of eastern sand darter ( Ammocrypta pellucida ) - Britney L. Firth; Paul M. Craig; D. Andrew R. Drake; Michael Power (Journal of Fish Biology, 2024)
Anthropogenic stressors such as agriculture and urbanization can increase river turbidity, which can negatively impact fish gill morphology and growth due to reduced oxygen in the benthic environment. We assessed the gill morphology, field metabolic rate (FMR), and two hypoxia tolerance metrics (oxygen partial pressure at loss of equilibrium, PO 2 at LOE, and critical oxygen tension, P crit ) of eastern sand darter ( Ammocrypta pellucida ), a small benthic fish listed as threatened under the Species at Risk Act in Canada, from rivers in southern Ontario. Field trials were conducted streamside in the Grand River (August 2019; mean NTU 8) and in the comparatively more turbid Thames River (August 2020; mean NTU 94) to test the effect of turbidity on each physiological endpoint. Gills were collected from incidental mortalities and museum specimens, and were assessed using hematoxylin and eosin and immunofluorescent staining. The between‐river comparison indicated that turbidity significantly increased interlamellar space and filament width but had no significant influence on other gill morphometrics or FMR. Turbidity significantly increased PO 2 at LOE (i.e., fish had a lower hypoxia tolerance) but did not significantly impact P crit . Therefore, although turbidity influences hypoxia tolerance through LOE, turbidity levels were not sufficiently high in the study rivers to contribute to measurable changes in gill morphology or metabolism in the wild. Determining whether changes in gill morphology or metabolism occur under higherturbidity levels would help resolve the ecological importance of turbidity on species physiology in urban and agricultural ecosystems.

Climate‐related variation of metabolic rate across the distribution of a broadly tolerant invasive forest pest - Sean D. Powers; Lily M. Thompson; Dylan Parry; Kristine L. Grayson; Eloy Martinez; Salvatore J. Agosta (Journal of Biogeography, 2024)
Aim Metabolic rate is a widely studied physiological species trait related to energetics, climate, and geographical distributions. Hypotheses have been proposed to explain variation in metabolic rate, but evidence has been mixed due to the limited sampling scope of intraspecific studies. Successful biological invasions offer a unique opportunity to examine the development of intraspecific physiological variation and how it relates to climate, invasive spread and species range limits. The aim of this study was to determine if metabolic rate variation across the spongy moth invasive range was consistent with a pattern of adaptation to local climate. Location Northeastern United States of America. Taxon Lymantria dispar dispar L. (Lepidoptera: Erebidae). Methods Larvae were sourced from 14 populations across the invasion front and interior of the current L. d. dispar invasive range and were reared at a constant temperature. Routine metabolic rates (RMR) of larvae were assayed at three ecologically relevant temperatures. These data were analysed to determine if there were differences in RMR and temperature sensitivity of RMR among populations. Population‐level variation in RMR was then analysed as a function of local climate and geographical position to test for patterns consistent with local adaptation. Results Larval RMR showed significant variation among populations across all assay temperatures, but there was no difference in temperature sensitivity (i.e. slope). This variation followed a positive latitudinal cline with RMR increasing from the southern range to the north. This cline also showed a significant relationship with local climate variables. Main Conclusions Larval metabolic rate variation was consistent with a pattern of adaptation by L. d. dispar to divergent climates across its invasive range. These results indicated that thermal adaptation of whole‐organism physiology may play a key role in promoting species spread and expansion for biological invasions like L. d. dispar .

Stock discrimination of two European squids ( Illex coindetii , Loligo forbesii ) by statolith shape analysis - Bianca T. C. Bobowski; Anne Marie Power; Finlay Burns; Pierluigi Carbonara; Danila Cuccu; Marilena Donnaloia; Maria Cristina Follesa; Ana Moreno; Inna M. Sokolova; Maria Valls; Daniel Oesterwind (Fisheries Management and Ecology, 2024)
We evaluated the feasibility of classifying ommastrephid and loliginid squid species by statolith shape analysis into fisheries management units or stocks. Statoliths of Illex coindetii (Verany, 1839) and Loligo forbesii (Steenstrup, 1856) were studied from multiple areas of the North East Atlantic and Northern Mediterranean Sea during 2021–2022. I. coindetii and L. forbesii individuals were categorized into multiple stocks across the areas studied. Stocks migrating between fishing areas as well as multiple stocks in the same area, as identified for L. forbesii in this study, need to be considered for sustainable fisheries management.

Local environment shapes milk microbiomes while evolutionary history constrains milk macronutrients in captive cercopithecine primates - Sally L. Bornbusch; Hannah E. Shinnerl; Lindsey Gentry; Mia M. Keady; Virginia Glick; Carly R. Muletz‐Wolz; Michael L. Power (Environmental Microbiology, 2024)
Milk is a complex biochemical fluid that includes macronutrients and microbiota, which, together, are known to facilitate infant growth, mediate the colonization of infant microbiomes, and promote immune development. Examining factors that shape milk microbiomes and milk‐nutrient interplay across host taxa is critical to resolving the evolution of the milk environment. Using a comparative approach across four cercopithecine primate species housed at three facilities under similar management conditions, we test for the respective influences of the local environment (housing facility) and host species on milk (a) macronutrients (fat, sugar, and protein), (b) microbiomes (16S rRNA), and (c) predicted microbial functions. We found that milk macronutrients were structured according to host species, while milk microbiomes and predicted function were strongly shaped by the local environment and, to a lesser extent, host species. The milk microbiomes of rhesus macaques ( Macaca mulatta ) at two different facilities more closely resembled those of heterospecific facility‐mates compared to conspecifics at a different facility. We found similar, facility‐driven patterns of microbial functions linked to physiology and immune modulation, suggesting that milk microbiomes may influence infant health and development. These results provide novel insight into the complexity of milk and its potential impact on infants across species and environments.

Differential tissue immune stimulation through immersion in bacterial and viral agonists in the Antarctic Notothenia rossii - Cármen S.V. Sousa; Maoxiao Peng; Pedro M. Guerreiro; João C.R. Cardoso; Liangbiao Chen; Adelino V.M. Canário; Deborah M. Power (Fish & Shellfish Immunology, 2024)

The mussel larvae microbiome changes in response to a temperature rise - You-Ting Zhu; Xiao Liang; Tian-Tian Liu; Deborah M. Power; Yi-Feng Li; Jin-Long Yang (Frontiers in Marine Science, 2024)
Ocean warming caused by global climate change influences the function, diversity, and community dynamics of commensal microorganisms, including the hemolymph and the gut microbiota in mussels. However, the microbiota in hard-shelled mussel ( Mytilus coruscus ) larvae and the effect of temperature on the microbial community structure have yet to be studied. Herein, we investigated the core microbiota of M. coruscus larvae and the impact of acute (4 h) and gradual (4 days) exposure to a rise in seawater temperature from 21 to 25 °C. Eleven core genera were identified in M. coruscus larvae by 16S rDNA gene sequencing: Alteromonas , Brevundimonas , Delftia , Microbacterium , Neptuniibacter , Neptunomonas , Pseudoalteromonas , Rhodococcus , Stenotrophomonas , Tenacibaculum , and Thalassotalea . The microbiota of larvae in the short exposure treatment was similar to the control. However, the abundance of Delftia , Neptunomonas , Pseudoalteromonadaceae , Rhodococcus , and Stenotrophomonas decreased significantly in the long-exposure larvae. In contrast, at the genus level, the abundance of Tenacibaculum increased significantly. Diversity and multivariate analyses confirmed that the microbiota patterns were linked to seawater warming over the long term. Microbiota diversity did not change significantly, regardless of whether the seawater temperature increased quickly or slowly; however, we observed a significant increase in the microbiota species abundance at higher temperatures. Among the altered bacterial genera, Delftia , Neptunomonas , and Rhodococcus function in the degradation of organic compounds; Pseudoalteromonas is closely associated with mussel attachment and metamorphosis, and Tenacibaculum is an opportunistic pathogen that can cause marine mollusk death. The results suggest that marine heat waves caused by climate change may reduce the ability of symbiotic bacteria to degrade environmental toxins, will affect mussel larvae metamorphosis, and increase the abundance of opportunistic pathogens, thereby increasing the risk of disease and death of mussel larvae.

Habitat-dependent metabolic costs for a wild cold-water fish - Benjamin L. Hlina; Daniel M. Glassman; Elodie J. I. Lédée; Liane B. Nowell; Julie E. Claussen; David P. Philipp; J. Ellen Marsden; Michael Power; Steven J. Cooke (Aquatic Sciences, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

The physiological effect of polystyrene nanoplastic particles on fish and human fibroblasts - Maoxiao Peng; Rute C. Félix; Adelino V.M. Canário; Deborah M. Power (Science of The Total Environment, 2024)

Magnesite everywhere: Formation of carbonates in the alkaline lakes and playas of the Cariboo Plateau, British Columbia, Canada - Maija J. Raudsepp; Sasha Wilson; Nina Zeyen; Maria L. Arizaleta; Ian M. Power (Chemical Geology, 2024)

Dominance of net autotrophy in arid landscape low relief polar lakes, Nunavut, Canada - Paola Ayala‐Borda; Matthew J. Bogard; Guillaume Grosbois; Vilmantas Prėskienis; Joseph M. Culp; Michael Power; Milla Rautio (Global Change Biology, 2024)
The Arctic is the fastest warming biome on the planet, and environmental changes are having striking effects on freshwater ecosystems that may impact the regional carbon cycle. The metabolic state of Arctic lakes is often considered net heterotrophic, due to an assumed supply of allochthonous organic matter that supports ecosystem respiration and carbon mineralization in excess of rates of primary production. However, lake metabolic patterns vary according to regional climatic characteristics, hydrological connectivity, organic matter sources and intrinsic lake properties, and the metabolism of most Arctic lakes is unknown. We sampled 35 waterbodies along a connectivity gradient from headwater to downstream lakes, on southern Victoria Island, Nunavut, in an area characterized by low precipitation, organic‐poor soils, and high evaporation rates. We evaluated whether lakes were net autotrophic or heterotrophic during the open water period using an oxygen isotopic mass balance approach. Most of the waterbodies were autotrophic and sites of net organic matter production or close to metabolic equilibrium. Autotrophy was associated with higher benthic primary production, as compared to its pelagic counterpart, due to the high irradiance reaching the bottom and efficient internal carbon and nutrient cycling. Highly connected midstream and downstream lakes showed efficient organic matter cycling, as evidenced by the strong coupling between gross primary production (GPP) and ecosystem respiration, while decoupling was observed in some headwater lakes with significantly higher GPP. The shallow nature of lakes in the flat, arid region of southern Victoria Island supports net autotrophy in most lakes during the open water season. Ongoing climate changes that lengthen the ice‐free irradiance period and increase rates of nutrient evapoconcentration may further promote net autotrophy, with uncertain long‐term effects for lake functioning.

Rejection sampling and agent-based models for data limited fisheries - Ernesto Carrella; Joseph Powers; Steven Saul; Richard M. Bailey; Nicolas Payette; Katyana A. Vert-pre; Aarthi Ananthanarayanan; Michael Drexler; Chris Dorsett; Jens Koed Madsen (Frontiers in Marine Science, 2024)
Many of the world’s fisheries are “data-limited” where the information does not allow precise determination of fish stock status and limits the development of appropriate management responses. Two approaches are proposed for use in data-limited stock management strategy evaluations to guide the evaluations and to understand the sources of uncertainty: rejection sampling methods and the incorporation of more complex socio-economic dynamics into management evaluations using agent-based models. In rejection sampling (or rejection filtering) a model is simulated many times with a wide range of priors on parameters and outcomes are compared multiple filtering criteria. Those simulations that pass all the filters form an ensemble of feasible models. The ensemble can be used to look for robust management strategies, robust to both model uncertainties. Agent-based models of fishery economics can be implemented within the rejection framework, integrating the biological and economic understanding of the fishery. A simple artificial example of a difference equation bio-economic model is given to demonstrate the approach. Then rejection sampling is applied to an agent-based model for the hairtail ( Trichiurus japonicas ) fishery, where an operating model is constructed with rejection/agent-based methods and compared to known data and analyses of the fishery. The usefulness of information and rejection filters are illuminated and efficacy examined. The methods can be helpful for strategic guidance where multiple states of nature are possible as a part of management strategy evaluation.

Ioxynil and diethylstilbestrol impair cardiac performance and shell growth in the mussel Mytilus coruscus - Yi-Feng Li; Yue-Tong Lin; Yu-Qing Wang; Ji-Yue Ni; Deborah M. Power (Science of The Total Environment, 2023)

Odour management in drinking water systems fed by mixed water supplies - Jin Zhu; Richard M. Stuetz; Lisa Hamilton; Kaye Power; Bojan Tamburic (Journal of Water Process Engineering, 2023)

Tracking kelp-type seaweed fuel in the archaeological record through Raman spectroscopy of charred particles: examples from the Atacama Desert coast - Luca Sitzia; Ximena Power; Debora Zurro; Jean Paul Maalouf; José Cárcamo; Kristopher Chandía; J. M. Alonso Vega; César Borie; Constanza Roa; Claudia Silva; Diego Salazar; Sebastián Vivanco; et al. (Archaeological and Anthropological Sciences, 2023)

The impact of egg thermal regimes on the response to food deprivation and refeeding in juvenile European Sea bass (Dicentrarchus labrax) - Ana Patrícia Mateus; Rita A. Costa; Javier Jiménez Herrero; Bastien Sadoul; Marie Laure Bégout; Xavier Cousin; Adelino V.M. Canario; Deborah M. Power (Aquaculture, 2023)

Surface material of acoustic transmitters influences the inflammatory response of rainbow trout (Oncorhynchus mykiss) during long-term implantation - George Heath; Shawna L. Semple; Tania Rodríguez-Ramos; Sarah Hardy; Philip Harrison; Ingeborg M. Mulder; Michael Power; Brian Dixon (Veterinary Immunology and Immunopathology, 2023)

Impact of wet-dry cycles on enhanced rock weathering of brucite, wollastonite, serpentinite and kimberlite: Implications for carbon verification - Amanda R. Stubbs; Ian M. Power; Carlos Paulo; Baolin Wang; Nina Zeyen; Sasha Wilson; Evelyn Mervine; Chris Gunning (Chemical Geology, 2023)

Core microbiome profiles and their modification by environmental, biological, and rearing factors in aquaculture hatcheries - Babak Najafpour; Patricia I.S. Pinto; Eric Climent Sanz; Juan F. Martinez-Blanch; Adelino V.M. Canario; Katerina A. Moutou; Deborah M. Power (Marine Pollution Bulletin, 2023)

Novel estimation of gear selectivity using a concurrent mass mortality event: A case study using red drum (Sciaenops ocellatus) in the northern Gulf of Mexico - Sean P. Powers; Crystal L. Hightower; John M. Hoenig; Jeffrey D. Plumlee; T. Reid Nelson; J. Marcus Drymon (Fisheries Research, 2023)

The Western Lake Erie culture collection: A promising resource for evaluating the physiological and genetic diversity of Microcystis and its associated microbiome - Colleen E. Yancey; E. Anders Kiledal; Subba Rao Chaganti; Vincent J. Denef; Reagan M. Errera; Jacob T. Evans; Lauren N. Hart; Dragan Isailovic; William S. James; Jenan J. Kharbush; Jeffrey A. Kimbrel; Wei Li; et al. (Harmful Algae, 2023)

Enhanced Pharmacokinetic Bioanalysis of Antibody–drug Conjugates using Hybrid Immunoaffinity Capture and Microflow LC-MS/MS - Moo-jin Suh; Joshua B. Powers; Casey M. Daniels; Yuling Wu (The AAPS Journal, 2023)

High-resolution entry and exit surface dosimetry in a 1.5 T MR-linac - E. Patterson; P. Stokes; D. Cutajar; A. Rosenfeld; J. Baines; P. Metcalfe; M. Powers (Physical and Engineering Sciences in Medicine, 2023)
The magnetic field of a transverse MR-linac alters electron trajectories as the photon beam transits through materials, causing lower doses at flat entry surfaces and increased doses at flat beam-exiting surfaces. This study investigated the response of a MOSFET detector, known as the MO Skin ™, for high-resolution surface and near-surface percentage depth dose measurements on an Elekta Unity. Simulations with Geant4 and the Monaco treatment planning system (TPS), and EBT-3 film measurements, were also performed for comparison. Measured MO Skin ™ entry surface doses, relative to D max , were (9.9 ± 0.2)%, (10.1 ± 0.3)%, (11.3 ± 0.6)%, (12.9 ± 1.0)%, and (13.4 ± 1.0)% for 1 × 1 cm 2 , 3 × 3 cm 2 , 5 × 5 cm 2 , 10 × 10 cm 2 , and 22 × 22 cm 2 fields, respectively. For the investigated fields, the maximum percent differences of Geant4, TPS, and film doses extrapolated and interpolated to a depth suitable for skin dose assessment at the beam entry, relative to MO Skin ™ measurements at an equivalent depth were 1.0%, 2.8%, and 14.3%, respectively, and at a WED of 199.67 mm at the beam exit, 3.2%, 3.7% and 5.7%, respectively. The largest measured increase in exit dose, due to the electron return effect, was 15.4% for the 10 × 10 cm 2 field size using the MO Skin ™ and 17.9% for the 22 × 22 cm 2 field size, using Geant4 calculations. The results presented in the study validate the suitability of the MO Skin ™ detector for transverse MR-linac surface dosimetry.

Stable isotopes and foraging behaviors support the role of antipredator benefits in driving the association between two marine fishes - Christopher R. Haak; Michael Power; Alexander D. M. Wilson; Andy J. Danylchuk (Oecologia, 2023)

Drivers of the microbial metabolic quotient across global grasslands - A. C. Risch; S. Zimmermann; M. Schütz; E. T. Borer; A. A. D. Broadbent; M. C. Caldeira; K. F. Davies; N. Eisenhauer; A. Eskelinen; P. A. Fay; F. Hagedorn; J. M. H. Knops; et al. (Global Ecology and Biogeography, 2023)
Aim The microbial metabolic quotient (MMQ; mg CO 2 ‐C/mg MBC/h), defined as the amount of microbial CO 2 respired (MR; mg CO 2 ‐C/kg soil/h) per unit of microbial biomass C (MBC; mg C/kg soil), is a key parameter for understanding the microbial regulation of the carbon (C) cycle, including soil C sequestration. Here, we experimentally tested hypotheses about the individual and interactive effects of multiple nutrient addition (nitrogen + phosphorus + potassium + micronutrients) and herbivore exclusion on MR, MBC and MMQ across 23 sites (five continents). Our sites encompassed a wide range of edaphoclimatic conditions; thus, we assessed which edaphoclimatic variables affected MMQ the most and how they interacted with our treatments. Location Australia, Asia, Europe, North/South America. Time period 2015–2016. Major taxa Soil microbes. Methods Soils were collected from plots with established experimental treatments. MR was assessed in a 5‐week laboratory incubation without glucose addition, MBC via substrate‐induced respiration. MMQ was calculated as MR/MBC and corrected for soil temperatures (MMQsoil). Using linear mixed effects models (LMMs) and structural equation models (SEMs), we analysed how edaphoclimatic characteristics and treatments interactively affected MMQsoil. Results MMQsoil was higher in locations with higher mean annual temperature, lower water holding capacity and lower soil organic C concentration, but did not respond to our treatments across sites as neither MR nor MBC changed. We attributed this relative homeostasis to our treatments to the modulating influence of edaphoclimatic variables. For example, herbivore exclusion, regardless of fertilization, led to greater MMQsoil only at sites with lower soil organic C ( Main conclusions Our results pinpoint the main variables related to MMQsoil across grasslands and emphasize the importance of the local edaphoclimatic conditions in controlling the response of the C cycle to anthropogenic stressors. By testing hypotheses about MMQsoil across global edaphoclimatic gradients, this work also helps to align the conflicting results of prior studies.

121 Impact of environmental conditions and dragging schedules on changes in moisture content in equine arena footing - S. McGill; M. Hayes; K. Power; M. Peterson; R. Coleman (Journal of Equine Veterinary Science, 2023)

120 Determining moisture content in equine arena footing on-farm - S. McGill; M. Hayes; K. Power; M. Peterson; R. Coleman (Journal of Equine Veterinary Science, 2023)

Geochemical modeling of CO2 sequestration in ultramafic mine wastes from Australia, Canada, and South Africa: Implications for carbon accounting and monitoring - Carlos Paulo; Ian M. Power; Nina Zeyen; Baolin Wang; Sasha Wilson (Applied Geochemistry, 2023)

Influence of topical capsaicin cream on thermoregulation and perception during acute exercise in the heat - Alejandro M. Rosales; Marie Powers; Matthias J. Walters; Mark L. McGlynn; Christopher W. Collins; Dustin R. Slivka (Journal of Thermal Biology, 2023)

The relationship between single muscle fibre and voluntary rate of force development in young and old males - Benjamin E. Dalton; Nicole Mazara; Mathew I. B. Debenham; Derek P. Zwambag; Alex M. Noonan; Erin Weersink; Stephen H. M. Brown; Geoffrey A. Power (European Journal of Applied Physiology, 2023)

Assessing the consistency of crop leaf area index derived from seasonal Sentinel-2 and Landsat 8 imagery over Manitoba, Canada - Taifeng Dong; Jane Liu; Jiangui Liu; Liming He; Rong Wang; Budong Qian; Heather McNairn; Jarrett Powers; Yichao Shi; Jing M Chen; Jiali Shang (Agricultural and Forest Meteorology, 2023)

Thermal imprinting during embryogenesis modifies skin repair in juvenile European sea bass (Dicentrarchus labrax) - Ana Patrícia Mateus; Rita A. Costa; Bastien Sadoul; Marie-Laure Bégout; Xavier Cousin; Adelino VM. Canario; Deborah M. Power (Fish & Shellfish Immunology, 2023)

Cephalopods, a gap in the European Marine Strategy Framework Directive and their future integration - Bianca T. C. Bobowski; Anne Marie Power; Graham J. Pierce; Ana Moreno; Ane Iriondo; Julio Valeiras; Inna M. Sokolova; Daniel Oesterwind (Marine Biology, 2023)
With the aim of maintaining or obtaining good environmental status in the Northeast Atlantic and northern Mediterranean Sea, the European Marine Strategy Framework Directive (EU-MSFD) came into force in 2008. All EU Member States (MS) have the task of assessing the current state of their adjacent waters to guarantee sustainable use of marine resources and healthy ecosystems for the current and future generations. Although the MSFD has been implemented for over a decade, there are still gaps in the assessment of various ecologically and commercially important marine species, such as cephalopods. Here we describe the status of cephalopods, a key component of marine ecosystems and a valuable fishing resource, within the MSFD. To do so, we review how MS deal with this group in their reporting and identify and explain the gaps in the cephalopod assessment. We describe the main challenges including the limited data and the rarity of dedicated surveys on cephalopods. However, we argue that cephalopods can be partially integrated into the EU-MSFD assessment, illustrating the current opportunities and future possibilities of their integration into the MSFD, mainly using Descriptors 1–4. Graphical abstract

The impacts of a global pandemic on the efficacy and stability of contemporary wildlife conservation: South Africa as a case study - David A. Ehlers Smith; Yvette C. Ehlers Smith; Harriet T. Davies-Mostert; Lindy J. Thompson; Daniel M. Parker; Deon de Villiers; Dean Ricketts; Brent Coverdale; Peter J. Roberts; Christopher Kelly; Duncan N. Macfadyen; Nomthandazo S. Manqele; et al. (Ambio, 2023)
Conservationists speculated on potential benefits to wildlife of lockdown restrictions because of the COVID-19 pandemic but voiced concern that restrictions impeded nature conservation. We assessed the effects of lockdown restrictions on biodiversity conservation in South Africa, a biodiverse country with economic inequality and reliance on wildlife resources. We solicited expert opinion using the IUCN’s Threats Classification Scheme to structure a questionnaire and illustrated responses with individual case studies from government parastatal and non-governmental conservation organisations. The most highly reported threats were biological resource use, residential/commercial developments, invasive species, and human intrusions. The trends reported by 90 survey respondents were supported by case studies using environmental compliance data from parastatal conservation organisations. Lack of tourism revenue and funding were cited as hindrances to conservation. Mechanisms to prevent environmental degradation in the face of global emergencies must be implemented and ‘ring-fenced’ to ensure conservation is not a casualty during future global crises.

Impacts of dissolved phosphorus and soil-mineral-fluid interactions on CO2 removal through enhanced weathering of wollastonite in soils - Cameron Wood; Anna L. Harrison; Ian M. Power (Applied Geochemistry, 2023)

Ecological stoichiometry and fungal community turnover reveal variation among mycorrhizal partners in their responses to warming and drought - Haiyang Zhang; Amber C. Churchill; Ian C. Anderson; Chioma Igwenagu; Sally A. Power; Jonathan M. Plett; Catriona A. Macdonald; Elise Pendall; Yolima Carrillo; Jeff R. Powell (Molecular Ecology, 2023)
Symbiotic fungi mediate important energy and nutrient transfers in terrestrial ecosystems. Environmental change can lead to shifts in communities of symbiotic fungi, but the consequences of these shifts for nutrient dynamics among symbiotic partners are poorly understood. Here, we assessed variation in carbon (C), nitrogen (N) and phosphorus (P) in tissues of arbuscular mycorrhizal (AM) fungi and a host plant ( Medicago sativa ) in response to experimental warming and drought. We linked compositional shifts in AM fungal communities in roots and soil to variation in hyphal chemistry by using high‐throughput DNA sequencing and joint species distribution modelling. Compared to plants, AM hyphae was 43% lower in (C) and 24% lower in (N) but more than nine times higher in (P), with significantly lower C:N, C:P and N:P ratios. Warming and drought resulted in increases in (P) and reduced C:P and N:P ratios in all tissues, indicating fungal P accumulation was exacerbated by climate‐associated stress. Warming and drought modified the composition of AM fungal communities, and many of the AM fungal genera that were linked to shifts in mycelial chemistry were also negatively impacted by climate variation. Our study offers a unified framework to link climate change, fungal community composition, and community‐level functional traits. Thus, our study provides insight into how environmental change can alter ecosystem functions via the promotion or reduction of fungal taxa with different stoichiometric characteristics and responses.

Two canonically aerobic foraminifera express distinct peroxisomal and mitochondrial metabolisms - Christopher Powers; Fatma Gomaa; Elizabeth B. Billings; Daniel R. Utter; David J. Beaudoin; Virginia P. Edgcomb; Colleen M. Hansel; Scott D. Wankel; Helena L. Filipsson; Ying Zhang; Joan M. Bernhard (Frontiers in Marine Science, 2022)
Certain benthic foraminifera thrive in marine sediments with low or undetectable oxygen. Potential survival avenues used by these supposedly aerobic protists include fermentation and anaerobic respiration, although details on their adaptive mechanisms remain elusive. To better understand the metabolic versatility of foraminifera, we studied two benthic species that thrive in oxygen-depleted marine sediments. Here we detail, via transcriptomics and metatranscriptomics, differential gene expression of Nonionella stella and Bolivina argentea , collected from Santa Barbara Basin, California, USA, in response to varied oxygenation and chemical amendments. Organelle-specific metabolic reconstructions revealed these two species utilize adaptable mitochondrial and peroxisomal metabolism. N. stella , most abundant in anoxia and characterized by lack of food vacuoles and abundance of intracellular lipid droplets, was predicted to couple the putative peroxisomal beta-oxidation and glyoxylate cycle with a versatile electron transport system and a partial TCA cycle. In contrast, B. argentea , most abundant in hypoxia and contains food vacuoles, was predicted to utilize the putative peroxisomal gluconeogenesis and a full TCA cycle but lacks the expression of key beta-oxidation and glyoxylate cycle genes. These metabolic adaptations likely confer ecological success while encountering deoxygenation and expand our understanding of metabolic modifications and interactions between mitochondria and peroxisomes in protists.

Taking flight: An ecological, evolutionary and genomic perspective on bat telomeres - Megan L. Power; Nicole M. Foley; Gareth Jones; Emma C. Teeling (Molecular Ecology, 2022)
Over 20% of all living mammals are bats (order Chiroptera). Bats possess extraordinary adaptations including powered flight, laryngeal echolocation and a unique immune system that enables them to tolerate a diversity of viral infections without presenting clinical disease symptoms. They occupy multiple trophic niches and environments globally. Significant physiological and ecological diversity occurs across the order. Bats also exhibit extreme longevity given their body size with many species showing few signs of ageing. The molecular basis of this extended longevity has recently attracted attention. Telomere maintenance potentially underpins bats’ extended healthspan, although functional studies are still required to validate the causative mechanisms. In this review, we detail the current knowledge on bat telomeres, telomerase expression, and how these relate to ecology, longevity and life‐history strategies. Patterns of telomere shortening and telomerase expression vary across species, and comparative genomic analyses suggest that alternative telomere maintenance mechanisms evolved in the longest‐lived bats. We discuss the unique challenges faced when working with populations of wild bats and highlight ways to advance the field including expanding long‐term monitoring across species that display contrasting life‐histories and occupy different environmental niches. We further review how new high quality, chromosome‐level genome assemblies can enable us to uncover the molecular mechanisms governing telomere dynamics and how phylogenomic analyses can reveal the adaptive significance of telomere maintenance and variation in bats.

Leaf habit affects the distribution of drought sensitivity but not water transport efficiency in the tropics - German Vargas G.; Norbert Kunert; William M. Hammond; Z. Carter Berry; Leland K. Werden; Chris M. Smith‐Martin; Brett T. Wolfe; Laura Toro; Ariadna Mondragón‐Botero; Jesús N. Pinto‐Ledezma; Naomi B. Schwartz; María Uriarte; et al. (Ecology Letters, 2022)
Considering the global intensification of aridity in tropical biomes due to climate change, we need to understand what shapes the distribution of drought sensitivity in tropical plants. We conducted a pantropical data synthesis representing 1117 species to test whether xylem‐specific hydraulic conductivity (K S ), water potential at leaf turgor loss (Ψ TLP ) and water potential at 50% loss of K S (Ψ P50 ) varied along climate gradients. The Ψ TLP and Ψ P50 increased with climatic moisture only for evergreen species, but K S did not. Species with high Ψ TLP and Ψ P50 values were associated with both dry and wet environments. However, drought‐deciduous species showed high Ψ TLP and Ψ P50 values regardless of water availability, whereas evergreen species only in wet environments. All three traits showed a weak phylogenetic signal and a short half‐life. These results suggest strong environmental controls on trait variance, which in turn is modulated by leaf habit along climatic moisture gradients in the tropics.

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Age, growth and diet of crevalle jack ( Caranx hippos ) in the Gulf of Mexico - Amanda E. Jefferson; Matthew B. Jargowsky; Genevieve M. Ivec; Pearce T. Cooper; Jessica L. Carroll; Carissa L. Gervasi; Jennifer S. Rehage; John F. Mareska; Sean P. Powers; J. Marcus Drymon (Fisheries Management and Ecology, 2022)
The goals of this study were to generate baseline population dynamics parameters for Gulf of Mexico crevalle jack Caranx hippos and examine the foraging habits of Mississippi and Alabama crevalle jack. Specimens were collected from Mississippi, Alabama and Florida, and age was estimated from sagittal otoliths. Stomachs from some specimens were retained for dietary analyses. Age classes spanned 0–20 years. Overall growth was best represented by the logistic growth model, whereas sex‐specific growth was best represented by a version of the von Bertalanffy growth function that allowed L ∞ to vary by sex while holding k and t 0 constant between sexes. Fishes were more important to crevalle jack diet than invertebrates, and diet varied among locations and years. These findings will address fundamental knowledge gaps to inform age‐based stock assessments for crevalle jack and ecosystem approaches to fisheries management in the Gulf of Mexico.

Summer ecosystem structure in mountain lakes linked to interannual variability of lake ice, snowpack, and landscape attributes - Stephen M. Powers; Steven C. Fradkin; William Baccus; Carmen Archambault; John R. Boetsch; Matthew R. Brousil; Rebecca Lofgren; Ashley Rawhouser; Stephanie E. Hampton (Limnology and Oceanography, 2022)
Mountain lakes experience interannual variability in spring snowpack and ice cover that can lead to differences in physical, chemical, and biological properties in the succeeding summer. Lake studies that capture extreme years of snow and ice would be useful to understand and anticipate effects of climate change, but such data are rare for remote mountain lakes. Monitoring of lakes in Olympic, North Cascades, and Mount Rainier National Parks from 2007 to 2018 allowed us to examine limnological differences along interannual and elevation‐driven climate gradients that included unusually high (2011–2012) and 100‐yr record low (2015) snowpack years. Years with lower spring snowpack had earlier ice‐out. Across lakes, our analysis suggested an average of 0.075°C lake warming per day of lost ice duration (0.525°C per week), giving rise to other ecosystem changes linked to temperature such as lower dissolved oxygen, higher total dissolved N, higher chlorophyll, and higher abundance of cladoceran zooplankton. Conversely, in years with higher snowpack and a shorter ice‐free season, lakes were colder and clearer (1 m deeper Secchi depth for every 1 m May snow water equivalent), with more dilute ions as well as lower algal biomass and zooplankton abundance. These results add to evidence that changes in snowpack or ice‐out dates alter mountain lake ecology through multiple processes associated with hydrology, terrestrial‐aquatic connection, water temperature, productivity, ion composition, and plankton communities.

Transmission of Klebsiella strains and plasmids within and between grey‐headed flying fox colonies - Ben Vezina; Louise M. Judd; Fiona K. McDougall; Wayne S. J. Boardman; Michelle L. Power; Jane Hawkey; Sylvain Brisse; Jonathan M. Monk; Kathryn E. Holt; Kelly L. Wyres (Environmental Microbiology, 2022)
Summary The grey‐headed flying fox ( Pteropus poliocephalus ) is an endemic Australian fruit bat, known to carry zoonotic pathogens. We recently showed they harbour bacterial pathogen Klebsiella pneumoniae and closely related species in the K . pneumoniae species complex ( Kp SC); however, the dynamics of Kp SC transmission and gene flow within flying fox colonies are poorly understood. High‐resolution genome comparisons of 39 Kp SC isolates from grey‐headed flying foxes identified five putative strain transmission clusters (four intra‐ and one inter‐colony). The instance of inter‐colony strain transmission of K . africana was found between two flying fox populations within flying distance, indicating either direct or indirect transmission through a common food/water source. All 11 plasmids identified within the Kp SC isolates showed 73% coverage (mean) and ≥95% identity to human‐associated Kp SC plasmids, indicating gene flow between human clinical and grey‐headed flying fox isolates. Along with strain transmission, inter‐species horizontal plasmid transmission between K . pneumoniae and Klebsiella africana was also identified within a flying fox colony. Finally, genome‐scale metabolic models were generated to predict and compare substrate usage to previously published Kp SC models, from human and environmental sources. These models indicated no distinction on the basis of metabolic capabilities. Instead, metabolic capabilities were consistent with population structure and ST/lineage.

Transcriptomic Down-Regulation of Immune System Components in Barrier and Hematopoietic Tissues after Lipopolysaccharide Injection in Antarctic Notothenia coriiceps - Cármen S. V. Sousa; Deborah M. Power; Pedro M. Guerreiro; Bruno Louro; Liangbiao Chen; Adelino V. M. Canário (Fishes, 2022)
The environmental conditions and isolation in the Antarctic have driven the evolution of a unique biodiversity at a macro to microorganism scale. Here, we investigated the possible adaptation of the teleost Nototheniacoriiceps immune system to the cold environment and unique microbial community of the Southern Ocean. The fish immune system was stimulated through an intraperitoneal injection of lipopolysaccharide (LPS 0111:B4 from E. coli) and the tissue transcriptomic response and plasma biochemistry were analyzed 7 days later and compared to a sham injected control. Gene transcription in the head-kidney, intestine and skin was significantly modified by LPS, although tissues showed different responsiveness, with the duodenum most modified and the skin the least modified. The most modified processes in head-kidney, duodenum and skin were related to cell metabolism (up-regulated) and the immune system (comprising 30% of differentially expressed genes). The immune processes identified were mostly down-regulated, particularly interleukins and pattern recognition receptors (PRRs), nucleotide-binding oligomerization domain-like receptors and mannose receptors, unlike the toll-like receptors response commonly described in other teleost fish. The modified transcriptional response was not mirrored by a modified systemic response, as the circulating levels of enzymes of innate immunity, lysozyme and antiproteases, were not significantly different from the untreated and sham control fish. In conclusion, while the N.coriiceps immune system shares many features with other teleosts there are also some specificities. Further studies should better characterize the PRRs and their role in Antarctic teleosts, as well as the importance of the LPS source and its consequences for immune activation in teleosts.

Strategies to acquire and use phosphorus in phosphorus-impoverished and fire-prone environments - Hans Lambers; Patrícia de Britto Costa; Gregory R. Cawthray; Matthew D. Denton; Patrick M. Finnegan; Patrick E. Hayes; Rafael S. Oliveira; Simon C. Power; Kosala Ranathunge; Qi Shen; Xiao Wang; Hongtao Zhong (Plant and Soil, 2022)
Background Unveiling the diversity of plant strategies to acquire and use phosphorus (P) is crucial to understand factors promoting their coexistence in hyperdiverse P-impoverished communities within fire-prone landscapes such as in cerrado (South America), fynbos (South Africa) and kwongan (Australia). Scope We explore the diversity of P-acquisition strategies, highlighting one that has received little attention: acquisition of P following fires that temporarily enrich soil with P. This strategy is expressed by fire ephemerals as well as fast-resprouting perennial shrubs. A plant’s leaf manganese concentration ([Mn]) provides significant clues on P-acquisition strategies. High leaf [Mn] indicates carboxylate-releasing P-acquisition strategies, but other exudates may play the same role as carboxylates in P acquisition. Intermediate leaf [Mn] suggests facilitation of P acquisition by P-mobilising neighbours, through release of carboxylates or functionally similar compounds. Very low leaf [Mn] indicates that carboxylates play no immediate role in P acquisition. Release of phosphatases also represents a P-mining strategy, mobilising organic P. Some species may express multiple strategies, depending on time since germination or since fire, or on position in the landscape. In severely P-impoverished landscapes, photosynthetic P-use efficiency converges among species. Efficient species exhibit rapid rates of photosynthesis at low leaf P concentrations. A high P-remobilisation efficiency from senescing organs is another way to use P efficiently, as is extended longevity of plant organs. Conclusions Many P-acquisition strategies coexist in P-impoverished landscapes, but P-use strategies tend to converge. Common strategies of which we know little are those expressed by ephemeral or perennial species that are the first to respond after a fire. We surmise that carboxylate-releasing P-mobilising strategies are far more widespread than envisaged so far, and likely expressed by species that accumulate metals, exemplified by Mn, metalloids, such as selenium, fluorine, in the form of fluoroacetate, or silicon. Some carboxylate-releasing strategies are likely important to consider when restoring sites in biodiverse regions as well as in cropping systems on P-impoverished or strongly P-sorbing soils, because some species may only be able to establish themselves next to neighbours that mobilise P.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Nutrients and herbivores impact grassland stability across spatial scales through different pathways - Qingqing Chen; Shaopeng Wang; Eric W. Seabloom; Andrew S. MacDougall; Elizabeth T. Borer; Jonathan D. Bakker; Ian Donohue; Johannes M. H. Knops; John W. Morgan; Oliver Carroll; Mick Crawley; Miguel N. Bugalho; et al. (Global Change Biology, 2022)
Nutrients and herbivores are well‐known drivers of grassland diversity and stability in local communities. However, whether they interact to impact the stability of aboveground biomass and whether these effects depend on spatial scales remain unknown. It is also unclear whether nutrients and herbivores impact stability via different facets of plant diversity including species richness, evenness, and changes in community composition through time and space. We used a replicated experiment adding nutrients and excluding herbivores for 5 years in 34 global grasslands to explore these questions. We found that both nutrient addition and herbivore exclusion alone reduced stability at the larger spatial scale (aggregated local communities; gamma stability), but through different pathways. Nutrient addition reduced gamma stability primarily by increasing changes in local community composition over time, which was mainly driven by species replacement. Herbivore exclusion reduced gamma stability primarily by decreasing asynchronous dynamics among local communities (spatial asynchrony). Their interaction weakly increased gamma stability by increasing spatial asynchrony. Our findings indicate that disentangling the processes operating at different spatial scales may improve conservation and management aiming at maintaining the ability of ecosystems to reliably provide functions and services for humanity.

The 16th Workshop on Antarctic Meteorology and Climate and 6th Year of Polar Prediction in the Southern Hemisphere Meeting - David H. Bromwich; Matthew A. Lazzara; Arthur M. Cayette; Jordan G. Powers; Kirstin Werner; John J. Cassano; Steven R. Colwell; Scott Carpentier; Xun Zou (Advances in Atmospheric Sciences, 2022)

Reduced ecosystem resilience quantifies fine‐scale heterogeneity in tropical forest mortality responses to drought - Donghai Wu; German Vargas G.; Jennifer S. Powers; Nate G. McDowell; Justin M. Becknell; Daniel Pérez‐Aviles; David Medvigy; Yanlan Liu; Gabriel G. Katul; Julio César Calvo‐Alvarado; Ana Calvo‐Obando; Arturo Sanchez‐Azofeifa; et al. (Global Change Biology, 2022)
Sensitivity of forest mortality to drought in carbon‐dense tropical forests remains fraught with uncertainty, while extreme droughts are predicted to be more frequent and intense. Here, the potential of temporal autocorrelation of high‐frequency variability in Landsat Enhanced Vegetation Index (EVI), an indicator of ecosystem resilience, to predict spatial and temporal variations of forest biomass mortality is evaluated against in situ census observations for 64 site‐year combinations in Costa Rican tropical dry forests during the 2015 ENSO drought. Temporal autocorrelation, within the optimal moving window of 24 months, demonstrated robust predictive power for in situ mortality (leave‐one‐out cross‐validation R 2 = 0.54), which allows for estimates of annual biomass mortality patterns at 30 m resolution. Subsequent spatial analysis showed substantial fine‐scale heterogeneity of forest mortality patterns, largely driven by drought intensity and ecosystem properties related to plant water use such as forest deciduousness and topography. Highly deciduous forest patches demonstrated much lower mortality sensitivity to drought stress than less deciduous forest patches after elevation was controlled. Our results highlight the potential of high‐resolution remote sensing to “fingerprint” forest mortality and the significant role of ecosystem heterogeneity in forest biomass resistance to drought.

Reduced Cerebellar Brain Inhibition Measured Using Dual-Site TMS in Older Than in Younger Adults - B. K. Rurak; J. P. Rodrigues; B. D. Power; P. D. Drummond; A. M. Vallence (The Cerebellum, 2022)

Post-traumatic Osteoarthritis in Rabbits Following Traumatic Injury and Surgical Reconstruction of the Knee - Feng Wei; Madeleine J. F. Powers; Gerardo E. Narez; Loic M. Dejardin; Tammy Haut Donahue; Roger C. Haut (Annals of Biomedical Engineering, 2022)

Perspectives on the environmental implications of sustainable hydro-power: comparing countries, problems and approaches - K. Alfredsen; I. P. Helland; E. G. Martins; M. Power (Hydrobiologia, 2022)

A synoptic history of the development, production and environmental oversight of hydropower in Brazil, Canada, and Norway - K. Alfredsen; P.-A. Amundsen; L. Hahn; P. M. Harrison; I. P. Helland; E. G. Martins; W. M. Twardek; M. Power (Hydrobiologia, 2022)

Earlier snow melt and reduced summer precipitation alter floral traits important to pollination - John M. Powers; Heather M. Briggs; Rachel G. Dickson; Xinyu Li; Diane R. Campbell (Global Change Biology, 2022)
Climate change can cause changes in expression of organismal traits that influence fitness. In flowering plants, floral traits can respond to drought, and that phenotypic plasticity has the potential to affect pollination and plant reproductive success. Global climate change is leading to earlier snow melt in snow‐dominated ecosystems as well as affecting precipitation during the growing season, but the effects of snow melt timing on floral morphology and rewards remain unknown. We conducted crossed manipulations of spring snow melt timing (early vs. control) and summer monsoon precipitation (addition, control, and reduction) that mimicked recent natural variation, and examined plastic responses in floral traits of Ipomopsis aggregata over 3 years in the Rocky Mountains. We tested whether increased summer precipitation compensated for earlier snow melt, and if plasticity was associated with changes in soil moisture and/or leaf gas exchange. Lower summer precipitation decreased corolla length, style length, corolla width, sepal width, and nectar production, and increased nectar concentration. Earlier snow melt (taking into account natural and experimental variation) had the same effects on those traits and decreased inflorescence height. The effect of reduced summer precipitation was stronger in earlier snow melt years for corolla length and sepal width. Trait reductions were explained by drier soil during the flowering period, but this effect was only partially explained by how drier soils affected plant water stress, as measured by leaf gas exchange. We predicted the effects of plastic trait changes on pollinator visitation rates, pollination success, and seed production using prior studies on I. aggregata . The largest predicted effect of drier soil on relative fitness components via plasticity was a decrease in male fitness caused by reduced pollinator rewards (nectar production). Early snow melt and reduced precipitation are strong drivers of phenotypic plasticity, and both should be considered when predicting effects of climate change on plant traits in snow‐dominated ecosystems.

Tsunami Generation by Underwater Volcanic Explosions: Application to the 1952 Explosions of Myojinsho Volcano - Natalia Lipiejko; Colin N. Whittaker; Emily M. Lane; James D. L. White; William L. Power (Pure and Applied Geophysics, 2021)

The genetic and ecophysiological diversity of Microcystis - Gregory J. Dick; Melissa B. Duhaime; Jacob T. Evans; Reagan M. Errera; Casey M. Godwin; Jenan J. Kharbush; Helena S. Nitschky; McKenzie A. Powers; Henry A. Vanderploeg; Kathryn C. Schmidt; Derek J. Smith; Colleen E. Yancey; et al. (Environmental Microbiology, 2021)
Summary Microcystis is a cyanobacterium that forms toxic blooms in freshwater ecosystems around the world. Biological variation among taxa within the genus is apparent through genetic and phenotypic differences between strains and via the spatial and temporal distribution of strains in the environment, and this fine‐scale diversity exerts strong influence over bloom toxicity. Yet we do not know how varying traits of Microcystis strains govern their environmental distribution, the tradeoffs and links between these traits, or how they are encoded at the genomic level. Here we synthesize current knowledge on the importance of diversity within Microcystis and on the genes and traits that likely underpin ecological differentiation of taxa. We briefly review spatial and environmental patterns of Microcystis diversity in the field and genetic evidence for cohesive groups within Microcystis . We then compile data on strain‐level diversity regarding growth responses to environmental conditions and explore evidence for variation of community interactions across Microcystis strains. Potential links and tradeoffs between traits are identified and discussed. The resulting picture, while incomplete, highlights key knowledge gaps that need to be filled to enable new models for predicting strain‐level dynamics, which influence the development, toxicity and cosmopolitan nature of Microcystis blooms.

Temporal rarity is a better predictor of local extinction risk than spatial rarity - Peter A. Wilfahrt; Ashley L. Asmus; Eric W. Seabloom; Jeremiah A. Henning; Peter Adler; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Lars A. Brudvig; Marc Cadotte; Pedro Daleo; Anu Eskelinen; et al. (Ecology, 2021)
Spatial rarity is often used to predict extinction risk, but rarity can also occur temporally. Perhaps more relevant in the context of global change is whether a species is core to a community (persistent) or transient (intermittently present), with transient species often susceptible to human activities that reduce niche space. Using 5–12 yr of data on 1,447 plant species from 49 grasslands on five continents, we show that local abundance and species persistence under ambient conditions are both effective predictors of local extinction risk following experimental exclusion of grazers or addition of nutrients; persistence was a more powerful predictor than local abundance. While perturbations increased the risk of exclusion for low persistence and abundance species, transient but abundant species were also highly likely to be excluded from a perturbed plot relative to ambient conditions. Moreover, low persistence and low abundance species that were not excluded from perturbed plots tended to have a modest increase in abundance following perturbance. Last, even core species with high abundances had large decreases in persistence and increased losses in perturbed plots, threatening the long‐term stability of these grasslands. Our results demonstrate that expanding the concept of rarity to include temporal dynamics, in addition to local abundance, more effectively predicts extinction risk in response to environmental change than either rarity axis predicts alone.

Relationship Between Time-Weighted Head Impact Exposure on Directional Changes in Diffusion Imaging in Youth Football Players - Suraj K. Puvvada; Elizabeth M. Davenport; James M. Holcomb; Logan E. Miller; Christopher T. Whitlow; Alexander K. Powers; Joseph A. Maldjian; Joel D. Stitzel; Jillian E. Urban (Annals of Biomedical Engineering, 2021)

Feeding habitat and silvering stage affect lipid content and fatty acid composition of European eel Anguilla anguilla tissues - Camilla Parzanini; Michael T. Arts; Mehis Rohtla; Janet Koprivnikar; Michael Power; Anne Berit Skiftesvik; Howard I. Browman; Dino Milotic; Caroline M. F. Durif (Journal of Fish Biology, 2021)
Lipids, particularly fatty acids (FAs), are major sources of energy and nutrients in aquatic ecosystems and play key roles during vertebrate development. The European eel Anguilla anguilla goes through major biochemical and physiological changes throughout its lifecycle as it inhabits sea‐ (SW), and/or brackish‐ (BW) and/or freshwater (FW) habitats. With the ultimate goal being to understand the reasons for eels adopting a certain life history strategy (FW or SW residency vs . ‘habitat shifting’), we explored differences in lipid content and FA composition of muscle, liver and eyes from eels collected across Norwegian SW, BW and FW habitats, and at different lifecycle stages (yellow to silver). FW and SW eels had a higher lipid content overall compared to BW eels, reflecting differences in food availability and life history strategies. SW eels had higher proportions of certain monounsaturated FAs (MUFAs; 18:1n‐9, 20:1n‐9), and of the essential polyunsaturated FAs 20:5n‐3 (eicosapentaenoic acid, EPA) and 22:6n‐3 (docosahexaenoic acid) than FW eels, reflecting a marine‐based diet. In contrast, the muscle of FW eels had higher proportions of 18:3n‐3, 18:2n‐6 and 20:4n‐6 (arachidonic acid), as is typical of FW organisms. MUFA proportions increased in later stage eels, consistent with the hypothesis that the eels accumulate energy stores prior to migration. In addition, the decrease of EPA with advancing stage may be associated with the critical role that this FA plays in eel sexual development. Lipid and FA information provided further understanding of the habitat use and overall ecology of this critically endangered species.

Deciphering the role of cartilage protein 1 in human dermal fibroblasts: a transcriptomic approach - Sophia Letsiou; Manuel Manchado; Mariela Zografaki; Sofia Marka; Liliana Anjos; Dimitrios Skliros; Juan F. Martínez-Blanch; E. Flemetakis; Deborah M. Power (Functional & Integrative Genomics, 2021)

The representativeness of the dental calculus dietary record: insights from Taï chimpanzee faecal phytoliths - Robert C. Power; Roman M. Wittig; Jeffery R. Stone; Kornelius Kupczik; Ellen Schulz-Kornas (Archaeological and Anthropological Sciences, 2021)
In recent years, new applications of microremain dietary analysis using dental calculus as a source of dietary data on ancient human subsistence and behaviours have accelerated. The dental calculus of contemporary human and non-human populations with known diets have been used as reference datasets, including the chimpanzees of Taï National Park (Côte d'Ivoire), but explaining the preservation mechanism involved is challenged by our incomplete knowledge of the microremain content within the diets of these reference populations and our rudimentary information on microremain incorporation into dental calculus. Here, we analyse phytoliths in faecal samples to assess to what extent plant phytoliths of a diet are reflected in the dental calculus as well as in the egested faeces. In this study, we identify and document the faecal phytolith assemblages as an indicator of plant consumption in two Western chimpanzees of the Taï National Park (Côte d'Ivoire) before (wet season), during (dry season) and after (dry season) a dust-rich period. Moreover, observational dietary records of these two individuals were compiled to improve the interpretability of this dental calculus phytolith dataset. The faecal phytolith assemblages vary significantly across samples in terms of abundance and diversity. The most common phytolith morphotypes were eudicot plates, single-cell and multi-cell tracheids, monocot rugulose and echinate spheroids and, to a lesser extent, unspecified thick and thin elongates. High loads of grit and other micro-remains (e.g. diatoms) are found during the dry period. Using observational dietary records as a starting point and our faecal results as a terminus, we consider how dental calculus can accumulate phytoliths. Our findings enable identification of the phytolith morphotypes that are under-represented in dental calculus, which is highly informative for future dental calculus research strategies.

Research Priorities for Coastal Geoscience and Engineering: A Collaborative Exercise in Priority Setting From Australia - Hannah E. Power; Andrew W. M. Pomeroy; Michael A. Kinsela; Thomas P. Murray (Frontiers in Marine Science, 2021)
We present the result of a collaborative priority setting exercise to identify emerging issues and priorities in coastal geoscience and engineering (CGE). We use a ranking process to quantify the criticality of each priority from the perspective of Australian CGE researchers and practitioners. 74 activities were identified across seven categories: Data Collection and Collation, Coastal Dynamics and Processes, Modelling, Engineering Solutions, Coastal Hazards and Climate Change, Communication and Collaboration, and Infrastructure, Innovation, and Funding. We found consistent and unanimous support for the vast majority of priorities identified by the CGE community, with 91% of priorities being allocated a score of ≥ 3 out of 5 (i.e., above average levels of support) by ≥ 75% of respondents. Data Collection and Collation priorities received the highest average score, significantly higher than four of the other six categories, with Coastal Hazards and Climate Change the second ranked category and Engineering Solutions the lowest scoring category. Of the 74 priorities identified, 11 received unified and strong support across the CGE community and indicate a critical need for: additional coastal data collection including topographic and bathymetric, hydrodynamic, oceanographic, and remotely sensed data; improved data compilation and access; improved understanding of extreme events and the quantification of future impacts of climate change on nearshore dynamics and coastal development; enhanced quantification of shoreline change and coastal inundation processes; and, additional funding to support CGE research and applications to mitigate and manage coastal hazards. The outcomes of this priority setting exercise can be applied to guide policy development and decision-making in Australia and jurisdictions elsewhere. Further, the research and application needs identified here will contribute to addressing key practical challenges identified at a national level. CGE research plays a critical role in identifying and enabling social, environmental, and economic benefits through the proactive management of coastal hazard impacts and informed planning to mitigate the potential impacts of growing coastal risk, particularly in a changing climate. The prevalence and commonalities of the challenges faced by coastal communities globally due to increasing pressures from coastal hazards in a changing climate suggest that our findings will be applicable to other settings.

The clinical presentation, treatment and outcome of serologically confirmed paediatric Lyme disease in the Republic of Ireland over a 5-year period: a retrospective cohort study - Karina M. Forde; Joanne O’Gorman; Patrick J. Gavin; Matthew S. Dryden; Deirbhile Keady; Belinda Hanahoe; Colm McDonnell; Lorraine Power; Bartley Cryan; James Sweeney; Karl F. Conyard; Michael J. O’Grady (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Brain Strain: Computational Model-Based Metrics for Head Impact Exposure and Injury Correlation - Logan E. Miller; Jillian E. Urban; Elizabeth M. Davenport; Alexander K. Powers; Christopher T. Whitlow; Joseph A. Maldjian; Joel D. Stitzel (Annals of Biomedical Engineering, 2021)

Climate‐related geographical variation in performance traits across the invasion front of a widespread non‐native insect - Lily M. Thompson; Sean D. Powers; Ashley Appolon; Petra Hafker; Lelia Milner; Dylan Parry; Salvatore J. Agosta; Kristine L. Grayson (Journal of Biogeography, 2021)
Aim Invasive species are ideal systems for testing geographical differences in performance traits and measuring evolutionary responses as a species spreads across divergent climates and habitats. The European gypsy moth, Lymantria dispar dispar L. (Lepidoptera: Erebidae), is a generalist forest defoliator introduced to Medford, Massachusetts, USA in 1869. The invasion front extends from Minnesota to North Carolina and the ability of this species to adapt to local climate may contribute to its continuing spread. We evaluated the performance of populations along the climatic gradient of the invasion front to test for a relationship between climate and ecologically important performance traits. Location Eastern United States of America Taxon Lymantria dispar dispar L. (Lepidoptera: Erebidae) Methods Insects from 14 populations across the US invasion front and interior of the invasive range were reared from hatch to adult emergence in six constant temperature treatments. The responses of survival, pupal mass and larval development time were analysed as a function of source climate (annual mean normal temperature), rearing temperature and their interaction using multiple polynomial regression. Results With the exception of female development time, there were no significant interactions between source climate and rearing temperature, indicating little divergence in the shape of thermal reaction norms among populations. Source population and rearing temperature were significant predictors of survival and pupal mass. Independent of rearing temperature, populations from warmer climates had lower survival than those from colder climates, but attained larger body size despite similar development times. Larval development time was dependent on rearing temperature, but there were not consistent relationships with source climate. Main Conclusions Thermal adaptation can be an important factor shaping the spread of invasive species, particularly in the context of climate change. Our results suggest that L. d. dispar is highly plastic, but has undergone climate‐related adaptation in thermal performance and life‐history traits as it spread across North America.

Diet overlap of common and at-risk riverine benthic fishes before and after Round Goby (Neogobius melanostomus) invasion - B. L. Firth; M. S. Poesch; M. A. Koops; D. A. R. Drake; M. Power (Biological Invasions, 2021)

Global impacts of fertilization and herbivore removal on soil net nitrogen mineralization are modulated by local climate and soil properties - Anita C. Risch; Stefan Zimmermann; Barbara Moser; Martin Schütz; Frank Hagedorn; Jennifer Firn; Philip A. Fay; Peter B. Adler; Lori A. Biederman; John M. Blair; Elizabeth T. Borer; Arthur A. D. Broadbent; et al. (Global Change Biology, 2020)
Soil nitrogen (N) availability is critical for grassland functioning. However, human activities have increased the supply of biologically limiting nutrients, and changed the density and identity of mammalian herbivores. These anthropogenic changes may alter net soil N mineralization (soil net N min ), that is, the net balance between N mineralization and immobilization, which could severely impact grassland structure and functioning. Yet, to date, little is known about how fertilization and herbivore removal individually, or jointly, affect soil net N min across a wide range of grasslands that vary in soil and climatic properties. Here we collected data from 22 grasslands on five continents, all part of a globally replicated experiment, to assess how fertilization and herbivore removal affected potential (laboratory‐based) and realized (field‐based) soil net N min . Herbivore removal in the absence of fertilization did not alter potential and realized soil net N min . However, fertilization alone and in combination with herbivore removal consistently increased potential soil net N min. Realized soil net N min , in contrast, significantly decreased in fertilized plots where herbivores were removed. Treatment effects on potential and realized soil net N min were contingent on site‐specific soil and climatic properties. Fertilization effects on potential soil net N min were larger at sites with higher mean annual precipitation (MAP) and temperature of the wettest quarter (T.q.wet). Reciprocally, realized soil net N min declined most strongly with fertilization and herbivore removal at sites with lower MAP and higher T.q.wet. In summary, our findings show that anthropogenic nutrient enrichment, herbivore exclusion and alterations in future climatic conditions can negatively impact soil net N min across global grasslands under realistic field conditions. This is an important context‐dependent knowledge for grassland management worldwide.

Lifetime antiretroviral exposure and neurocognitive impairment in HIV - Precious Amusan; Christopher Power; M. John Gill; Daniela Gomez; Erika Johnson; Leah H. Rubin; Esther Fujiwara (Journal of NeuroVirology, 2020)

Microbial processing of plant remains is co‐limited by multiple nutrients in global grasslands - Raúl Ochoa‐Hueso; Elizabeth T. Borer; Eric W. Seabloom; Sarah E. Hobbie; Anita C. Risch; Scott L. Collins; Juan Alberti; Héctor A. Bahamonde; Cynthia S. Brown; Maria C. Caldeira; Pedro Daleo; Chris R. Dickman; et al. (Global Change Biology, 2020)
Microbial processing of aggregate‐unprotected organic matter inputs is key for soil fertility, long‐term ecosystem carbon and nutrient sequestration and sustainable agriculture. We investigated the effects of adding multiple nutrients (nitrogen, phosphorus and potassium plus nine essential macro‐ and micro‐nutrients) on decomposition and biochemical transformation of standard plant materials buried in 21 grasslands from four continents. Addition of multiple nutrients weakly but consistently increased decomposition and biochemical transformation of plant remains during the peak‐season, concurrent with changes in microbial exoenzymatic activity. Higher mean annual precipitation and lower mean annual temperature were the main climatic drivers of higher decomposition rates, while biochemical transformation of plant remains was negatively related to temperature of the wettest quarter. Nutrients enhanced decomposition most at cool, high rainfall sites, indicating that in a warmer and drier future fertilized grassland soils will have an even more limited potential for microbial processing of plant remains.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Development and deployment of KASP markers for multiple alleles of Lr34 in wheat - Tilin Fang; Lei Lei; Genqiao Li; Carol Powers; Robert M. Hunger; Brett F. Carver; Liuling Yan (Theoretical and Applied Genetics, 2020)
Key message Heterogeneous Lr34 genes for leaf rust in winter wheat cultivar ‘Duster’ and KASP markers for allelic variation in exon 11 and exon 22 of Lr34. Abstract Wheat, Triticum aestivum (2 n = 6 x = 42, AABBDD), is a hexaploid species, and each of three homoeologous genomes A, B, and D should have one copy for a gene in its ancestral form if the gene has no duplication. Previously reported leaf rust resistance gene Lr34 has one copy on the short arm of chromosome 7D in hexaploid wheat, and allelic variation in Lr34 is in intron 4, exon 11, exon 12, or exon 22. In this study, we discovered that Oklahoma hard red winter wheat cultivar ‘Duster’ (PI 644,016) has two copies of the Lr34 gene, the resistance allele Lr34a and the susceptibility allele Lr34b . Both Lr34a and Lr34b were mapped in the same linkage group on chromosome 7D in a doubled-haploid population generated from a cross between Duster and a winter wheat cultivar ‘Billings’ which carries the susceptibility allele Lr34c . A chromosomal fragment including Lr34 and at least two neighboring genes on its proximal side but excluding genes on its distal side was duplicated in Duster. The Duster Lr34ab allele was associated with tip necrosis and increased resistance against leaf rust at adult plants in the Duster × Billings DH population tested in the field, demonstrating the function of the Duster Lr34ab allele in wheat. We have developed KASP markers for allelic variation in exon 11 and exon 22 of Lr34 in wheat. These markers can be utilized to accelerate the selection of Lr34 in wheat.

Consequences of Piscine orthoreovirus genotype 1 (PRV‐1) infections in Chinook salmon ( Oncorhynchus tshawytscha ), coho salmon ( O. kisutch ) and rainbow trout ( O. mykiss ) - Maureen K. Purcell; Rachel L. Powers; Torunn Taksdal; Doug McKenney; Carla M. Conway; Diane G. Elliott; Mark Polinski; Kyle Garver; James Winton (Journal of Fish Diseases, 2020)
Piscine orthoreovirus genotype 1 (PRV‐1) is the causative agent of heart and skeletal muscle inflammation (HSMI) in farmed Atlantic salmon ( Salmo salar L.). The virus has also been found in Pacific salmonids in western North America, raising concerns about the risk to native salmon and trout. Here, we report the results of laboratory challenges using juvenile Chinook salmon, coho salmon and rainbow trout injected with tissue homogenates from Atlantic salmon testing positive for PRV‐1 or with control material. Fish were sampled at intervals to assess viral RNA transcript levels, haematocrit, erythrocytic inclusions and histopathology. While PRV‐1 replicated in all species, there was negligible mortality in any group. We observed a few erythrocytic inclusion bodies in fish from the PRV‐1‐infected groups. At a few time points, haematocrits were significantly lower in the PRV‐1‐infected groups relative to controls, but in no case was anaemia noted. The most common histopathological finding was mild, focal myocarditis in both the non‐infected controls and PRV‐1‐infected fish. All cardiac lesions were judged mild, and none were consistent with those of HSMI. Together, these results suggest all three species are susceptible to PRV‐1 infection, but in no case did infection cause notable disease in these experiments.

Mercury and stable isotope (δ13C and δ15N) trends in decapods of the Beaufort Sea - A. Loria; P. Archambault; A. Burt; A. Ehrman; C. Grant; M. Power; G. A. Stern (Polar Biology, 2020)

The 13th and 14th Workshops on Antarctic Meteorology and Climate - Matthew A. Lazzara; Sophie A. Orendorf; Taylor P. Norton; Jordan G. Powers; David H. Bromwich; Scott Carpentier; John J. Cassano; Steven R. Colwell; Arthur M. Cayette; Kirstin Werner (Advances in Atmospheric Sciences, 2020)

A catastrophic tropical drought kills hydraulically vulnerable tree species - Jennifer S. Powers; German Vargas G.; Timothy J. Brodribb; Naomi B. Schwartz; Daniel Pérez‐Aviles; Chris M. Smith‐Martin; Justin M. Becknell; Filippo Aureli; Roger Blanco; Erick Calderón‐Morales; Julio C. Calvo‐Alvarado; Ana Julieta Calvo‐Obando; et al. (Global Change Biology, 2020)
Drought‐related tree mortality is now a widespread phenomenon predicted to increase in magnitude with climate change. However, the patterns of which species and trees are most vulnerable to drought, and the underlying mechanisms have remained elusive, in part due to the lack of relevant data and difficulty of predicting the location of catastrophic drought years in advance. We used long‐term demographic records and extensive databases of functional traits and distribution patterns to understand the responses of 20–53 species to an extreme drought in a seasonally dry tropical forest in Costa Rica, which occurred during the 2015 El Niño Southern Oscillation event. Overall, species‐specific mortality rates during the drought ranged from 0% to 34%, and varied little as a function of tree size. By contrast, hydraulic safety margins correlated well with probability of mortality among species, while morphological or leaf economics spectrum traits did not. This firmly suggests hydraulic traits as targets for future research.

Tsunami Modelling with Static and Dynamic Tides in Drowned River Valleys with Morphological Constrictions - Kaya M. Wilson; Hannah E. Power (Pure and Applied Geophysics, 2020)

Evaluation of Australian Tsunami Warning Thresholds Using Inundation Modelling - Diana J. M. Greenslade; Burak Uslu; Stewart C. R. Allen; Claire L. Kain; Kaya M. Wilson; Hannah E. Power (Pure and Applied Geophysics, 2020)

Effect of Shallow Slip Amplification Uncertainty on Probabilistic Tsunami Hazard Analysis in Subduction Zones: Use of Long-Term Balanced Stochastic Slip Models - A. Scala; S. Lorito; F. Romano; S. Murphy; J. Selva; R. Basili; A. Babeyko; A. Herrero; A. Hoechner; F. Løvholt; F. E. Maesano; P. Perfetti; et al. (Pure and Applied Geophysics, 2020)

Methane Seeps on the US Atlantic Margin and Their Potential Importance to Populations of the Commercially Valuable Deep-Sea Red Crab, Chaceon quinquedens - Phillip J. Turner; Bernard Ball; Zoie Diana; Andrea Fariñas-Bermejo; Ian Grace; Doreen McVeigh; Megan M. Powers; Loïc Van Audenhaege; Svetlana Maslakova; Craig M. Young; Cindy L. Van Dover (Frontiers in Marine Science, 2020)

Defining Sex-Specific Habitat Suitability for a Northern Gulf of Mexico Shark Assemblage - J. M. Drymon; S. Dedman; J. T. Froeschke; E. A. Seubert; A. E. Jefferson; A. M. Kroetz; J. F. Mareska; S. P. Powers (Frontiers in Marine Science, 2020)

Machine learning models reveal neurocognitive impairment type and prevalence are associated with distinct variables in HIV/AIDS - Wei Tu; Patricia A. Chen; Noshin Koenig; Daniela Gomez; Esther Fujiwara; M. John Gill; Linglong Kong; Christopher Power (Journal of NeuroVirology, 2020)

The Presence of a High Peak Feature Within Low-Average Shear Stimuli Induces Quiescence in Venous Endothelial Cells - M. Franzoni; D. T. O’Connor; L. Marcar; D. Power; M. A. Moloney; E. G. Kavanagh; R. L. Leask; J. Nolan; P. A. Kiely; M. T. Walsh (Annals of Biomedical Engineering, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Unravelling the anthropogenic pathways of phosphorus in the food production and consumption system of Bangladesh through the lens of substance flow analysis - Bidhan Bhuson Roy; Rubel Biswas Chowdhury; Amit Robert Baroi; Shupa Rahman; Stephen M. Powers; Nick Milne; Mohammad Sujauddin (Journal of Industrial Ecology, 2019)
Phosphorus (P) is central to food production. Current understanding about the global phosphorus system is dominated by studies in wealthier nations where soil fertility, fertilizer supply chains, and agronomic tracking have long been established. In contrast, developing nations are experiencing major agricultural transitions and the associated phosphorus flows remain a significant knowledge gap. We compiled and analyzed several years of recent agricultural datasets for Bangladesh, currently the eighth most populous nation, using substance flow analysis for phosphorus. From 2000 to 2016, rice production increased by >50% and remained the dominant crop with remarkably higher phosphorus flow (49.96 kt in 2016) than all other crops. Phosphorus content of livestock products in 2016 exceeded 6.00 kt, more than double in the year 2000, driven primarily by phosphorus in milk and secondarily in meat/eggs. These agricultural changes coincided with a doubling of national phosphorus fertilizer consumption since 2000, a fourfold increase since the global food crisis (2009), and a pronounced rise in the phosphorus import dependency ratio, which was the highest among all countries compared. In turn, during 2010s fertilizer phosphorus use exceeded phosphorus as food + feed production leading to soil phosphorus accumulation, and loss as burned manure became one of the largest phosphorus flows in the entire system, equivalent to half of fertilizer use. This dramatic reconfiguration of the Bangladesh phosphorus system illustrates an important case of agricultural expansion and intensification that is still playing out, with similar situations occurring in developing nations where population growth rates are high, and access to commercial fertilizers has risen.

Transcutaneous electrical nerve stimulation improves fatigue performance of the treated and contralateral knee extensors - D. G. Behm; E. M. Colwell; G. M. J. Power; H. Ahmadi; A. S. M. Behm; A. Bishop; C. Murph; J. Pike; B. McAssey; K. Fraser; S. Kearley; M. Ryan (European Journal of Applied Physiology, 2019)

Assessing Nearshore Nekton Abundance, Substrate, and Environmental Conditions in the Northern Gulf of Mexico: Are There Differences Among Three Adjacent Coastal Areas and Have There Been Changes over Three Decades (1986–2015)? - Martin T. O’Connell; Mark S. Peterson; Sean P. Powers; Ann M. Uzee-O’Connell; E. John Anderson; J. Read Hendon (Estuaries and Coasts, 2019)

Trace and rare earth element geochemistry of Holocene hydromagnesite from Dujiali Lake, central Qinghai–Tibetan Plateau, China - Yongjie Lin; Mianping Zheng; Chuanyong Ye; Ian M. Power (Carbonates and Evaporites, 2019)

Listeria monocytogenes Cancer Vaccines: Bridging Innate and Adaptive Immunity - Zachary T. Morrow; Zachary M. Powers; John-Demian Sauer (Current Clinical Microbiology Reports, 2019)

Effects of dry‐season irrigation on leaf physiology and biomass allocation in tropical lianas and trees - Chris M. Smith‐Martin; Carolina L. Bastos; Omar R. Lopez; Jennifer S. Powers; Stefan A. Schnitzer (Ecology, 2019)
Lianas are more abundant in seasonal forests than in wetter forests and are thought to perform better than trees when light is abundant and water is limited. We tested the hypothesis that lianas perform better than trees during seasonal drought using a common garden experiment with 12 taxonomically diverse species (six liana and six tree species) in 12 replicated plots. We irrigated six of the plots during the dry season for four years, while the remaining six control plots received only ambient rainfall. In year 5, we measured stem diameters for all individuals and harvested above‐ and belowground biomass for a subset of individuals to quantify absolute growth and biomass allocation to roots, stems, and leaves, as well as total root length and maximum rooting depth. We also measured rate of photosynthesis, intrinsic water use efficiency ( iWUE ), pre‐dawn and midday water potential, and a set of functional and hydraulic traits. During the peak of the dry season, lianas in control plots had 54% higher predawn leaf water potentials (Ψ PD ), and 45% higher photosynthetic rates than trees in control plots. By contrast, during the peak of the wet season, these physiological differences between lianas and trees become less pronounced and, in some cases, even disappeared. Trees had higher specific leaf area ( SLA ) than lianas; however, no other functional trait differed between growth forms. Trees responded to the irrigation treatment with 15% larger diameters and 119% greater biomass than trees in control plots. Liana growth, however, did not respond to irrigation; liana diameter and biomass were similar in control and irrigation plots, suggesting that lianas were far less limited by soil moisture than were trees. Contrary to previous hypotheses, lianas did not have deeper roots than trees; however, lianas had longer roots per stem diameter than did trees. Our results support the hypothesis that lianas perform better and experience less physiological stress than trees during seasonal drought, suggesting clear differences between growth forms in response to altered rainfall regimes. Ultimately, better dry‐season performance may explain why liana abundance peaks in seasonal forests compared to trees, which peak in abundance in less seasonal, wetter forests.

Tiger sharks eat songbirds: reply - J. M. Drymon; K. Feldheim; A. M. V. Fournier; E. A. Seubert; A. E. Jefferson; A. M. Kroetz; S. P. Powers (Ecology, 2019)

Assessing the impact of charr research past, present, and future - Michael J. Hansen; Charles C. Krueger; Andrew M. Muir; Anders Klemetsen; Michael Power (Hydrobiologia, 2019)

Diel activity patterns in overwintering Labrador anadromous Arctic charr - I. M. Mulder; J. B. Dempson; I. A. Fleming; M. Power (Hydrobiologia, 2019)

Influences of environmental variation on anadromous Arctic charr from the Hornaday River, NWT - L. Chavarie; J. D. Reist; M. M. Guzzo; L. Harwood; M. Power (Hydrobiologia, 2019)

Tiger sharks eat songbirds: scavenging a windfall of nutrients from the sky - J. M. Drymon; K. Feldheim; A. M. V. Fournier; E. A. Seubert; A. E. Jefferson; A. M. Kroetz; S. P. Powers (Ecology, 2019)

Comparing total mercury concentrations of northern Dolly Varden, Salvelinus malma malma, in two Canadian Arctic rivers 1986–1988 and 2011–2013 - L. Tran; J. D. Reist; C. P. Gallagher; M. Power (Polar Biology, 2019)

Turbine entrainment and passage of potadromous fish through hydropower dams: Developing conceptual frameworks and metrics for moving beyond turbine passage mortality - Philip M. Harrison; Eduardo G. Martins; Dirk A. Algera; Trina Rytwinski; Brent Mossop; Alf J. Leake; Michael Power; Steven J. Cooke (Fish and Fisheries, 2019)
Potadromous fishes are vulnerable to involuntary entrainment through hydropower turbines. However, turbines can also provide a downstream passage route for potadromous fish. Here, we review evidence for turbine entrainment and passage in potadromous fish, and evaluate the effects of these processes on upstream and downstream populations. We develop conceptual frameworks and metrics to quantify vulnerability to turbine entrainment removals, and to quantify the efficiency of turbines as a downstream passage route. We highlight factors that influence these processes and provide case‐studies demonstrating their applicability. We found that juvenile potadromous fish are being entrained through turbines at rates high enough to impact upstream populations. Given that juvenile passage survival is often high, we argue that turbines provide an important downstream passage route for potadromous fish. We show that entrainment vulnerability is likely a function of interactions between in‐reservoir fish behaviour, habitat configuration and operations and thus not well captured by passage mortality estimates. Similarly, we show that while passage mortality can limit downstream passage efficiency, passage success is also dependent on reservoir and forebay navigation, along with survival and fitness in the downstream river. We advocate for a shift in focus away from estimates of passage mortality and injury, which have previously accounted for the majority of turbine passage research. Instead, we recommend an approach that focusses on quantification of the factors that influence downstream passage efficiency and entrainment vulnerability. Moreover, we highlight the need to better understand the broader scale impacts of these events on upstream and downstream populations.

Whole Genome Sequence Analysis of Burkholderia contaminans FFH2055 Strain Reveals the Presence of Putative β-Lactamases - José J. Degrossi; Cindy Merino; Adela M. Isasmendi; Lorena M. Ibarra; Chelsea Collins; Nicolás E. Bo; Mariana Papalia; Jennifer S. Fernandez; Claudia M. Hernandez; Krisztina M. Papp-Wallace; Robert A. Bonomo; Miryam S. Vazquez; et al. (Current Microbiology, 2019)

Social-ecological research in urban natural areas: an emergent process for integration - Michelle L. Johnson; D. S. Novem Auyeung; Nancy F. Sonti; Clara C. Pregitzer; Heather L. McMillen; Richard Hallett; Lindsay K. Campbell; Helen M. Forgione; Mina Kim; Sarah Charlop-Powers; Erika S. Svendsen (Urban Ecosystems, 2019)

Empiric neurocognitive performance profile discovery and interpretation in HIV infection - Daniela Gomez; Christopher Power; M. John Gill; Noshin Koenig; Roberto Vega; Esther Fujiwara (Journal of NeuroVirology, 2019)

Introduced European smelt (Osmerus eperlanus) affects food web and fish community in a large Norwegian lake - Antti P. Eloranta; Stein I. Johnsen; Michael Power; Kim M. Bærum; Odd Terje Sandlund; Anders G. Finstad; Sigurd Rognerud; Jon Museth (Biological Invasions, 2019)

Focal Ischaemic Infarcts Expand Faster in Cerebellar Cortex than Cerebral Cortex in a Mouse Photothrombotic Stroke Model - Nagarajesh Gorlamandala; Jasneet Parmar; Amanda J. Craig; John M. Power; Andrew J. Moorhouse; Arun V. Krishnan; Gary D. Housley (Translational Stroke Research, 2018)

Potential for offsetting diamond mine carbon emissions through mineral carbonation of processed kimberlite: an assessment of De Beers mine sites in South Africa and Canada - Evelyn M. Mervine; Sasha Wilson; Ian M. Power; Gregory M. Dipple; Connor C. Turvey; Jessica L. Hamilton; Sterling Vanderzee; Mati Raudsepp; Colette Southam; Juerg M. Matter; Peter B. Kelemen; Johann Stiefenhofer; et al. (Mineralogy and Petrology, 2018)

Context‐dependent interactions between pathogens and a mutualist affect pathogen fitness and mutualist benefits to hosts - Katherine M. Marchetto; Alison G. Power (Ecology, 2018)
Plants and animals host many microbial symbionts, including both pathogens and mutualists. However, most experimental studies include only one symbiont, and few examine interactions of more than two microbes with their host. Here, we examined whether coinfection with two pathogens causes a synergistic reduction in the benefits that hosts receive from a microbial mutualist. We also measured the effects of a microbial mutualist on the within‐ and between‐host competition between coinfecting pathogens. We manipulated the presence of Clover yellow vein virus (Cl YVV ), Bean common mosaic virus ( BCMV ), rhizobia bacteria, and nitrogen fertilizer in common beans ( Phaseolus vulgaris ). We found asymmetric, context‐dependent interactions among the three microbial symbionts and their host. Coinfection with both viruses led to greater than additive negative effects on the amount of nitrogen that plants received from rhizobia. Rhizobia colonization decreased immune signaling in singly infected plants, but not in coinfected plants. Compared to single Cl YVV infection, Cl YVV reached higher concentrations within hosts coinfected with BCMV , but only in the presence of rhizobia. Coinfection increased BCMV vertical transmission rates for plants without supplemental nitrogen, but overall vertical transmission opportunities were not affected due to reduced seed production. Examining interactions between multiple microbes sharing a host can reveal important insights about nutrient cycling, disease severity, and pathogen epidemiology.

Diverse effects of the common hippopotamus on plant communities and soil chemistry - Douglas J. McCauley; Stuart I. Graham; Todd E. Dawson; Mary E. Power; Mordecai Ogada; Wanja D. Nyingi; John M. Githaiga; Judith Nyunja; Lacey F. Hughey; Justin S. Brashares (Oecologia, 2018)

Stable‐isotope analysis reveals the importance of soft‐bodied prey in the diet of lesser spotted dogfish Scyliorhinus canicula - Alina M. Wieczorek; Anne Marie Power; Patricia Browne; Conor T. Graham (Journal of Fish Biology, 2018)
This study examines the diet of lesser spotted dogfish Scyliorhinus canicula , one of the most ubiquitous predators of European coastal waters. This species is of increasing ecological significance as other large predatory fish decline as it has known interactions with fisheries. Scyliorhinus canicula diet was investigated in Irish coastal waters during June and July 2014 using both stomach‐content analysis and δ 13 C and δ 15 N stable‐isotope ratios. Prey contribution to the diet from dual stable‐isotope data was estimated using Bayesian mixing models. It was found that only stable‐isotope analysis provided a time‐integrated picture of the diet of S. canicula and allowed for a new estimation of their trophic position. Trophic positions from stomach‐content analysis within the present study and previous studies were found to be higher than revealed by isotopes. Stomach‐content analysis could not reveal the importance of soft‐bodied animals in the diet of these fish, however this approach remains a valuable tool to understand the potential prey spectrum in advance of isotope analysis and allows for a better resolution down to species level. The results highlight a greater variety in the diet of this important predator and the benefit of taking a multidisciplinary approach in dietary studies.

Recent ecological change in ancient lakes - Stephanie E. Hampton; Suzanne McGowan; Ted Ozersky; Salvatore G. P. Virdis; Tuong Thuy Vu; Trisha L. Spanbauer; Benjamin M. Kraemer; George Swann; Anson W. Mackay; Stephen M. Powers; Michael F. Meyer; Stephanie G. Labou; et al. (Limnology and Oceanography, 2018)
Ancient lakes are among the best archivists of past environmental change, having experienced more than one full glacial cycle, a wide range of climatic conditions, tectonic events, and long association with human settlements. These lakes not only record long histories of environmental variation and human activity in their sediments, but also harbor very high levels of biodiversity and endemism. Yet, ancient lakes are faced with a familiar suite of anthropogenic threats, which may degrade the unusual properties that make them especially valuable to science and society. In all ancient lakes for which data exist, significant warming of surface waters has occurred, with a broad range of consequences. Eutrophication threatens both native species assemblages and regional economies reliant on clean surface water, fisheries, and tourism. Where sewage contributes nutrients and heavy metals, one can anticipate the occurrence of less understood emerging contaminants, such as pharmaceuticals, personal care products, and microplastics that negatively affect lake biota and water quality. Human populations continue to increase in most of the ancient lakes’ watersheds, which will exacerbate these concerns. Further, human alterations of hydrology, including those produced through climate change, have altered lake levels. Co‐occurring with these impacts have been intentional and unintentional species introductions, altering biodiversity. Given that the distinctive character of each ancient lake is strongly linked to age, there may be few options to remediate losses of species or other ecosystem damage associated with modern ecological change, heightening the imperative for understanding these systems.

Effects of competition and herbivory over woody seedling growth in a temperate woodland trump the effects of elevated CO2 - L. Collins; M. M. Boer; V. Resco de Dios; S. A. Power; E. R. Bendall; S. Hasegawa; R. Ochoa Hueso; J. Piñeiro Nevado; R. A. Bradstock (Oecologia, 2018)

What shapes plant and animal diversity on urban golf courses? - Sabine S. Nooten; Patrick Schultheiss; Jules Wright; Catriona Macdonald; Brajesh K. Singh; James M. Cook; Sally A. Power (Urban Ecosystems, 2018)

Socio-environmental consideration of phosphorus flows in the urban sanitation chain of contrasting cities - Geneviève S. Metson; Steve M. Powers; Rebecca L. Hale; Jesse S. Sayles; Gunilla Öberg; Graham K. MacDonald; Yusuke Kuwayama; Nathaniel P. Springer; Anthony J. Weatherley; Kelly L. Hondula; Kristal Jones; Rubel B. Chowdhury; et al. (Regional Environmental Change, 2018)

A Meta-analysis of Arsenic Exposure and Lung Function: Is There Evidence of Restrictive or Obstructive Lung Disease? - Tiffany R. Sanchez; Martha Powers; Matthew Perzanowski; Christine M. George; Joseph H. Graziano; Ana Navas-Acien (Current Environmental Health Reports, 2018)

Structural and functional maturation of skin during metamorphosis in the Atlantic halibut (Hippoglossus hippoglossus) - Ricardo N. Alves; Kristina S. Sundell; Liliana Anjos; Henrik Sundh; Torstein Harboe; Birgitta Norberg; Deborah M. Power (Cell and Tissue Research, 2018)

Trophic niche dynamics of three nearshore benthic predators in The Bahamas - Oliver N. Shipley; Karen J. Murchie; Michael G. Frisk; Owen R. O’Shea; Maggie M. Winchester; Edward J. Brooks; Jessie Pearson; Michael Power (Hydrobiologia, 2018)

Metabolomics of tomato xylem sap during bacterial wilt reveals Ralstonia solanacearum produces abundant putrescine, a metabolite that accelerates wilt disease - Tiffany M. Lowe‐Power; Connor G. Hendrich; Edda von Roepenack‐Lahaye; Bin Li; Dousheng Wu; Raka Mitra; Beth L. Dalsing; Patrizia Ricca; Jacinth Naidoo; David Cook; Amy Jancewicz; Patrick Masson; et al. (Environmental Microbiology, 2018)
Summary Ralstonia solanacearum thrives in plant xylem vessels and causes bacterial wilt disease despite the low nutrient content of xylem sap. We found that R. solanacearum manipulates its host to increase nutrients in tomato xylem sap, enabling it to grow better in sap from infected plants than in sap from healthy plants. Untargeted GC/MS metabolomics identified 22 metabolites enriched in R. solanacearum ‐infected sap. Eight of these could serve as sole carbon or nitrogen sources for R. solanacearum . Putrescine, a polyamine that is not a sole carbon or nitrogen source for R. solanacearum , was enriched 76‐fold to 37 µM in R. solanacearum ‐infected sap. R. solanacearum synthesized putrescine via a SpeC ornithine decarboxylase. A Δ speC mutant required ≥ 15 µM exogenous putrescine to grow and could not grow alone in xylem even when plants were treated with putrescine. However, co‐inoculation with wildtype rescued ΔspeC growth, indicating R. solanacearum produced and exported putrescine to xylem sap. Intriguingly, treating plants with putrescine before inoculation accelerated wilt symptom development and R. solanacearum growth and systemic spread. Xylem putrescine concentration was unchanged in putrescine‐treated plants, so the exogenous putrescine likely accelerated disease indirectly by affecting host physiology. These results indicate that putrescine is a pathogen‐produced virulence metabolite.

Molecular testing of adult Pacific salmon and trout ( Oncorhynchus spp.) for several RNA viruses demonstrates widespread distribution of piscine orthoreovirus in Alaska and Washington - M K Purcell; R L Powers; J Evered; J Kerwin; T R Meyers; B Stewart; J R Winton (Journal of Fish Diseases, 2018)
This research was initiated in conjunction with a systematic, multiagency surveillance effort in the United States (U.S.) in response to reported findings of infectious salmon anaemia virus ( ISAV ) RNA in British Columbia, Canada. In the systematic surveillance study reported in a companion paper, tissues from various salmonids taken from Washington and Alaska were surveyed for ISAV RNA using the U.S.‐approved diagnostic method, and samples were released for use in this present study only after testing negative. Here, we tested a subset of these samples for ISAV RNA with three additional published molecular assays, as well as for RNA from salmonid alphavirus ( SAV ), piscine myocarditis virus ( PMCV ) and piscine orthoreovirus ( PRV ). All samples ( n = 2,252; 121 stock cohorts) tested negative for RNA from ISAV , PMCV , and SAV . In contrast, there were 25 stock cohorts from Washington and Alaska that had one or more individuals test positive for PRV RNA ; prevalence within stocks varied and ranged from 2% to 73%. The overall prevalence of PRV RNA ‐positive individuals across the study was 3.4% (77 of 2,252 fish tested). Findings of PRV RNA were most common in coho ( Oncorhynchus kisutch Walbaum) and Chinook ( O. tshawytscha Walbaum) salmon.

A comparison of the trophic ecology of Beaufort Sea Gadidae using fatty acids and stable isotopes - J. D. Brewster; C. Giraldo; E. S. Choy; S. A. MacPhee; C. Hoover; B. Lynn; D. G. McNicholl; A. Majewski; B. Rosenberg; M. Power; J. D. Reist; L. L. Loseto (Polar Biology, 2018)

5-HT modulation of pain perception in humans - Sarah L. Martin; Andrea Power; Yvonne Boyle; Ian M. Anderson; Monty A. Silverdale; Anthony K. P. Jones (Psychopharmacology, 2017)

Locus Mapping, Molecular Cloning, and Expression Analysis of rps6kb2, a Novel Metamorphosis-Related Gene in Chinese Tongue Sole (Cynoglossus semilaevis) - Yang Liu; Min Wei; Hua Guo; Changwei Shao; Liang Meng; Wenteng Xu; Na Wang; Lei Wang; Deborah M Power; Jilun Hou; Shahid Mahboob; Zhongkai Cui; et al. (Marine Biotechnology, 2017)

Daily temperature experience and selection by adfluvial bull trout (Salvelinus confluentus) - L. F. G. Gutowsky; P. M. Harrison; E. G. Martins; A. Leake; D. A. Patterson; D. Z. Zhu; M. Power; S. J. Cooke (Environmental Biology of Fishes, 2017)

Thermal pasteurization of ready-to-eat foods and vegetables: Critical factors for process design and effects on quality - Jing Peng; Juming Tang; Diane M. Barrett; Shyam S. Sablani; Nathan Anderson; Joseph R. Powers (Critical Reviews in Food Science and Nutrition, 2017)

Tsunami runup and tide-gauge observations from the 14 November 2016 M7.8 Kaikōura earthquake, New Zealand - William Power; Kate Clark; Darren N. King; Jose Borrero; Jamie Howarth; Emily M. Lane; Derek Goring; James Goff; Catherine Chagué-Goff; James Williams; Catherine Reid; Colin Whittaker; et al. (Pure and Applied Geophysics, 2017)

Comparative Dietary Diversity and Trophic Ecology of Two Estuarine Mesopredators - Andrea M. Kroetz; J. Marcus Drymon; Sean P. Powers (Estuaries and Coasts, 2017)

Effects of Inundation by the 14th November, 2016 Kaikōura Tsunami on Banks Peninsula, Canterbury, New Zealand - Emily M. Lane; Jose Borrero; Colin N. Whittaker; Jo Bind; Catherine Chagué-Goff; James Goff; Derek Goring; Jo Hoyle; Christof Mueller; William L. Power; Catherine M. Reid; James H. Williams; et al. (Pure and Applied Geophysics, 2017)

Individual isotopic specializations predict subsequent inter‐individual variation in movement in a freshwater fish - P. M. Harrison; L. F. G. Gutowsky; E. G. Martins; T. D. Ward; D. A. Patterson; S. J. Cooke; M. Power (Ecology, 2017)
Despite many similarities and intuitive links between individual dietary specialization and behavioral inter‐individual variation, these phenomena have been studied in isolation, and empirical data confirming relationships between these intraspecific variance sources are lacking. Here we use stable isotope analysis and acoustic telemetry to test the hypothesis that individual specialization in trophic (δ 15 N) and littoral/pelagic prey reliance (δ 13 C) covary with inter‐individual variation in movement in a group of 34 free‐swimming burbot ( Lota lota ). By performing stable isotope analysis on tissues with differing isotopic turnover rates (anal fin and dorsal muscle), in 24 lethally sampled burbot, we demonstrate that individual specialization in trophic niche (δ 15 N) and littoral/pelagic prey reliance (δ 13 C) occurred within the population. By performing stable isotope analysis on anal fins of a group of telemetry tagged burbot, we were able to show that interactions between trophic niche and littoral/pelagic prey reliance, explained a significant proportion of the subsequent between‐individual variance in mean movement rates. These findings demonstrate an empirical connection between behavioral inter‐individual variation and dietary specialization, thus providing a substantial expansion of our understanding of the wider ecological consequences of these interesting phenomena.

cis-Jasmone Elicits Aphid-Induced Stress Signalling in Potatoes - Islam S. Sobhy; Christine M. Woodcock; Stephen J. Powers; John C. Caulfield; John A. Pickett; Michael A. Birkett (Journal of Chemical Ecology, 2017)

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Probabilistic Hazard of Tsunamis Generated by Submarine Landslides in the Cook Strait Canyon (New Zealand) - Emily M. Lane; Joshu J. Mountjoy; William L. Power; Christof Mueller (Pure and Applied Geophysics, 2016)

Northern Dolly Varden charr total mercury concentrations: variation by life-history type - L. Tran; J. D. Reist; M. Power (Hydrobiologia, 2016)

Attentional function and basal forebrain cholinergic neuron morphology during aging in the Ts65Dn mouse model of Down syndrome - Brian E. Powers; Ramon Velazquez; Christy M. Kelley; Jessica A. Ash; Myla S. Strawderman; Melissa J. Alldred; Stephen D. Ginsberg; Elliott J. Mufson; Barbara J. Strupp (Brain Structure and Function, 2016)

Contribution of lianas to plant area index and canopy structure in a Panamanian forest - M. Elizabeth Rodríguez‐Ronderos; Gil Bohrer; Arturo Sanchez‐Azofeifa; Jennifer S. Powers; Stefan A. Schnitzer (Ecology, 2016)
Lianas are an important component of tropical forests, where they reduce tree growth, fecundity, and survival. Competition for light from lianas may be intense; however, the amount of light that lianas intercept is poorly understood. We used a large‐scale liana‐removal experiment to quantify light interception by lianas in a Panamanian secondary forest. We measured the change in plant area index ( PAI ) and forest structure before and after cutting lianas (for 4 yr) in eight 80 m × 80 m plots and eight control plots (16 plots total). We used ground‐based Li DAR to measure the 3‐dimensional canopy structure before cutting lianas, and then annually for 2 yr afterwards. Six weeks after cutting lianas, mean plot PAI was 20% higher in control vs. liana removal plots. One yr after cutting lianas, mean plot PAI was ~17% higher in control plots. The differences between treatments diminished significantly 2 yr after liana cutting and, after 4 yr, trees had fully compensated for liana removal. Ground‐based Li DAR revealed that lianas attenuated light in the upper‐ and middle‐forest canopy layers, and not only in the upper canopy as was previously suspected. Thus, lianas compete with trees by intercepting light in the upper‐ and mid‐canopy of this forest.

Burbot and large hydropower in North America: benefits, threats and research needs for mitigation - P. M. Harrison; L. F. G. Gutowsky; E. G. Martins; D. A. Patterson; S. J. Cooke; M. Power (Fisheries Management and Ecology, 2016)
In North America, burbot Lota lota (L.), interactions with hydropower are common, southern burbot populations are endangered and hydropower has been implicated in the decline. Thus, the objectives of this review were to identify threats and benefits of hydropower to riverine and reservoir dwelling burbot, assess overall impacts and identify key research needs for mitigation. Review findings suggest that while winter hydropower discharge regimes threaten riverine burbot spawning, burbot often successfully exploit reservoir environments. Further, while turbine entrainment has been hypothesised as a factor in the decline of burbot populations, low adult vulnerability to passage and a high resilience to juvenile removals likely mean risk to populations is low. Identified research needs include better definitions of flow and temperature requirements for riverine burbot and a quantification of the potential for reservoirs to act as source populations for downstream impacted zones. This review highlights the Pacific watershed focus of existing work and calls for status assessments and ecological research of burbot in North American Arctic and Atlantic watersheds where large hydropower and burbot interactions are common yet rarely studied.

Forest composition modifies litter dynamics and decomposition in regenerating tropical dry forest - Erik M. Schilling; Bonnie G. Waring; Jonathan S. Schilling; Jennifer S. Powers (Oecologia, 2016)

Temporal plasticity in thermal‐habitat selection of burbot Lota lota a diel‐migrating winter‐specialist - P. M. Harrison; L. F. G. Gutowsky; E. G. Martins; D. A. Patterson; S. J. Cooke; M. Power (Journal of Fish Biology, 2016)
In this study, animal‐borne telemetry with temperature sensors was coupled with extensive habitat temperature monitoring in a dimictic reservoir, to test the following hypotheses: behavioural thermoregulation occurs throughout the year and temperature selection varies on a diel and seasonal basis, in a winter‐specialist diel‐migrating fish. Burbot Lota lota demonstrated nightly behavioural thermoregulation throughout the year, with a large seasonal shift between selection for very cold temperatures ( L. lota avoided habitats warmer than optimal for reproduction and feeding during the spawning and non‐reproductive periods, respectively, active selection was limited to selection for 4–6° C habitat during the prespawning period. Although behavioural thermoregulation explained the night‐time migration, behavioural thermoregulation only partially explained daytime behaviour, indicating that diel migration is best explained by a combination of factors. Thus, thermal‐habitat selection was a good predictor of night‐time habitat occupancy in a diel‐migrating species. Together, these results show that thermal‐habitat selection by fishes may be important throughout the year and a more seasonally plastic behaviour than previously recognized.

The 10th Antarctic meteorological observation, modeling, and forecasting workshop - Steve R. Colwell; Arthur M. Cayette; Matthew A. Lazzara; Jordan G. Powers; David H. Bromwich; John J. Cassano; Scott Carpentier (Advances in Atmospheric Sciences, 2016)

A moving target—incorporating knowledge of the spatial ecology of fish into the assessment and management of freshwater fish populations - Steven J. Cooke; Eduardo G. Martins; Daniel P. Struthers; Lee F. G. Gutowsky; Michael Power; Susan E. Doka; John M. Dettmers; David A. Crook; Martyn C. Lucas; Christopher M. Holbrook; Charles C. Krueger (Environmental Monitoring and Assessment, 2016)

Slimy Sculpin (Cottus cognatus) annual growth in contrasting regulated and unregulated riverine environments - B. Kelly; K. E. Smokorowski; M. Power (Hydrobiologia, 2016)

Interactions between Bacteria And Aspen Defense Chemicals at the Phyllosphere – Herbivore Interface - Charles J. Mason; Tiffany M. Lowe-Power; Kennedy F. Rubert-Nason; Richard L. Lindroth; Kenneth F. Raffa (Journal of Chemical Ecology, 2016)

Transient up- and down-regulation of expression of myosin light chain 2 and myostatin mRNA mark the changes from stratified hyperplasia to muscle fiber hypertrophy in larvae of gilthead sea bream (Sparus aurata L.) - Stella Georgiou; Hélène Alami-Durante; Deborah M. Power; Elena Sarropoulou; Zissis Mamuris; Katerina A. Moutou (Cell and Tissue Research, 2016)

Shifting grassland plant community structure drives positive interactive effects of warming and diversity on aboveground net primary productivity - Jane M. Cowles; Peter D. Wragg; Alexandra J. Wright; Jennifer S. Powers; David Tilman (Global Change Biology, 2016)
Ecosystems worldwide are increasingly impacted by multiple drivers of environmental change, including climate warming and loss of biodiversity. We show, using a long‐term factorial experiment, that plant diversity loss alters the effects of warming on productivity. Aboveground primary productivity was increased by both high plant diversity and warming, and, in concert, warming (≈1.5 °C average above and belowground warming over the growing season) and diversity caused a greater than additive increase in aboveground productivity. The aboveground warming effects increased over time, particularly at higher levels of diversity, perhaps because of warming‐induced increases in legume and C4 bunch grass abundances, and facilitative feedbacks of these species on productivity. Moreover, higher plant diversity was associated with the amelioration of warming‐induced environmental conditions. This led to cooler temperatures, decreased vapor pressure deficit, and increased surface soil moisture in higher diversity communities. Root biomass (0–30 cm) was likewise consistently greater at higher plant diversity and was greater with warming in monocultures and at intermediate diversity, but at high diversity warming had no detectable effect. This may be because warming increased the abundance of legumes, which have lower root : shoot ratios than the other types of plants. In addition, legumes increase soil nitrogen (N) supply, which could make N less limiting to other species and potentially decrease their investment in roots. The negative warming × diversity interaction on root mass led to an overall negative interactive effect of these two global change factors on the sum of above and belowground biomass, and thus likely on total plant carbon stores. In total, plant diversity increased the effect of warming on aboveground net productivity and moderated the effect on root mass. These divergent effects suggest that warming and changes in plant diversity are likely to have both interactive and divergent impacts on various aspects of ecosystem functioning.

Lianas suppress seedling growth and survival of 14 tree species in a Panamanian tropical forest - Laura Martínez‐Izquierdo; María M. García; Jennifer S. Powers; Stefan A. Schnitzer (Ecology, 2016)
Lianas are a common plant growth form in tropical forests, where they compete intensely with trees, decreasing tree recruitment, growth, and survival. If the detrimental effects of lianas vary significantly with tree species identity, as is often assumed, then lianas may influence tree species diversity and community composition. Furthermore, recent studies have shown that liana abundance and biomass are increasing relative to trees in neotropical forests, which will likely magnify the detrimental effects of lianas and may ultimately alter tree species diversity, relative abundances, and community composition. Few studies, however, have tested the responses of multiple tree species to the presence of lianas in robust, well‐replicated experiments. We tested the hypotheses that lianas reduce tree seedling growth and survival, and that the effect of lianas varies with tree species identity. We used a large‐scale liana removal experiment in Central Panama in which we planted 14 replicate seedlings of 14 different tree species that varied in shade tolerance in each of 16 80 × 80 m plots (eight liana‐removal and eight unmanipulated controls; 3136 total seedlings). Over a nearly two‐yr period, we found that tree seedlings survived 75% more, grew 300% taller, and had twice the aboveground biomass in liana‐removal plots than seedlings in control plots, consistent with strong competition between lianas and tree seedlings. There were no significant differences in the response of tree species to liana competition (i.e., there was no species by treatment interaction), indicating that lianas had a similar negative effect on all 14 tree species. Furthermore, the effect of lianas did not vary with tree species shade tolerance classification, suggesting that the liana effect was not solely based on light. Based on these findings, recently observed increases in liana abundance in neotropical forests will substantially reduce tree regeneration, but will not significantly alter tropical tree species diversity, relative abundance, or community composition.

An analysis of P seudomonas genomic diversity in take‐all infected wheat fields reveals the lasting impact of wheat cultivars on the soil microbiota - T. H. Mauchline; D. Chedom‐Fotso; G. Chandra; T. Samuels; N. Greenaway; A. Backhaus; V. McMillan; G. Canning; S. J. Powers; K. E. Hammond‐Kosack; P. R. Hirsch; I. M. Clark; et al. (Environmental Microbiology, 2015)
Summary Manipulation of the soil microbiota associated with crop plants has huge promise for the control of crop pathogens. However, to fully realize this potential we need a better understanding of the relationship between the soil environment and the genes and phenotypes that enable microbes to colonize plants and contribute to biocontrol. A recent 2 years of investigation into the effect of wheat variety on second year crop yield in the context of take‐all fungal infection presented the opportunity to examine soil microbiomes under closely defined field conditions. Amplicon sequencing of second year soil samples showed that P seudomonas spp. were particularly affected by the wheat cultivar grown in year one. Consequently, 318 rhizosphere‐associated P seudomonas fluorescens strains were isolated and characterized across a variety of genetic and phenotypic traits. Again, the wheat variety grown in the first year of the study was shown to exert considerable selective pressure on both the extent and nature of P seudomonas genomic diversity. Furthermore, multiple significant correlations were identified within the phenotypic/genetic structure of the Pseudomonas population, and between individual genotypes and the external wheat field environment. The approach outlined here has considerable future potential for our understanding of plant–microbe interactions, and for the broader analysis of complex microbial communities.

Nitrogen, phosphorus, and cation use efficiency in stands of regenerating tropical dry forest - Bonnie G. Waring; Justin M. Becknell; Jennifer S. Powers (Oecologia, 2015)

Fish community dynamics following dam removal in a fragmented agricultural stream - Matthew S. Kornis; Brian C. Weidel; Stephen M. Powers; Matthew W. Diebel; Timothy J. Cline; Justin M. Fox; James F. Kitchell (Aquatic Sciences, 2015)

Acidification effects on biofouling communities: winners and losers - Lloyd S. Peck; Melody S. Clark; Deborah Power; João Reis; Frederico M. Batista; Elizabeth M. Harper (Global Change Biology, 2015)
How ocean acidification affects marine life is a major concern for science and society. However, its impacts on encrusting biofouling communities, that are both the initial colonizers of hard substrata and of great economic importance, are almost unknown. We showed that community composition changed significantly, from 92% spirorbids, 3% ascidians and 4% sponges initially to 47% spirorbids, 23% ascidians and 29% sponges after 100 days in acidified conditions (pH 7.7). In low pH, numbers of the spirorbid Neodexiospira pseudocorrugata were reduced ×5 compared to controls. The two ascidians present behaved differently with Aplidium sp. decreasing ×10 in pH 7.7, whereas Molgula sp. numbers were ×4 higher in low pH than controls. Calcareous sponge ( Leucosolenia sp.) numbers increased ×2.5 in pH 7.7 over controls. The diatom and filamentous algal community was also more poorly developed in the low pH treatments compared to controls. Colonization of new surfaces likewise showed large decreases in spirorbid numbers, but numbers of sponges and Molgula sp. increased. Spirorbid losses appeared due to both recruitment failure and loss of existing tubes. Spirorbid tubes are comprised of a loose prismatic fabric of calcite crystals. Loss of tube materials appeared due to changes in the binding matrix and not crystal dissolution, as SEM analyses showed crystal surfaces were not pitted or dissolved in low pH conditions. Biofouling communities face dramatic future changes with reductions in groups with hard exposed exoskeletons and domination by soft‐bodied ascidians and sponges.

Data dialogues: critical connections for designing and implementing future nanomaterial research - Christina M. Powers; Khara D. Grieger; Christian Beaudrie; Christine Ogilvie Hendren; J. Michael Davis; Amy Wang; Christie M. Sayes; Margaret MacDonell; Jeffrey S. Gift (Environment Systems and Decisions, 2015)

Eating between the lines: functional feeding response of bonnetheads (Sphyrna tiburo) - Andrea M. Kroetz; Sean P. Powers (Environmental Biology of Fishes, 2015)

Evaluating the use of side-scan sonar for detecting freshwater mussel beds in turbid river environments - Jarrod Powers; Shannon K. Brewer; James M. Long; Thomas Campbell (Hydrobiologia, 2015)

Genetic diversity, population structure and phenotypic variation in European Salix viminalis L. (Salicaceae) - S. Berlin; S. O. Trybush; J. Fogelqvist; N. Gyllenstrand; H. R. Hallingbäck; I. Åhman; N-E. Nordh; I. Shield; S. J. Powers; M. Weih; U. Lagercrantz; A-C. Rönnberg-Wästljung; et al. (Tree Genetics & Genomes, 2014)

Metagenetic analysis of patterns of distribution and diversity of marine meiobenthic eukaryotes - Vera G. Fonseca; Gary R. Carvalho; Ben Nichols; Christopher Quince; Harriet F. Johnson; Simon P. Neill; John D. Lambshead; W. Kelley Thomas; Deborah M. Power; Simon Creer (Global Ecology and Biogeography, 2014)
Aim Meiofaunal communities that inhabit the marine benthos offer unique opportunities to simultaneously study the macroecology of numerous phyla that exhibit different life‐history strategies. Here, we ask: (1) if the macroecology of meiobenthic communities is explained mainly by dispersal constraints or by environmental conditions; and (2) if levels of meiofaunal diversity surpass existing estimates based on morphological taxonomy. Location UK and mainland European coast. Methods Next‐generation sequencing techniques ( NGS ; R oche 454 FLX platform) using 18S nuclear small subunit ribosomal DNA ( rDNA ) gene. Pyrosequences were analysed using A mplicon N oise followed by chimera removal using P erseus . Results Rarefaction curves revealed that sampling saturation was only reached at 15% of sites, highlighting that the bulk of meiofaunal diversity is yet to be discovered. Overall, 1353 OTU s were recovered and assigned to 23 different phyla. The majority of sampled sites had c. 60–70 unique operational taxonomic units ( OTU s) per site, indicating high levels of beta diversity. The environmental parameters that best explained community structure were seawater temperature, geographical distance and sediment size, but most of the variability ( R 2 = 70%–80%) remains unexplained. Main conclusions High percentages of endemic OTU s suggest that meiobenthic community composition is partly niche‐driven, as observed in larger organisms, but also shares macroecological features of microorganisms by showing high levels of cosmopolitanism (albeit on a much smaller scale). Meiobenthic communities exhibited patterns of isolation by distance as well as associations between niche, latitude and temperature, indicating that meiobenthic communities result from a combination of niche assembly and dispersal processes. Conversely, isolation‐by‐distance patterns were not identified in the featured protists, suggesting that animals and protists adhere to radically different macroecological processes, linked to life‐history strategies.

The Role of Nitrogen Deposition in Widespread Plant Community Change Across Semi-natural Habitats - Chris D. Field; Nancy B. Dise; Richard J. Payne; Andrea J. Britton; Bridget A. Emmett; Rachel C. Helliwell; Steve Hughes; Laurence Jones; Steven Lees; Jonathan R. Leake; Ian D. Leith; Gareth K. Phoenix; et al. (Ecosystems, 2014)

A new index for variations in the position of the South Pacific convergence zone 1910/11–2011/2012 - M. J. Salinger; Simon McGree; Florent Beucher; Scott B. Power; François Delage (Climate Dynamics, 2014)

Characterization of the DYX2 locus on chromosome 6p22 with reading disability, language impairment, and IQ - John D. Eicher; Natalie R. Powers; Laura L. Miller; Kathryn L. Mueller; Sara Mascheretti; Cecilia Marino; Erik G. Willcutt; John C. DeFries; Richard K. Olson; Shelley D. Smith; Bruce F. Pennington; J. Bruce Tomblin; et al. (Human Genetics, 2014)

Nonlinear precipitation response to El Niño and global warming in the Indo-Pacific - Christine T. Y. Chung; Scott B. Power; Julie M. Arblaster; Harun A. Rashid; Gregory L. Roff (Climate Dynamics, 2014)

Tsunami inundation in Napier, New Zealand, due to local earthquake sources - Stuart A. Fraser; William L. Power; Xiaoming Wang; Laura M. Wallace; Christof Mueller; David M. Johnston (Natural Hazards, 2014)

Proteomic Approach to Skin Regeneration in a Marine Teleost: Modulation by Oestradiol-17β - Antoni Ibarz; Patricia I. S. Pinto; Deborah M. Power (Marine Biotechnology, 2013)

Multivariate analysis of MLH1 c.1664T>C (p.Leu555Pro) mismatch repair gene variant demonstrates its pathogenicity - M. P. Farrell; D. J. Hughes; M. Drost; A. J. Wallace; R. J. Cummins; T. A. Fletcher; M. A. Meany; E. W. Kay; N. de Wind; D. G. Power; E. J. Andrews; A. J. Green; et al. (Familial Cancer, 2013)

Head Impact Exposure in Youth Football: Elementary School Ages 9–12 Years and the Effect of Practice Structure - Bryan R. Cobb; Jillian E. Urban; Elizabeth M. Davenport; Steven Rowson; Stefan M. Duma; Joseph A. Maldjian; Christopher T. Whitlow; Alexander K. Powers; Joel D. Stitzel (Annals of Biomedical Engineering, 2013)

Head Impact Exposure in Youth Football: High School Ages 14 to 18 Years and Cumulative Impact Analysis - Jillian E. Urban; Elizabeth M. Davenport; Adam J. Golman; Joseph A. Maldjian; Christopher T. Whitlow; Alexander K. Powers; Joel D. Stitzel (Annals of Biomedical Engineering, 2013)

A Probabilistic Tsunami Hazard Study of the Auckland Region, Part II: Inundation Modelling and Hazard Assessment - E. M. Lane; P. A. Gillibrand; X. Wang; W. Power (Pure and Applied Geophysics, 2013)

Dynamics of scale regeneration in seawater- and brackish water-acclimated sea bass, Dicentrarchus labrax - Pedro M. Guerreiro; Rita Costa; Deborah M. Power (Fish Physiology and Biochemistry, 2013)

Assessing the food web impacts of an anadromous A rctic charr introduction to a sub‐ A rctic watershed using stable isotopes - A. Murdoch; G. Klein; D. W. Doidge; M. Power (Fisheries Management and Ecology, 2013)
Anadromous A rctic charr, S alvelinus alpinus (L.), was introduced to a sub‐ A rctic river–lake system near the village of K ujjuuaq, N unavik, and the stable isotope values and diets of key resident fish species were used to assess changes in feeding patterns. Stable isotope values for most species did not differ significantly between the pre‐ and post‐introduction periods, with observed shifts being within the bounds of expected natural variation. Lake chub, C ouesius plumbeus ( A gassiz), were the single species to show a difference between study periods, with a small but significant increase in δ 15 N. No significant post‐introduction changes were seen in lake trout, S alvelinus namaycush ( W albaum), omnivory or in any of the assessed quantitative food web metrics. Gut contents of major fish species similarly showed significant temporal overlap between the pre‐ and post‐introduction periods, and there was no significant change in species' weight–length relationships. The minor ecological impact was interpreted in relation to the availability of open niches exploitable by ecological generalists such as A rctic charr. The explanation accords with the known habitat and feeding flexibility of A rctic charr and the ecological immaturity of sub‐ A rctic lakes known to have driven adaptive variation among A rctic charr. Findings suggest that anadromous A rctic charr may be introduced at moderate densities to other sub‐ A rctic watersheds without major negative food web consequences for other resident fish species.

Whole exome sequencing in dominant cataract identifies a new causative factor, CRYBA2, and a variety of novel alleles in known genes - Linda M. Reis; Rebecca C. Tyler; Sanaa Muheisen; Victor Raggio; Leonardo Salviati; Dennis P. Han; Deborah Costakos; Hagith Yonath; Sarah Hall; Patricia Power; Elena V. Semina (Human Genetics, 2013)

Investigation of the persistence of rafoxanide residues in bovine milk and fate during processing - C. Power; M. Danaher; R. Sayers; B. O’Brien; M. Whelan; A. Furey; K. Jordan (Food Additives & Contaminants: Part A, 2013)

Investigation of the persistence of triclabendazole residues in bovine milk following lactating-cow and dry-cow treatments - C. Power; M. Whelan; M. Danaher; Y. Bloemhoff; R. Sayers; B. O’Brien; A. Furey; K. Jordan (Food Additives & Contaminants: Part A, 2013)

The effects of visual training on multisensory temporal processing - Ryan A. Stevenson; Magdalena M. Wilson; Albert R. Powers; Mark T. Wallace (Experimental Brain Research, 2013)

Ontogenetic shifts in morphology and resource use of cisco Coregonus artedi - A. M. Muir; P. Vecsei; T. C. Pratt; C. C. Krueger; M. Power; J. D. Reist (Journal of Fish Biology, 2013)
Two previously described lacustrine cisco Coregonus spp. morphs [ i.e . a small ( L F ), low‐gillraker (≤44) morph and a large (≥300 mm L F ), high‐gillraker (≥45) morph] from Great Slave Lake, NT , Canada, were found to be synonymous with cisco Coregonus artedi. Geometric body shape did not differ between the two size classes nor could they be differentiated by 24 size‐corrected linear measurements, indicating that the two groups had similar phenotypes. Strong, positive correlations between all linear characters and geometric centroid size (a composite variable of fish body length, mass and age) suggested that body morphology changed with age as fish grew. Total gillraker number ( N GR ) increased with L F according to: N GR = 36·3 + 0·034 L F . Differences in gillraker number and phenotype with age and size were explained by shifts in habitat and trophic resource use. Relative abundance within 0–30, 30–60, 60–90 and >90 m depth strata differed between size classes suggesting that morphology changed when fish shifted their habitat as they grew older. Large C. artedi had lower δ 13 C and slightly higher δ 15 N, indicating greater reliance on pelagic prey resources ( i.e . more or larger zooplankton, such as Mysis spp.), compared to small C. artedi , which relied slightly more on benthic prey. Gillraker shape and number have always been used as key diagnostic characters in coregonine taxonomy; based on the findings presented here, ontogenetic shifts should be accounted for in resulting classifications.

Thyroid disruption in the lizard Podarcis bocagei exposed to a mixture of herbicides: a field study - Rita C. Bicho; Maria José Amaral; Augusto M. R. Faustino; Deborah M. Power; Alexandra Rêma; Miguel A. Carretero; Amadeu M. V. M. Soares; Reinier M. Mann (Ecotoxicology, 2013)

Effects of an exercise and hypocaloric healthy eating program on biomarkers associated with long-term prognosis after early-stage breast cancer: a randomized controlled trial - E. Scott; A. J. Daley; H. Doll; N. Woodroofe; R. E. Coleman; N. Mutrie; H. Crank; H. J. Powers; J. M. Saxton (Cancer Causes & Control, 2013)

Structural and biological control of the Cenozoic epithermal uranium concentrations from the Sierra Peña Blanca, Mexico - Samuel Angiboust; Mostafa Fayek; Ian M. Power; Alfredo Camacho; Georges Calas; Gordon Southam (Mineralium Deposita, 2012)

Water absorption and bicarbonate secretion in the intestine of the sea bream are regulated by transmembrane and soluble adenylyl cyclase stimulation - Edison S. M. Carvalho; Sílvia F. Gregório; Deborah M. Power; Adelino V. M. Canário; Juan Fuentes (Journal of Comparative Physiology B, 2012)

Current evidence for human yersiniosis in Ireland - T. Ringwood; B. P. Murphy; N. Drummond; J. F. Buckley; A. P. Coveney; H. P. Redmond; J. P. Power; S. Fanning; M. B. Prentice (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Spring climate and summer otolith growth in juvenile Arctic charr, Salvelinus alpinus - J. A. Godiksen; R. Borgstrøm; J. B. Dempson; J. Kohler; H. Nordeng; M. Power; A. Stien; M.-A. Svenning (Environmental Biology of Fishes, 2012)

Molecular and cellular changes in skin and muscle during metamorphosis of Atlantic halibut (Hippoglossus hippoglossus) are accompanied by changes in deiodinases expression - M. A. Campinho; M. Galay-Burgos; N. Silva; R. A. Costa; R. N. Alves; G. E. Sweeney; D. M. Power (Cell and Tissue Research, 2012)

Global major histocompatibility Class II β (mh‐IIβ) ‐polymorphism in Arctic charr Salvelinus alpinus - P. Conejeros; M. Power; S. Alekseyev; B. Dixon (Journal of Fish Biology, 2012)
This study explored the use of the gene encoding the β subunit of the major histocompatibility (MH) receptor as a population marker in Arctic charr Salvelinus alpinus . The use of this polymorphic marker allowed differentiation of the S. alpinus lineages previously defined using mitochondrial DNA (mtDNA) but also allowed differentiation between the populations studied within those lineages. The majority of the variation observed here occurred prior to the last glaciation event. Nevertheless, all S. alpinus populations were differentiated using both MH Class II β ( mh‐IIβ ) sequences and allelic frequencies. The fact that all the populations studied presented high rates of non‐synonymous: synonymous substitutions and high levels of interpopulation variation, suggested mh‐IIβ as an ideal marker to assess differentiation among S. alpinus populations in ways that may represent divergence both by genetic drift and natural adaptation to the local environment.

Engineering gibberellin metabolism in Solanum nigrum L. by ectopic expression of gibberellin oxidase genes - A. Bhattacharya; D. A. Ward; P. Hedden; A. L. Phillips; J. B. Power; M. R. Davey (Plant Cell Reports, 2012)

Nutrient Retention and the Problem of Hydrologic Disconnection in Streams and Wetlands - Stephen M. Powers; Robert A. Johnson; Emily H. Stanley (Ecosystems, 2012)

Impacts of atmospheric nitrogen deposition: responses of multiple plant and soil parameters across contrasting ecosystems in long‐term field experiments - Gareth K. Phoenix; Bridget A. Emmett; Andrea J. Britton; Simon J. M. Caporn; Nancy B. Dise; Rachel Helliwell; Laurence Jones; Jonathan R. Leake; Ian D. Leith; Lucy J. Sheppard; Alwyn Sowerby; Michael G. Pilkington; et al. (Global Change Biology, 2012)
Atmospheric nitrogen ( N ) deposition is a global and increasing threat to biodiversity and ecosystem function. Much of our current understanding of N deposition impacts comes from field manipulation studies, although interpretation may need caution where simulations of N deposition (in terms of dose, application rate and N form) have limited realism. Here, we review responses to simulated N deposition from the UKREATE network, a group of nine experimental sites across the UK in a diversity of heathland, grassland, bog and dune ecosystems which include studies with a high level of realism and where many are also the longest running globally on their ecosystem type. Clear responses were seen across the sites with the greatest sensitivity shown in cover and species richness of bryophytes and lichens. Productivity was also increased at sites where N was the limiting nutrient, while flowering also showed high sensitivity, with increases and declines seen in dominant shrub and forb species, respectively. Critically, these parameters were responsive to some of the lowest additional loadings of N (7.7–10 kg ha −1 yr −1 ) showing potential for impacts by deposition rates seen in even remote and ‘unpolluted’ regions of E urope. Other parameters were less sensitive, but nevertheless showed response to higher doses. These included increases in soil % N and ‘plant available’ KCl extractable N , N cycling rates and acid–base status. Furthermore, an analysis of accumulated dose that quantified response against the total N input over time suggested that N impacts can ‘build up’ within an ecosystem such that even relatively low N deposition rates can result in ecological responses if continued for long enough. Given the responses have important implications for ecosystem structure, function, and recovery from N loading, the clear evidence for impacts at relatively low N deposition rates across a wide range of habitats is of considerable concern.

Source of Selenium Supplementation Influences Testis Selenium Content and Gene Expression Profiles in Single Comb White Leghorn Roosters - Kristen M. Brennan; James L. Pierce; Austin H. Cantor; Anthony J. Pescatore; Rijin Xiao; Ronan F. Power (Biological Trace Element Research, 2012)

Non-cancer endpoints in BRCA1/2 carriers after risk-reducing salpingo-oophorectomy - J. V. Cohen; L. Chiel; L. Boghossian; M. Jones; J. E. Stopfer; J. Powers; T. R. Rebbeck; K. L. Nathanson; S. M. Domchek (Familial Cancer, 2012)

Legume seeders of the Cape Floristic Region inhabit more fertile soils than congeneric resprouters—sometimes - Simon C. Power; Michael D. Cramer; G. Anthony Verboom; Samson B. M. Chimphango (Plant Ecology, 2011)

The July 15, 2009 Fiordland, New Zealand Tsunami: Real-Time Assessment - B. Uslu; W. Power; D. Greenslade; M. Eblé; V. Titov (Pure and Applied Geophysics, 2011)

Physiological tolerance predicts species composition at different scales in a barnacle guild - Anne Marie Power; Karen McCrann; David McGrath; Ruth M. O’ Riordan; Christina Simkanin; Alan A. Myers (Marine Biology, 2011)

Red snapper management in the Gulf of Mexico: science- or faith-based? - J. H. Cowan; C. B. Grimes; W. F. Patterson; C. J. Walters; A. C. Jones; W. J. Lindberg; D. J. Sheehy; W. E. Pine; J. E. Powers; M. D. Campbell; K. C. Lindeman; S. L. Diamond; et al. (Reviews in Fish Biology and Fisheries, 2011)

Occurrence of ghrelin-producing cells, the ghrelin receptor and Na+,K+-ATPase in tissues of Atlantic halibut (Hippoglossus hippoglossus) during early development - Ingibjörg Eir Einarsdóttir; Deborah M. Power; Elisabeth Jönsson; Björn Thrandur Björnsson (Cell and Tissue Research, 2011)

Stable isotope-based determinations of the average temperatures experienced by young-of-the-year Svalbard Arctic charr (Salvelinus alpinus (L.)) - J. A. Godiksen; M.-A. Svenning; R. N. Sinnatamby; J. B. Dempson; R. Borgstrøm; M. Power (Polar Biology, 2011)

Earth stewardship: a strategy for social–ecological transformation to reverse planetary degradation - F. Stuart Chapin; Steward T. A. Pickett; Mary E. Power; Robert B. Jackson; David M. Carter; Clifford Duke (Journal of Environmental Studies and Sciences, 2011)

Cellular morphology and markers of cartilage and bone in the marine teleost Sparus auratus - M. Dulce Estêvão; Nadia Silva; Begona Redruello; Rita Costa; Silvia Gregório; Adelino V. M. Canário; Deborah M. Power (Cell and Tissue Research, 2011)

Expression of the myosin light chains 1, 2 and 3 in the muscle of blackspot seabream (Pagellus bogaraveo, Brunnich), during development - P. Silva; D. M. Power; L. M. P. Valente; N. Silva; R. A. F. Monteiro; E. Rocha (Fish Physiology and Biochemistry, 2010)

Maternal care and infant development in Callimico goeldii and Callithrix jacchus - Abigail C. Ross; Leila M. Porter; Michael L. Power; Vince Sodaro (Primates, 2010)

Epidemiology of non-multiresistant methicillin-resistant Staphylococcus aureus infection in Queensland, Australia: associations with indigenous populations and Panton–Valentine leukocidin - G. R. Nimmo; J. M. Schooneveldt; J. L. Sutherland; S. Power; D. Olesen; C. Selvey; F. Beard; M. Jones; D. L. Paterson (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Relative importance of human activities and climate driving common murre population trends in the Northwest Atlantic - Paul M. Regular; Gregory J. Robertson; William A. Montevecchi; Fyzee Shuhood; Tony Power; Douglas Ballam; John F. Piatt (Polar Biology, 2010)

Does phosphate acquisition constrain legume persistence in the fynbos of the Cape Floristic Region? - Simon C. Power; Michael D. Cramer; G. Anthony Verboom; Samson B. M. Chimphango (Plant and Soil, 2010)

Latitudinal variation in growth among Arctic charr in eastern North America: evidence for countergradient variation? - Louise Chavarie; J. Brian Dempson; C. J. Schwarz; J. D. Reist; G. Power; M. Power (Hydrobiologia, 2010)

High frequency direct plant regeneration from leaf and petals of Cape Primrose (Streptocarpus) - A. Chaudhury; J. B. Power; M. R. Davey (Journal of Crop Science and Biotechnology, 2010)

Tyrosine hydroxylase, chromogranin A, and steroidogenic acute regulator as markers for successful separation of human adrenal medulla - Stephanie M. J. Fliedner; Jan Breza; Richard Kvetnansky; James F. Powers; Arthur S. Tischler; Robert Wesley; Maria Merino; Hendrik Lehnert; Karel Pacak (Cell and Tissue Research, 2010)

Ultrasequencing of the meiofaunal biosphere: practice, pitfalls and promises - S. CREER; V. G. FONSECA; D. L. PORAZINSKA; R. M. GIBLIN‐DAVIS; W. SUNG; D. M. POWER; M. PACKER; G. R. CARVALHO; M. L. BLAXTER; P. J. D. LAMBSHEAD; W. K. THOMAS (Molecular Ecology, 2010)
Biodiversity assessment is the key to understanding the relationship between biodiversity and ecosystem functioning, but there is a well‐acknowledged biodiversity identification gap related to eukaryotic meiofaunal organisms. Meiofaunal identification is confounded by the small size of taxa, morphological convergence and intraspecific variation. However, the most important restricting factor in meiofaunal ecological research is the mismatch between diversity and the number of taxonomists that are able to simultaneously identify and catalogue meiofaunal diversity. Accordingly, a molecular operational taxonomic unit (MOTU)‐based approach has been advocated for en mass meiofaunal biodiversity assessment, but it has been restricted by the lack of throughput afforded by chain termination sequencing. Contemporary pyrosequencing offers a solution to this problem in the form of environmental metagenetic analyses, but this represents a novel field of biodiversity assessment. Here, we provide an overview of meiofaunal metagenetic analyses, ranging from sample preservation and DNA extraction to PCR, sequencing and the bioinformatic interrogation of multiple, independent samples using 454 Roche sequencing platforms. We report two examples of environmental metagenetic nuclear small subunit 18S (nSSU) analyses of marine and tropical rainforest habitats and provide critical appraisals of the level of putative recombinant DNA molecules (chimeras) in metagenetic data sets. Following stringent quality control measures, environmental metagenetic analyses achieve MOTU formation across the eukaryote domain of life at a fraction of the time and cost of traditional approaches. The effectiveness of Roche 454 sequencing brings substantial advantages to studies aiming to elucidate the molecular genetic richness of not only meiofaunal, but also all complex eukaryotic communities.

Climate‐related, decadal‐scale assemblage changes of seagrass‐associated fishes in the northern Gulf of Mexico - F. JOEL FODRIE; KENNETH L. HECK; SEAN P. POWERS; WILLIAM M. GRAHAM; KELLY L. ROBINSON (Global Change Biology, 2010)
Global temperatures are rising, and are expected to produce a poleward shift in the distribution of many organisms. We quantified changes in fish assemblages within seagrass meadows of the northern Gulf of Mexico (GOM) between the 1970s and 2006–2007, and observed changes consistent with this forecast. During 2006–2007 we sampled seagrass meadows using the same gears and methods previously employed by R. J. Livingston in coastal waters of northwest Florida throughout the 1970s. Comparisons between datasets revealed numerous additions to the fish fauna during 2006–2007 that were completely absent in the 1970s, including: Lutjanus synagris (lane snapper), Epinephelus morio (red grouper), Chaetodon ocellatus (spotfin butterflyfish), Mycteroperca sp (grouper, non gag), Centropristis philadelphica (rock sea bass), Fistularia tabacaria (bluespotted cornetfish), Ocyurus chrysurus (yellowtail snapper), Thalassoma bifasciatum (bluehead wrasse), Abudefduf saxatilis (sergeant major), Acanthuridae spp. (surgeonfishes) and Sparisoma viride (stoplight parrotfish). Several other species showed large increases in abundance during the interval between 1979 and 2006, including Mycteroperca microlepis (gag grouper, up ∼200 ×), Lutjanus griseus (gray snapper, up ∼105 ×), and Nicholsina usta (emerald parrotfish, up ∼22 ×). All of these are tropical or subtropical species that now make up a greater percentage of seagrass‐associated fish assemblages in the northern GOM than in the past. Additionally, we observed regional increases in air and sea surface temperatures (> 3 °C) during the ∼30 years that separate Livingston's samples and ours that correlate with northern shifts in the distribution of warm‐water fishes. Documenting these range shifts is a critical first step in investigating the consequences of global warming for endemic marine communities and fishery production in the northern GOM.

A Control Volume Radial Basis Function Techniques for the Numerical Simulation of Saturated Flows in Semi-confined Aquifer - P. Orsini; H. Power; M. Lees; H. Morvan (Transport in Porous Media, 2009)

Murres, capelin and ocean climate: inter-annual associations across a decadal shift - P. M. Regular; F. Shuhood; T. Power; W. A. Montevecchi; G. J. Robertson; D. Ballam; J. F. Piatt; B. Nakashima (Environmental Monitoring and Assessment, 2009)

Ungulate Carcasses Perforate Ecological Filters and Create Biogeochemical Hotspots in Forest Herbaceous Layers Allowing Trees a Competitive Advantage - Joseph K. Bump; Christopher R. Webster; John A. Vucetich; Rolf O. Peterson; Joshua M. Shields; Matthew D. Powers (Ecosystems, 2009)

Phylogeography and sympatric differentiation of the Arctic charr Salvelinus alpinus (L.) complex in Siberia as revealed by mtDNA sequence analysis - S. S. Alekseyev; R. Bajno; N. V. Gordeeva; J. D. Reist; M. Power; A. F. Kirillov; V. P. Samusenok; A. N. Matveev (Journal of Fish Biology, 2009)
Sequence variation in the mtDNA control region of Arctic charr Salvelinus alpinus and Dolly Varden Salvelinus malma from 56 Siberian and North American populations was analysed to assess their phylogeographic relationships and the origins of sympatric forms. Phylogenetic trees confirm the integrity of phylogroups reported in previous mtDNA studies except that the Siberian group does not separate as a single cluster. Haplotype network analysis indicates the proximity of Siberian and Atlantic haplotypes. These are considered as one Eurasian group represented by the Atlantic, east Siberian (interior Siberia including Transbaikalia, Taimyr) and Eurosiberian (Finland, Spitsbergen, Taimyr) sub‐groups. Salvelinus alpinus with presumably introgressed Bering group (malma) haplotypes were found along eastern Siberian coasts up to the Olenek Bay and the Lena Delta region, where they overlap with the Eurasian group and in the easternmost interior region. It is proposed that Siberia was colonized by S. alpinus in two stages: from the west by the Eurasian group and later from the east by the Bering group. The high diversity of Eurasian group haplotypes in Siberia indicates its earlier colonization by S. alpinus as compared with the European Alps. This colonization was rapid, proceeded from a diverse gene pool, and was followed by differential survival of ancestral mtDNA lineages in different basins and regions, and local mutational events in isolated populations. The results presented here support a northern origin of Transbaikalian S. alpinus , the dispersion of S. alpinus to the Lake Baikal Basin from the Lena Basin, segregation of S. alpinus between Lena tributaries and their restricted migration over the divides between sub‐basins. These results also support sympatric origin of intralacustrine forms of S. alpinus .

Cell Death Discrimination with Raman Spectroscopy and Support Vector Machines - Georgios Pyrgiotakis; O. Erhun Kundakcioglu; Kathryn Finton; Panos M. Pardalos; Kevin Powers; Brij M. Moudgil (Annals of Biomedical Engineering, 2009)

Absence of Ross River virus amongst Common brushtail possums (Trichosurus vulpecula) from metropolitan Sydney, Australia - Nichola J. Hill; Michelle L. Power; Elizabeth M. Deane (European Journal of Wildlife Research, 2009)

Tropical nematode diversity: vertical stratification of nematode communities in a Costa Rican humid lowland rainforest - T. O. POWERS; D. A. NEHER; P. MULLIN; A. ESQUIVEL; R. M. GIBLIN‐DAVIS; N. KANZAKI; S. P. STOCK; M. M. MORA; L. URIBE‐LORIO (Molecular Ecology, 2009)
Comparisons of nematode communities among ecosystems have indicated that, unlike many organisms, nematode communities have less diversity in the tropics than in temperate ecosystems. There are, however, few studies of tropical nematode diversity on which to base conclusions of global patterns of diversity. This study reports an attempt to estimate nematode diversity in the lowland tropical rainforest of La Selva Biological Research Station in Costa Rica. We suggest one reason that previous estimates of tropical nematode diversity were low is because habitats above the mineral soil are seldom sampled. As much as 62% of the overall genetic diversity, measured by an 18S ribosomal barcode, existed in litter and understorey habitats and not in soil. A maximum‐likelihood tree of barcodes from 360 individual nematodes indicated most major terrestrial nematode lineages were represented in the samples. Estimated ‘species’ richness ranged from 464 to 502 within the four 40 × 40 m plots. Directed sampling of insects and their associated nematodes produced a second set of barcodes that were not recovered by habitat sampling, yet may constitute a major class of tropical nematode diversity. While the generation of novel nematode barcodes proved relatively easy, their identity remains obscure due to deficiencies in existing taxonomic databases. Specimens of Criconematina, a monophyletic group of soil‐dwelling plant‐parasitic nematodes were examined in detail to assess the steps necessary for associating barcodes with nominal species. Our results highlight the difficulties associated with studying poorly understood organisms in an understudied ecosystem using a destructive (i.e. barcode) sampling method.

Dual lentivirus infection potentiates neuroinflammation and neurodegeneration: viral copassage enhances neurovirulence - Amir Afkhami-Goli; Amir Afkhami-Goli; Shu-Hong Liu; Amir Afkhami-Goli; Shu-Hong Liu; Yu Zhu; Joseph M Antony; Hosseinali Arab; Christopher Power (Journal of NeuroVirology, 2009)

Smoking Sleuths: A pilot tobacco prevention elective for medical school students - Catherine A. Powers; Carey C. Thomson; Ilana Feuerstein; Megan Cross; Erin M. Powers; Marianne Prout; Alan C. Geller (Journal of Cancer Education, 2008)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Involvement of growth hormone-insulin-like growth factor I system in cranial remodeling during halibut metamorphosis as indicated by tissue- and stage-specific receptor gene expression and the presence of growth hormone receptor protein - Jon Hildahl; Deborah M. Power; Björn Thrandur Björnsson; Ingibjörg Eir Einarsdóttir (Cell and Tissue Research, 2008)

Over-expression of a gibberellin 2-oxidase gene from Phaseolus coccineus L. enhances gibberellin inactivation and induces dwarfism in Solanum species - C. Dijkstra; E. Adams; A. Bhattacharya; A. F. Page; P. Anthony; S. Kourmpetli; J. B. Power; K. C. Lowe; S. G. Thomas; P. Hedden; A. L. Phillips; M. R. Davey (Plant Cell Reports, 2008)

Basic skills for working with smokers: A pilot test of an online course for medical students - Mary jo White; Beth M. Ewy; Judith Ockene; Scott Mcintosh; Jane Zapka; Catherine A. Powers; Alan Geller (Journal of Cancer Education, 2007)

Closed-tube DNA extraction using a thermostable proteinase is highly sensitive, capable of single parasite detection - B. C. Ferrari; M. L. Power; P. L. Bergquist (Biotechnology Letters, 2007)

Occurrence of Cryptosporidium parvum and Bacterial Pathogens in Faecal Material in the Red Fox (Vulpes vulpes) Population - Y. Nagano; M. B. Finn; C. J. Lowery; T. Murphy; J. Moriarty; E. Power; D. Toolan; A. O’Loughlin; M. Watabe; K. A. McCorry; E. Crothers; J. S. G. Dooley; et al. (Veterinary Research Communications, 2007)

An assessment of de‐calcification procedures for δ 13 C and δ 15 N analysis of yellow perch, walleye and Atlantic salmon scales - R. N. Sinnatamby; J. E. Bowman; J. B. Dempson; M. Power (Journal of Fish Biology, 2007)
The scales of three species of fishes, yellow perch Perca flavescens , walleye Sander vitreus and Atlantic salmon Salmo salar , were acidified and the isotopic signatures were compared to non‐acidified scales from the same fishes. No significant acidification effects on either carbon or nitrogen isotope signatures were found. Results contrast with earlier literature findings noting significant acidification effects and suggest acidification tests be undertaken before scales are used for temporal reconstruction of fish food web positions.

Molecular, cellular and histological changes in skin from a larval to an adult phenotype during bony fish metamorphosis - Marco A. Campinho; Nádia Silva; Glen E. Sweeney; Deborah M. Power (Cell and Tissue Research, 2006)

NeuroAIDS, Drug Abuse, and Inflammation: Building Collaborative Research Activities - Joan W. Berman; Monica J. Carson; Linda Chang; Brian M. Cox; Howard S. Fox; R. Gilberto Gonzalez; Glen R. Hanson; Kurt F. Hauser; Wen-Zhe Ho; Jau-Shyong Hong; Eugene O. Major; William F. Maragos; et al. (Journal of Neuroimmune Pharmacology, 2006)

The effects of preservation on fish tissue stable isotope signatures - B. Kelly; J. B. Dempson; M. Power (Journal of Fish Biology, 2006)
The effects of formalin and ethanol preservation on the δ 13 C and δ 15 N isotope signatures of Arctic charr Salvelinus alpinus muscle tissue were examined. The lipid content of the tissue samples studied ranged from 3·6 to 6·1% and was not correlated with the magnitude of observed isotopic shifts in preserved samples. Ethanol and formalin significantly depleted and enriched, respectively, the δ 13 C isotope signatures of preserved tissues when compared to control samples. Ethanol did not significantly enrich δ 15 N signatures in comparison to controls, whereas formalin did. A meta‐analysis of multiple species effects further demonstrated significant preservation effects in fish tissue. Statistical analysis of data obtained by correcting preserved tissue isotope signatures with literature, bootstrapped or meta‐analysis derived correction factors demonstrated significant differences between corrected and control sample isotope signatures or failure to produce a unity slope when the data sets were regressed against one another. Species‐specific, bootstrapped linear correction models resulted in no such errors. Results suggest that species‐specific correction methods should be used for fishes because of the known wide variation in fish tissue lipid content and composition. Accordingly, the use of pilot studies will be required to develop correction factors that properly adjust for preservation effects when interpreting temporal patterns in historic analyses of food webs.

Comparative field performance over 3 years and two sites of transgenic wheat lines expressing HMW subunit transgenes - Peter R. Shewry; Stephen Powers; J. Michael Field; Roger J. Fido; Huw D. Jones; Gillian M. Arnold; Jevon West; Paul A. Lazzeri; Pilar Barcelo; Francisco Barro; Arthur S. Tatham; Frank Bekes; et al. (Theoretical and Applied Genetics, 2006)

Biotic interactions and plant invasions - Charles E. Mitchell; Anurag A. Agrawal; James D. Bever; Gregory S. Gilbert; Ruth A. Hufbauer; John N. Klironomos; John L. Maron; William F. Morris; Ingrid M. Parker; Alison G. Power; Eric W. Seabloom; Mark E. Torchin; et al. (Ecology Letters, 2006)
Introduced plant populations lose interactions with enemies, mutualists and competitors from their native ranges, and gain interactions with new species, under new abiotic conditions. From a biogeographical perspective, differences in the assemblage of interacting species, as well as in abiotic conditions, may explain the demographic success of the introduced plant populations relative to conspecifics in their native range. Within invaded communities, the new interactions and conditions experienced by the invader may influence both its demographic success and its effects on native biodiversity. Here, we examine indirect effects involving enemies, mutualists and competitors of introduced plants, and effects of abiotic conditions on biotic interactions. We then synthesize ideas building on Darwin's idea that the kinds of new interactions gained by an introduced population will depend on its relatedness to native populations. This yields a heuristic framework to explain how biotic interactions and abiotic conditions influence invader success. We conclude that species introductions generally alter plants’ interactions with enemies, mutualists and competitors, and that there is increasing evidence that these altered interactions jointly influence the success of introduced populations.

Brown trout spawning habitat selection preferences and redd characteristics in the Credit River, Ontario - M. P. Zimmer; M. Power (Journal of Fish Biology, 2006)
Brown trout Salmo trutta redds in the Credit River, Ontario, were enumerated and assessed for physical, location and cover feature characteristics during the 2002 spawning season. Hydraulic habitats were classified on the basis of channel morphology and availability recorded. Combined use and availability data were used to assess habitat selection preferences and test for significant differences. Significant preferences for upstream pool and riffle habitat were found, but all available habitat types were used to some degree. Non‐preferred habitat redds were significantly larger than those located in preferred habitats and more likely to be found in association with woody debris cover. Larger redds were interpreted as indicative of larger fish. The use of non‐preferred downstream habitats by larger fish was further interpreted in the context of overwinter habitat requirements to reflect possible trade‐offs between reproductive and adult over‐winter survival requirements resulting in the selection of habitat for multiple life‐history functions. Results suggest that redd density alone should not be used to infer critical autumn habitat requirements for brown trout.

Ligand binding and signalling pathways of PTH receptors in sea bream (Sparus auratus) enterocytes - J. Rotllant; P. M. Guerreiro; B. Redruello; H. Fernandes; L. Apolónia; L. Anjos; A. V. M. Canario; D. M. Power (Cell and Tissue Research, 2006)

Latitudinal variation in fecundity among Arctic charr populations in eastern North America - M. Power; J. B. Dempson; J. D. Reist; C. J. Schwarz; G. Power (Journal of Fish Biology, 2005)
Variation in fecundity was examined from 32 populations of Arctic charr Salvelinus alpinus in eastern North America covering a range of 37° latitude and extending from Maine, U.S.A., to northern Ellesmere Island in the Canadian Arctic. Populations were classed as dwarf, normal or anadromous and covered a suite of different habitat and climatic regimes. Fecundity varied with fork length ( L F ), with L F adjusted fecundity differing significantly among populations within each of the morphotypes implying that fecundity was a continuously responsive trait influenced by local environmental factors. Latitudinal variation in fecundity was also evident among morphotypes when the simultaneous effects of both latitude and L F were controlled. There was a significant trade‐off between fecundity and egg size in two of five populations of anadromous Arctic charr, but no evidence in limited data from either normal or dwarf populations. In contrast with some other studies of fecundity in salmonids, there was no evidence for a latitudinal cline in egg size.

Phenotypic and genotypic characterization of encapsulated Escherichia coli isolated from blooms in two Australian lakes - Michelle L. Power; Jane Littlefield‐Wyer; David M. Gordon; Duncan A. Veal; Martin B. Slade (Environmental Microbiology, 2005)
Summary Escherichia coli has long been used as an indicator organism for water quality assessment. Recently there has been an accumulation of evidence that suggests some strains of this organism are able to proliferate in the environment, a characteristic that would detract from its utility as an indicator of faecal pollution. Phenotypic and genotypic characterization of E. coli isolated from blooms in two Australian lakes, separated by a distance of approximately 200 km, identified that the blooms were dominated by three E. coli strains. A major phenotypic similarity among the three bloom strains was the presence of a group 1 capsule. Genetic characterization of a conserved region of the cps gene cluster, which encodes group 1 capsules, identified a high degree of genetic variation within the bloom isolates. This differs from previously described encapsulated E. coli strains which are highly conserved at the cps locus. The phenotypic or genotypic profiles of the bloom strains were not identified in 435 E. coli strains isolated from vertebrates. The occurrence of these encapsulated strains suggests that some E. coli have evolved a free‐living lifestyle and do not require a host in order to proliferate. The presence of the same three strains in bloom events in different geographical regions of a temperate climate, and at different times, indicates that free‐living E. coli strains are able to persist in these water reservoirs. This study provides further evidence of circumstances where caution is required in using E. coli as an indicator organism for water quality.

Solar radiation climate change over southern Africa and an assessment of the radiative impact of volcanic eruptions - H. C. Power; D. M. Mills (International Journal of Climatology, 2005)

Extractable bone morphogenetic protein and correlation with induced new bone formation in an in vivo assay in the athymic mouse model - Sittisak Honsawek; Ralph M. Powers; Lloyd Wolfinbarger (Cell and Tissue Banking, 2005)

Temperature sensitivity of skeletal ontogeny in Oreochromis mossambicus - M. A. Campinho; K. A. Moutou; D. M. Power (Journal of Fish Biology, 2004)
Sensitivity of skeletal ontogenesis to temperature was assessed in Mozambican tilapia Oreochromis mossambicus and culture temperature manipulations (22, 27 and 32° C) were used to establish if age or length gave the most suitable metric for standardization. Oreochromis mossambicus larval growth was composed of two growth stanzas: an initial period of rapid growth, followed by a slower growth phase. Irrespective of culture temperature chondrogenesis occurred during the first rapid growth phase and ossification was initiated during the second slower growth phase. The sequence of events and rate at which ossification occurred was much more sensitive to temperature than chondrogenesis. Cumulative counts provide a useful developmental index for skeletal ontogenesis; overall, age (effective days‐degrees) gave the best estimation of developmental status during chondrogenesis and the initiation of ossification, although standard length (as log 10 L S ) was a better metric for completion of ossification. The timing of development of functionally important structures, such as Meckel's cartilage, the branchial arches, the centra and the cleithrum important for breathing, feeding and swimming, was well conserved at all temperatures and may be a good index of teleost developmental stages.

Effects of land use history on hurricane damage and recovery in a neotropical forest - M. Uriarte; L.W. Rivera; J.K. Zimmerman; T.M. Aide; A.G. Power; A.S. Flecker (Plant Ecology, 2004)

Estimating soil carbon fluxes following land‐cover change: a test of some critical assumptions for a region in Costa Rica - Jennifer S. Powers; Jane M. Read; Julie S. Denslow; Sandra M. Guzman (Global Change Biology, 2004)
Changes in soil carbon storage that accompany land‐cover change may have significant effects on the global carbon cycle. The objective of this work was to examine how assumptions about preconversion soil C storage and the effects of land‐cover change influence estimates of regional soil C storage. We applied three models of land‐cover change effects to two maps of preconversion soil C in a 140 000 ha area of northeastern Costa Rica. One preconversion soil C map was generated using values assigned to tropical wet forest from the literature, the second used values obtained from extensive field sampling. The first model of land‐cover change effects used values that are typically applied in global assessments, the second and third models used field data but differed in how the data were aggregated (one was based on land‐cover transitions and one was based on terrain attributes). Changes in regional soil C storage were estimated for each combination of model and preconversion soil C for three time periods defined by geo‐referenced land‐cover maps. The estimated regional soil C under forest vegetation (to 0.3 m) was higher in the map based on field data (10.03 Tg C) than in the map based on literature data (8.90 Tg C), although the range of values derived from propagating estimation errors was large (7.67–12.40 Tg C). Regional soil C storage declined through time due to forest clearing for pasture and crops. Estimated CO 2 fluxes depended more on the model of land‐cover change effects than on preconversion soil C. Cumulative soil C losses (1950–1996) under the literature model of land‐cover effects exceeded estimates based on field data by factors of 3.8–8.0. In order to better constrain regional and global‐scale assessments of carbon fluxes from soils in the tropics, future research should focus on methods for extrapolating regional‐scale constraints on soil C dynamics to larger spatial and temporal scales.

Biological effects-based sediment quality in ecological risk assessment for European waters - Pieter J. den Besten; Eric de Deckere; Marc P. Babut; Beth Power; T. Angel DelValls; Christina Zago; Amy M. P. Oen; Susanne Heise (Journal of Soils and Sediments, 2003)

Shifting Priorities at the Department of Energy's Bomb Factories: Protecting Human and Ecological Health - JOANNA BURGER; THOMAS M. LESCHINE; MICHAEL GREENBERG; JAMES R. KARR; MICHAEL GOCHFELD; CHARLES W. POWERS (Environmental Management, 2003)

A conceptual model of the Mount Spurr magmatic system from seismic and geochemical observations of the 1992 Crater Peak eruption sequence - Power J.; Jolly A.; Nye C.; Harbin M. (Bulletin of Volcanology, 2002)

Using stable isotopes to confirm the trophic ecology of Arctic charr morphotypes from Lake Hazen, Nunavut, Canada - K. R. R. A. Guiguer; J. D. Reist; M. Power; J. A. Babaluk (Journal of Fish Biology, 2002)
Stable isotopes of carbon and nitrogen were used to examine differences in the feeding ecology of sympatric morphotypes of Arctic charr Sahelinus alpinus from Lake Hazen, Ellesmere Island, in the Canadian High Arctic. Large and small morphotypes possessed significantly different carbon and nitrogen signatures with large‐form Arctic charr being more depleted in 13 C and more enriched in 15 N than the small‐form. Isotope and stomach content analyses yielded consistent results and indicated short‐ and long‐term reliance on fish as a food for large Arctic charr. Large‐form individuals predate on juveniles but do not predate on small‐form individuals ≥ 250 mm. The observed cannibalism by large‐form individuals, therefore, does not act to maintain the bimodal length‐frequency distribution in Lake Hazen. Bimodality is argued to arise for ecological reasons connected with differing habitat use by the morphotypes and the associated differences in resource consumption opportunities.

STOIC: a study of coupled model climatology and variability in tropical ocean regions - Davey M.; Huddleston M.; Sperber K.; Braconnot P.; Bryan F.; Chen D.; Colman R.; Cooper C.; Cubasch U.; Delecluse P.; DeWitt D.; Fairhead L.; et al. (Climate Dynamics, 2002)

Neurovirulence depends on virus input titer in brain in feline immunodeficiency virus infection: Evidence for activation of innate immunity and neuronal injury - J. B. Johnston; C Silva; T Hiebert; R Buist; M. R. Dawood; J Peeling; C Power (Journal of NeuroVirology, 2002)

Molecular systematics of Solanum section Lycopersicum (Lycopersicon) using the nuclear ITS rDNA region - J. A. Marshall; S. Knapp; M. R. Davey; J. B. Power; E. C. Cocking; M. D. Bennett; A. V. Cox (Theoretical and Applied Genetics, 2001)

ENSIP: the El Niño simulation intercomparison project - M. Latif; K. Sperber; J. Arblaster; P. Braconnot; D. Chen; A. Colman; U. Cubasch; C. Cooper; P. Delecluse; D. Dewitt; L. Fairhead; G. Flato; et al. (Climate Dynamics, 2001)

Variation in the Sizes of Chthamalid Barnacle Post‐Settlement Cyprids on European Shores - Ruth M. O'Riordan; Jane Delany; David McGrath; Alan A. Myers; Anne Marie Power; Neil F. Ramsay; Damaso Alvarez; Teresa Cruz; Federica G. Pannacciulli; Pedro Range; Giulio Relini (Marine Ecology, 2001)
As part of a wider study on the settlement and recruitment of Chthamalus spp. in Europe, this study investigated whether chthamalid cyprids can be separated by length on a European scale. Variation in cyprid length with latitude and temporal variation at selected localities were also examined. The lengths of cyprids collected between 1996 – 1999 on nine rocky shores in Europe are reported. Elminius modestus cyprids were found only at Roscoff, NW France and could be distinguished due to their carapace shape and length. They showed a unimodal length distribution, measuring between 450 and 625 µm, with no variation in length between the two sampling dates (1997 and 1998). Based on carapace shape and length, the remaining cyprids in the collections were identified as one of three chthamalid species, Chthamalus montagui, Chthamalus stellatus or Euraphia depressa. Bimodal length distributions of chthamalid cyprids were seen on some shores, while others had a single small‐sized modal group (representing C. montagui on Atlantic shores and/or E. depressa in the Mediterranean) separated from a few distinctly larger cyprids ( C. stellatus ). Metamorphs collected simultaneously with cyprid collections were identified as C. stellatus or C. montagui , except at Roscoff, where E. modestus were also found. In southern Portugal, where all metamorphs collected were C. montagui and adult C. montagui were the dominant barnacles, most cyprids measured between 350 and 550 µm long and this size distribution coincides with the distribution expected for C. montagui. Cyprids collected on these four more southerly Portuguese shores had the same modal length class (475 µm) and this remained constant between successive years at Luz and Albufeira, Algarve. The smallest (350 µm long) wild chthamalid cyprids found were from southern Portugal and Italy. In Spain, France and Ireland the smallest chthamalid cyprid was 425 µm long. The results from the present study support the hypothesis that on Atlantic shores cyprids of C. montagui can be separated from those of C. stellatus based on size, although there is some variation in cyprid length with latitude as well as temporal variation at selected localities.

Volatile Compounds from Salix spp. Varieties Differing in Susceptibility to Three Willow Beetle Species - L. Peacock; M. Lewis; S. Powers (Journal of Chemical Ecology, 2001)

Behavioural and physiological responses of infective juveniles of the entomopathogenic nematode Heterorhabditis to desiccation - Sean A. O'Leary; Austin P. Power; Colin M. Stack; Ann M. Burnell (BioControl, 2001)

A simple and rapid procedure to establish embryogenic cell suspensions as a source of protoplasts for efficient plant regeneration from two Chinese commercial rice cultivars - K. Tang; X. Sun; D. An; J. B. Power; E. C. Cocking; M. R. Davey (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

Genetic transformation of wheat: progress during the 1990s into the Millennium - Heidi M. Ingram; Nancy L. Livesey; J. Brian Power; Michael R. Davey (Acta Physiologiae Plantarum, 2001)

Comparison of sensory differences of stored Russet Burbank potatoes treated with CIPC and alternative sprout inhibitors - Terri D. Boylston; Joseph R. Powers; Karen M. Weiler; Jian Yang (American Journal of Potato Research, 2001)

Osteologic development of the viscerocranial skeleton in sea bream: alternative ossification strategies in teleost fish - M. Faustino; D. M. Power (Journal of Fish Biology, 2001)
The ontogeny of the viscerocranial skeleton of sea bream Sparus aurata larvae was studied from 1 to 90 days post‐hatching. In the smallest specimens analysed at 2·7 mm L N no cephalic elements were present and at 3·1 mm L N the following cartilaginous structures were visible: trabecula cranii, auditory capsule, Meckel's cartilage, quadrate, hyosymplectic cartilage, sclerotic, hypohyal, ceratohyal epihyal cartilage, interhyal, hypobranchial 1 and ceratobranchial 1. The only structure ossified at this size is the maxillary and the next ossified structures to appear are the preopercle and opercle at about 3·7 mm L N . The last bones to appear are infraorbital 2 and 6 at 15·1 mm L S . The first cartilaginous elements and structures to ossify in S. aurata appear to be related with functional requirements, so that structures involved directly in feeding and breathing generally appear and ossify before those that are not. The ontogeny of different regional structures revealed that generally the dermal bones ossify before the cartilage replacement bones. Comparison of S. aurata viscerocranial skeleton ontogeny with that of phylogenetically distant fish demonstrates that different ossification strategies exist in higher and lower teleost fish.

Pheochromocytoma cell lines from heterozygous neurofibromatosis knockout mice - J. F. Powers; M. J. Evinger; P. Tsokas; S. Bedri; J. Alroy; M. Shahsavari; A. S. Tischler (Cell and Tissue Research, 2000)

Stratigraphical distribution of platinum-group minerals in the Eastern Layered Series, Rum, Scotland - M. R. Power; D. Pirrie; J. C. Ø. Andersen; A. R. Butcher (Mineralium Deposita, 2000)

The seasonal cycle in coupled ocean-atmosphere general circulation models - C. Covey; A. Abe-Ouchi; G. J. Boer; B. A. Boville; U. Cubasch; L. Fairhead; G. M. Flato; H. Gordon; E. Guilyardi; X. Jiang; T. C. Johns; H. Le Treut; et al. (Climate Dynamics, 2000)

Plant regeneration from embryogenic cultures of Phragmites australis (Cav.) Trin. Ex Steud. - Csaba Máthé; Márta M. Hamvas; István Grigorszky; Gábor Vasas; Erika Molnár; J. Brian Power; Michael R. Davey; George Borbély (Plant Cell, Tissue and Organ Culture (PCTOC), 2000)

Combined PI–DAPI staining (CPD) reveals NOR asymmetry and facilitates karyotyping of plant chromosomes - S. C. Andras; T. P. V. Hartman; J. Alexander; R. McBride; J. A. Marshall; J. B. Power; E. C. Cocking; M. R. Davey (Chromosome Research, 2000)

Environmental influences on an exploited anadromous Arctic charr stock in Labrador - M. Power; J. B. Dempson; G. Power; J. D. Reist (Journal of Fish Biology, 2000)
Arctic charr Salvelinus alpinus at Nain, Labrador, were influenced by recent variability in measured environmental variables and able to mitigate partially the effects of past conditions in a single year. Weather conditions prevailing during the first winter and sea migration life‐stages also exerted significant influence on measured age and weight characteristics and are argued to play a role in determining the population dynamics of exploited stocks.

Temporal abundance patterns and growth of juvenile herring and sprat from the Thames estuary 1977–1992 - M. Power; M. J. Attrill; R. M. Thomas (Journal of Fish Biology, 2000)
Most herring Clupea harengus and sprat Sprattus sprattus sampled from West Thurrock power station intake screens, middle Thames estuary, between 1977 and 1992 were age‐0 and followed regular patterns of seasonal occurrence. Juvenile herring entered the estuary in July, peaked in abundance November to March, and then declined. Juvenile sprat first appeared in September and peaked in abundance in January. Neither species was abundant in summer samples. While in the estuary, herring and sprat increased in length an average of 4·0 and 0·33 cm respectively. Abundance of both species was significantly affected by temperature, temporal trend, shoaling behaviour and seasonal variables, and of herring by suspended solids. Interactions between environmental variates did not influence the abundance of either species. As estuarine clupeids were influenced by a complex set of events within and outside the estuary, estuarine monitoring studies alone will not be sufficient for understanding the changes in estuarine fish communities resulting from future human activity.

The effect of food deprivation and refeeding on the liver, thyroid hormones and transthyretin in sea bream - D. M. Power; J. Melo; C. R. A. Santos (Journal of Fish Biology, 2000)
There was a significant reduction in body weight of sea bream Sparus aurata and the hepatosomatic index after 3 weeks food deprivation. Liver biochemical indices and morphology were altered by food deprivation, there was a loss of eosin staining in hepatocyte cytoplasm and the appearance of large depleted vacuoles. Cell and nuclear area were significantly reduced ( P T 3 (33·98±12·47 ng ml ‐1 ) and T 4 (16·54±9·5 ng ml ‐1 ) was significantly ( P 0·001) lower than the control (66·52±13·4 and 56·83±7·3, respectively). Refeeding for 1 week restored circulating T 3 ( P 0·05) close to control levels but did not significantly affect the concentration of T 4 . Northern blotting with an homologous probe for transthyretin (TTR) demonstrated clearly the expression of a single mRNA transcript of 0·7 kb for this protein in the liver. The level of TTR message was substantially reduced below control levels in the liver of fasted fish and 1 week refeeding failed to restore expression.

A Drop-spreading Technique to Produce Cytoplasm-free Mitotic Preparations from Plants with Small Chromosomes - S. C. Andras; T. P. V. Hartman; J. A. Marshall; R. Marchant; J. B. Power; E. C. Cocking; M. R. Davey (Chromosome Research, 1999)

Cefotaxime-Hydrolysing Beta Lactamases in Morganella morganii - P. Power; C. de Mier; M. Mollerach; M. Maltagliatti; G. Gutkind; A. Famiglietti; M. Radice; C. Barberis; C. Vay (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Expression of a chimeric nitrate reductase gene in transgenic lettuce reduces nitrate in leaves - I. S. Curtis; J. B. Power; A. M. M. de Laat; M. Caboche; M. R. Davey (Plant Cell Reports, 1999)

Increased stable inheritance of herbicide resistance in transgenic lettuce carrying a petE promoter-bar gene compared with a CaMV 35S-bar gene - M. S. McCabe; F. Schepers; A. van der Arend; U. Mohapatra; A. M. M. de Laat; J. B. Power; M. R. Davey (Theoretical and Applied Genetics, 1999)

Intergeneric somatic hybrids of rice [Oryza sativa L. (+) Porteresia coarctata (Roxb.) Tateoka] - N. B. Jelodar; N. W. Blackhall; T. P. V. Hartman; D. S. Brar; G. Khush; M. R. Davey; E. C. Cocking; J. B. Power (Theoretical and Applied Genetics, 1999)

Evidence for anadromy in a southern relict population of Arctic charr from North America - R. R. Doucett; M. Power; G. Power; F. Caron; J. D. Reist (Journal of Fish Biology, 1999)
Stable isotope analysis of Arctic charr from a southern relict population in Québec showed that some individuals adopted anadromy as a life‐history strategy, but the strategy did not predominate in the population. Differences in length‐at‐age, ages and sex ratios between identified freshwater residents and anadromous individuals were consistent with previous descriptions of partially migratory populations. This suggests that anadromy in relict populations in Québec is associated with niche shift and occurs as a conditional response to opportunities for maximizing the rewards (e.g. fitness) of habitat use.

Development of the pectoral, pelvic, dorsal and anal fins in cultured sea bream - M. Faustino; D. M. Power (Journal of Fish Biology, 1999)
The pectoral fin girdle was the first element of the fins to develop in Sparus aurata. By 3·1mm L N (notochord length) the cleithrum was ossified and the cartilaginous caracoid‐scapula was present. The fin was fully developed at 11·6 mm L S (standard length) and by 16·0 mm L S most elements of the fin were ossified. The pelvic fins were the last pair to develop and rudiments of these were first detected at 7·9 mm L S . The pelvic fin and girdle were completely formed and ossified at 16·0 mm L S . The development of dorsal and anal fins began at c. 6·5–7·0 mm L S with the formation of 10 cartilaginous dorsal proximal radials and eight cartilaginous ventral proximal radials. The three cartilaginous predorsals (supraneurals) appeared at 7·7 mm L S and the ossification of dorsal and anal proximal and distal radials began, respectively, at 10·5 mm L S and 11·3 mm L S . Ossified structures in the fins were also classified according to their origin, as being either dermal or endochondral. Finally the chronology of appearance of fin structures in S. aurata was compared with that reported for other Sparidae, Engraulidae and Haemulidae.

A stable transformation system for the ornamental plant, Datura meteloides D. C. - I. S. Curtis; J. B. Power; P. Hedden; D. A. Ward; A. Phillips; K. C. Lowe; M. R. Davey (Plant Cell Reports, 1999)

Use of the Polymerase Chain Reaction for Rapid Detection of High-Level Mupirocin Resistance in Staphylococci - R. M. Anthony; A. M. Connor; E. G. M. Power; G. L. French (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Stress-inducible transgenic nematodes as biomonitors of soil and water pollution - R S Power; H E David; M H A Z Mutwakil; K Fletcher; C Daniells; M A Nowell; J L Dennis; A Martinelli; R Wiseman; E Wharf; D I de Pomerai (Journal of Biosciences, 1998)

Seismic image of the Mount Spurr magmatic system - J. A. Power; A. Villaseñor; H. M. Benz (Bulletin of Volcanology, 1998)

A comparison of methods for direct gene transfer into maize (Zea mays L.) - E. M. Southgate; M. R. Davey; J. B. Power; R. J. Westcott (In Vitro Cellular & Developmental Biology - Plant, 1998)

Development of osteological structures in the sea bream: vertebral column and caudal fin complex - M. Faustino; D. M. Power (Journal of Fish Biology, 1998)
The development of cartilaginous structures in cultured sea bream Sparus aurata larvae and the timing of their ossification was studied. In cultivated sea bream larvae the first cartilaginous structure to be identified was hypural 1 at 4.1 mm notochord length ( L N ). By 5.3 mm L N , prior to the onset of ossification, it was possible to distinguish the following cartilaginous structures: all 23 neural arches, all 13 haemal arches and two of the four pairs of parapophyses. The neural arches 1–4 and 15–23 were formed on the notochord and elongated dorsally, while neural arches 5–14 appeared on the dorsal side of the spinal cord and elongated ventrally. Initiation of ossification occurred at 5.7–6.0 mm standard length ( L S ) when the cartilaginous ontogeny of the vertebral column was completed. Ossification was coincident with dorsal flexion at the posterior end of the notochord and occurred in a sequential manner: (1) dorsoanteriorly, the cartilaginous neural arches and the centra were the first structures to ossify; (2) ventrad at the centre, at 7.0–7.5 mm L S ; (3) posteriorly at 7.1 mm L S the hypural complex and urostyle (24th centrum) were ossified; and (4) dorsad at the centre (neural arches and spines).

Shoot regeneration from cultured root explants of spinach (Spinacia oleracea L.): a system for Agrobacterium transformation - K. A. Knoll; K. C. Short; I. S. Curtis; J. B. Power; M. R. Davey (Plant Cell Reports, 1997)

The role of larval retention and transport features in mortality and potential gene flow of walleye pollock - K. M. Bailey; P. J. Stabeno; D. A. Powers (Journal of Fish Biology, 1997)
This paper reviews the physical oceanography in the range of walleye pollock that influences transport and mortality of eggs and larvae, and summarizes the current status of stock structure studies of pollock. A synthesis is presented that links the genetic stock structure and the potential for gene flow due to transport. In the eastern North Pacific Ocean, walleye pollock Theragra chalcogramma consistently spawn in several locations, with the major deposition of planktonic eggs in Shelikof Strait in the Gulf of Alaska and in the eastern Bering Sea, near Unimak Pass. In the Gulf of Alaska, eddies are common features where pollock larvae tend to be concentrated; eddies in the region of Shelikof Strait retain larvae in the region, where they are protected from transport offshore in the Alaska Coastal Current (ACC). The ACC is vigorous in Shelikof Strait (20–50 cm s −1 ), but in the downstream region along the Alaska Peninsula it flows over the continental shelf and is more sluggish (10 cm s −1 ). There is equivocal information on the condition and mortality of larvae inside and outside eddies; there may be seasonal and interannual differences in the direct role of eddies on larval mortality. In some years with extremely high storm activity, resulting in a very energetic ACC, eddies are less prevalent and pollock larvae are swept offshore into the swift flowing Alaskan Stream (50–100 cm s −1 ). In the Alaskan Stream the nutritional condition and growth of larvae is poor, leading to high mortality. Satellite‐tracked drifter trajectories indicate that Alaskan Stream water can enter the Bering Sea through deep Aleutian passes, the nearest (easternmost) being Amutka Pass. Larvae surviving in the Alaskan Stream and carried into the Bering Sea through Amutka Pass would find themselves in the Aleutian Basin, where feeding conditions are poor and where larval mortality has been high. Therefore, geographical barriers (such as the Alaska Peninsula and shallow sills at passes between the Gulf of Alaska and Bering Sea), retention features, and high mortality rates of vagrants are likely to impede gene flow due to larval drift between the Gulf of Alaska and eastern Bering Sea. Recent findings using restriction fragment length polymorphism (RFLP) analysis of mtDNA variation, further supported by differences in nuclear DNA microsatellite loci, indicate distinct genetic stocks in the Bering Sea and Gulf of Alaska. Within the Bering Sea, several geographically separate pollock spawning grounds result in larvae occupying a variety of basin, slope and shelf habitats. Larvae can be concentrated in eddies in slope waters, but on the eastern Bering Sea shelf eddies are uncommon and a persistent mean northwestward flow exists along the 100‐m isobath. Thus, the potential for gene flow through larval drift is much higher. Genetically distinct stocks have not been identified in the eastern Bering Sea, although there is some evidence for their existence.

Somatic embryogenesis and plant regeneration from stem explants of Moricandia arvensis - W. Craig; A. Wiegand; C. M. O'Neill; R. J. Mathias; J. B. Power; M. R. Davey (Plant Cell Reports, 1997)

Carbon dioxide-gassed fluorocarbon enhances micropropagation of rose (Rosa chinesis Jacq.) - J. Wardrop; K. C. Lowe; M. R. Davey; R. Marchant; J. B. Power (Plant Cell Reports, 1997)

Strategies for promoting division of cultured plant protoplasts: synergistic beneficial effects of haemoglobin (Erythrogen) and Pluronic F-68 - P. Anthony; K. C. Lowe; M. R. Davey; J. B. Power (Plant Cell Reports, 1997)

Perspectives of the Scientific Community on the Status of Ecological Risk Assessment - M. Power; S. M. Adams (Environmental Management, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Homoeologous pairing and recombination in backcross derivatives of tomato somatic hybrids [Lycopersicon esculentum (+) L. peruvianum] - A. S. Parokonny; J. A. Marshall; M. D. Bennett; E. C. Cocking; M. R. Davey; J. Brian Power (Theoretical and Applied Genetics, 1997)

Egg removal and intraspecific brood parasitism in the European starling (Sturnus vulgaris) - M. P. Lombardo; H. W. Power; P. C. Stouffer; Linda C. Romagnano; Ann S. Hoffenberg (Behavioral Ecology and Sociobiology, 1989)

Factors influencing time to breakdown (TTB) of cooked potato tissue - W. M. Iritani; M. J. Powers; L. Hudson; L. Weller (American Journal of Potato Research, 1977)

Microbial interactions: Population and sporulation studies ofBacillus sphaericus grown in association withErwinia atroseptica - D. A. Power; M. J. Pelczar (Antonie van Leeuwenhoek, 1964)